Construction of Ni3S2/NiFe-LDH heterostructure via in-situ sulfidation for enhanced electrocatalytic urea oxidation with overall water splitting - Feng Fu; Min Wang; Jili Ren; Jindou Hu; Zhenjiang Lu; Jing Xie; Yali Cao (Fuel, 2027)

A probabilistic pedotransfer function for estimating the soil water characteristic curve and quantifying its uncertainty - Xin-Yuan Wang; He-Fu Pu; Ming Min; Yu Miao; Sen-Lin Xie; Xiao He (Computers and Geotechnics, 2027)

Three-dimensional global and local stability analysis of slurry trenches in spatially variable soils - Fu Huang; Wenqiang Xu; Min Zhang; Lu Chen (European Journal of Environmental and Civil Engineering, 2026)

Unlocking the microbial aerobic denitrification potential in reservoirs and lakes: Development of a novel aerobic denitrifying fungal medium and its practical application - Haihan Zhang; Lunpei Chen; Ben Ma; Xiang Liu; Xiaoyan Liu; Fengrui Li; Min Fu; Tinglin Huang; Kang Wang; Guoqiang Xi; Boris Adamovich; Dmitry B. Kosolapov (Water Research, 2026)

ε-Polylysine inhibits Alternaria alternata through membrane-targeted antifungal activity and N-glycosylation modification - Wenhui Xu; Min Wang; Hao Jiang; Yangyang Sun; Yamin Du; Maorun Fu (Postharvest Biology and Technology, 2026)

Decoding mitochondrial apoptosis in ischemic stroke via a miR-21a-3p/Plaur-centered regulatory network - Zhongwei Zhang; Yingying Li; Jincheng Yu; Chaojian Li; Shujuan Su; Xiaobo Wang; Min Wang; Shasha Wang; Jin Zhuo; Qiao Fu (Molecular Biology Reports, 2026)

High spatial variations of potential nitrification and N2O production across the Yangtze River and associated major tributaries - Caixia Lan; Qiuxun Lin; Mengting Qi; Yuxuan Fu; Guosen Zhang; Ye Li; Min Liu; Lijun Hou; Xiaofei Li (Water Research, 2026)

Direct and indirect impacts of road networks on vegetation cover - Ziheng Huang; Qingjie Fu; Huixin Lin; Jingyang Liu; Lanyi Zhang; Min Wu; Xisheng Hu (Transportation Research Part D: Transport and Environment, 2026)

A novel control strategy: Suppressing histone acetyltransferase ClHAC703 with curcumin to prevent germination of the invasive weed Cenchrus longispinus - Xiao-Min Han; Jia-Ying Wang; Yan-Ping Fu; Bin Guo; Wei He; Ya-Hui Wei (Plant Science, 2026)

Engineered small extracellular vesicles–integrated multifunctional hydrogel reprograms the wound immune microenvironment for accelerated skin repair - Zhong Liu; Xinyu Zhu; Jun Cheng; Kewei Li; Yang Lou; Xiaopeng Sun; Yuhong Fan; Min Wang; Hui Qian; Yanbin Liu; Hua Ding; Song Guo; et al. (Chemical Engineering Journal, 2026)

Targeted emission controls for ozone pollution mitigation based on mesoscale weather pattern classifications in China’s Pearl River Delta region - Aoxing Zhang; Jiongkai Chen; Huiran Feng; Wei Tao; Jiajia Mo; Wenlu Wu; Jianfeng Guo; Tianle Sun; Long Yun; Min Yan; Xiaolin Wang; Tzung-May Fu (ENGINEERING Environment, 2026)

Rapid and sensitive on-site detection of PBoV G3 using an EsCas13d-based platform - Peng-fei Fu; Zhuo-wei Zhang; Jun Hong; An-xin Hu; Yi-yang Shi; Jia-wen Lin; Si-yi Pi; Yu-yan Zhang; Yan-hong Wang; Min Lu; Guo-you Yin; Dong-mei Wang (Analytica Chimica Acta, 2026)

Additional records of Late Devonian seed plants in South China - Deming Wang; Min Qin; Peng Xu; Yi Zhou; Le Liu; Pu Huang; Qiang Fu; Yuehan Pan (Review of Palaeobotany and Palynology, 2026)

Temporal germination of lettuce under salinity and nano-silicon: A high-throughput phenomics framework with deep learning - Mohamed Ahmed Moustafa; Min Kang; Xiuqing Fu; Luxu Tian; Hanghang Li; Penghong Shen; Ziyi Zhang; Jianzhe Zhou; ChenXu Zhu; Junxiang Cheng; Sanglu Yang; Ahmed Elsayed Mahmoud Fodah; et al. (Plant Science, 2026)

Analytical modeling for uplift resistance of subsea pipelines in loose sand: Local flow-around failure mechanism and smooth-pipe validation - Xiao-Mi Li; Yu-Min Shi; Ning Wang; Xiao-Bing Lu; Fu-Ping Gao (Ocean Engineering, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

New insights into the changes of structure-activity characteristics from dark beer melanoidins through different chemical treatments and in vitro digestion and fermentation - Yaning Nie; Ting Xia; Yihong Fu; Yixie Chen; Jun Wang; Nannan Zhang; Shuxia Huang; Junhong Yu; Min Wang (Food Research International, 2026)

Optimized 3D hierarchical canopy Modeling of urban street trees for enhanced microclimate regulation - Yapeng Shao; Tailong Zhang; Xiaotong Fu; Youjun Liu; Hong Pan; Min Wan; Feng Qi; Yamei Shen (Energy and Buildings, 2026)

Two-pronged strategy of pore size sieving and recognition sites tailoring for perfluoropropylene-perfluoropropane separation - Zongzhen Han; Meiting Wang; Meng Gao; Kunhua Wang; Hao Yu; Zhiguo Bian; Ruitao Lv; Wei Chen; Liangmin Ning; Min Fu (Chemical Engineering Journal, 2026)

Multi-dimensional high-security encryption based on electrochemiluminescence steganography and cryptography - Chukai Lin; Wenxuan Fu; Min Qi; Yidan Rong; Yafeng Wang; Bin Su (Chemical Engineering Journal, 2026)

Bioinspired selective cell lumen densification for high-loading transparent cellulosic fiber composites with controlled light scattering - Yue Li; Jiawei Fu; Min Wang; Qiliang Fu; Liping Cai; Changlei Xia; Quanliang Wang (Carbohydrate Polymers, 2026)

Non-denaturing fluorescence in situ hybridization: a transformative tool for chromosome identification and engineering for crop improvement in the plant genomics era - Chengzhi Jiang; Guangrong Li; Min Wan; Ennian Yang; Shulan Fu; Zongxiang Tang; Peng Zhang; Zujun Yang (Planta, 2026)

Finite strain pattern inferred from magnetic fabrics across the southern portion of the Central Range, Taiwan - Ya-Chu Tseng; En-Chao Yeh; Ning-Shan Hui; Yu-Min Chou; Jian-Cheng Lee; Ching-Chou Fu (Tectonophysics, 2026)

Understanding variation in sustainable development goal relationships across spatial scales matters for making consistent priorities - Kai Wu; Junze Zhang; Prajal Pradhan; Cameron Allen; Min Cao; Jian Lin; Zhongchang Sun; Zheng Hu; Ya Tian; Guonian Lü; Huadong Guo; Bojie Fu; et al. (Sustainable Production and Consumption, 2026)

Co-treatment of arsenic-rich dust and iron-bearing slag by reduction smelting: Arsenic immobilization, phase transformation, and environmental stability - Fei Chai; Jianhua Wang; Yuan Zhou; Zelin Fu; Yuling Tu; Yanjie Liang; Xiaobo Min; Liyuan Chai (Process Safety and Environmental Protection, 2026)

Exopolysaccharides from Enterococcus faecium alleviate cadmium damage in rice seedlings via regulating soil-root nitrogen metabolism - Min Zhong; Min Li; Chun-na Zhong; Zu-xuan Yan; Wei-fu Peng; Xin Cheng (Journal of Environmental Sciences, 2026)

Oat protein-EGCG-sugar beet pectin ternary complexes: Role of pectin in driving non-covalent interactions and improving functional properties - Zihao Chen; Muyao Luo; Taotao Dai; Min Fu; Zhaoying Li; Qin Geng; Jun Chen; Ti Li; Risi Wang (Food Hydrocolloids, 2026)

Synergistic electrocatalytic reduction-oxidation cascade for efficient degradation of triclosan over an optimal amino-ionic liquid functionalized CoNi/RGO cathode - Dandan Xu; Xueli Xie; Han Zhou; Qin Zhang; Yanan Zhang; Min Huang; Yijian Zhong; Mingming Fu; Shaoyuan Bai (Environmental Research, 2026)

Low-dose arsenate promotes high-efficiency anammox: From granular properties to synergistic metabolism - Que Wang; Xiao-Wei Xu; Zhang-Yi Wang; Hong-Yuan Liu; Lei Wang; Hui-Ming Fu; Ya-Min Liu; Peng Yan; Ling-Ling Wang; You-Peng Chen (Chemical Engineering Journal, 2026)

Cosolvent-driven exciton delocalization and dual dissociation pathways enable high-efficiency inverted all-polymer solar cells - Jia-Fu Chang; Hui Chan Ahn; Sunil V. Barma; Cheng-Yu Yeh; Yu-Cheng Tseng; Hyun Min Kwon; Hyerin Jeon; Hsu-Tzu Cheng; Bumjoon J. Kim; Sae Byeok Jo; Chu-Chen Chueh (Chemical Engineering Journal, 2026)

Synergistic regulation of bimetallic d-band centers in NiM-NiMOx (M = Co/Cu) catalysts toward enhancing selective hydrogenation - Liangmin Ning; Jun Xie; Shiyan Sheng; Jiawen Wang; Tianyu Zhang; Shuai Li; Shuanglu Fu; Tianqi Xie; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Joule-thermal desert-beetle-inspired mesh for efficient purification of viscous emulsified kitchen oil - Jiawei Sun; Runtang Cai; Xiangyu Huang; Jialuo Dai; Huan Fu; Xinjuan Zeng; Limiao Lin; Penghui Li; Min Zhang (Journal of Water Process Engineering, 2026)

Chronic intermittent hypobaric hypoxia ameliorates iron metabolism disorder through ferritinophagy in collagen-induced arthritis mice - XueRui Fu; Fang Cui; RuoTong Wang; Shuang Liu; YunLu Zhao; AiJing Liu; BingYan Guo; Chen Jia; ManNa Zhang; Di Hao; Min Shi (Journal of Trace Elements in Medicine and Biology, 2026)

Understanding of deep groundwater age characteristics in the Yangtze River Delta through the combined use of 14C and 81Kr - Shiang Lu; Zhaojun Xie; Xin Dai; Wei Jiang; Yueqing Xie; Andrew J. Love; Xulong Gong; Guo-Min Yang; Yan Zhang; Lei He; Zheng-Tian Lu; Rongbing Fu; et al. (Journal of Hydrology, 2026)

Advances in goat milk–derived bioactive peptides: Angiotensin-converting enzyme-inhibitory and antioxidant properties - Wanning Ma; Lei Liang; Haofeng Gu; Zhenbao Zhu; Min Du; Jiahao Wang; Yuyu Fu; Jiaxue Hu; Xin Nan; Tingshu Chen; Yuexin Chen; Yang Liang (Food Bioscience, 2026)

The heterojunction regulated by Au nanoparticles efficient removal of NO through the synergistic effects of SPR and the electron bridge - Youzhou He; Zhiqiang Guo; Yue Li; Xingyan Liu; Kaili Wu; Yuyu Fang; Rong Peng; Min Fu; Bowen Lei (Environmental Research, 2026)

Next-Generation Hepatocyte Expansion: Bridging Molecular Reprogramming with Multicellular Organoids for Clinical Translation - Yiyang Zhou; Min Zeng; Gongbo Fu; Yi Gao (Stem Cell Reviews and Reports, 2026)

Deciphering the role of biochar type and particle size in anaerobic co-digestion of food waste and waste activated sludge under thermophilic conditions - Yuwei Yang; Min Zhang; Changhao Zheng; Xiaomei Su; Feng Dong; Xiao Xiao; Liang Xu; Hailu Fu; Faqian Sun (ENGINEERING Environment, 2026)

Long-term trends and risk regulation of heat exposure in megacities: seasonal dynamics and determinants - Ziwen Jin; Shuyi Zhang; Ke Zeng; Muyao Ma; Yue Yang; Yuling Fu; Hanxin Tang; Shan Yin; Ji Zheng; Min Liu (Environment, Development and Sustainability, 2026)

Inhibitory effect of gut microbiota-fermented trisaccharide GuFGa (Glc-Fuc-Gal) on Campylobacter jejuni: insights from transcriptomic and metabolomic analyses - Xinmiao Ren; Shuang Li; Changyun Wang; Francesco Secundo; Ningyang Li; Mengshi Xiao; Min Yang; Rong Li; Qing Kong; Han Sun; Xiaodan Fu; Haijin Mou (Marine Life Science & Technology, 2026)

Molecular unraveling of Li+-solvent interaction reversal and its impact on low-temperature desolvation for weakly solvated electrolytes - Yanyan Zhang; Yuxin Liu; Jia-Yan Liang; Min Niu; Yu Zhang; Xingyu Chen; Lulu Fu; Shuang-Yan Lang; Sen Xin; Chunhui Yang; Fuyi Wang; Yu-Guo Guo (Science Bulletin, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Characterization of wheat starch–safflower seed oil complex and its effects on noodle quality and starch digestibility - Xiaochun Zheng; Xiaoxiao Liu; Jing Wang; Yini Fu; Meina Cheng; Li Tai; Xinwen Xu; Laizhong Wang; Yi Zhao; Min Liu; Wenyu Liu; Changqing Wei (Food Chemistry, 2026)

Underestimation of industrial contributions to VOC fluctuation in the Hangzhou Bay: Insights from simultaneous measurements and ML-SHAP analysis - Kun Hu; Song Guo; Lei Shen; Zichao Wan; Xinshi Ni; Rui Tan; Xudong Tian; Bingye Xu; Limin Zeng; Qingyan Fu; Min Hu; Sihua Lu (Environmental Pollution, 2026)

Upgrading H2/CO2-containing waste gas to single cell protein: Tolerance and response of Cupriavidus necator H16 to hydrogen sulfide - Jie Wang; Rui Li; Manqian Wang; Xuening Wang; Min Xue; Ankun Xu; Kai Luo; Xiaolei Fan; Rongbo Guo; Shanfei Fu (Chemical Engineering Journal, 2026)

Alginate-based composite hydrogel derived from Azotobacter vinelandii Av1: Preparation, properties, and wound-healing efficacy - Peng Yang; Rongqiang Chen; Siyuan Peng; Lin Zhu; Yifei Chang; Zhi Bao; Xiaodan Fu; Mengshi Xiao; Min Yang; Haijin Mou (Carbohydrate Polymers, 2026)

Human Amniotic Fluid Stem Cell-mediated Biomechanical Restoration of Urinary Continence in Rats - Shing-Hwa Lu; Shiaw-Min Hwang; Navneet Kumar Dubey; Ming-Song Tsai; Tien-Fu Yun; Jiunn-Wang Liao (Tissue Engineering and Regenerative Medicine, 2026)

Generating Microglia-Integrated Cortical Organoids from Human Embryonic Stem Cells - Hongxin Quan; Xianglin Liu; Min Yan; Zongyong Ai; Baohua Niu; Jing Jiang; Hong Chang; Wenxiang Fu; Runrui Zhang (Stem Cell Reviews and Reports, 2026)

Homocysteine-induced bone formation dysfunction reversed by icariin via the AKT/FOXO1 signaling pathway - Suzhen Chao; Yunying Fu; Xinyi Peng; Yili Zhou; Junjie Xia; Ming Chen; Yang Li; Shengyuan Li; Min Shi; Xunli Xia; Bo Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Identification and pathogenicity of fungal pathogens associated with Morchella sextelata rot - Yiwen Fu; Min Yang; Zhao Huang; Xi Xu (Journal of Plant Pathology, 2026)

E-Syt1 recruits PI4KA to endoplasmic reticulum-plasma membrane junctions to enhance PI4P synthesis - Chunfang Tong; Ranran Mao; Dou Wang; Jing Xi; Min Su; Wenfeng Fu; Dong Li; Jia-Jia Liu (Science China Life Sciences, 2026)

The impact of borneolum on Citalopram hydrobromide pharmacokinetics and serotonin levels in the hypothalamus of conscious rats - Jing Wu; Fu-He Liu; Xiao-Liang Zhao; Min-Chen Liu (Natural Product Research, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Light-driven community assembly and functional performance of aeration-free filamentous algae–partial nitrification/anammox granule - Cui-Zhong Chen; Hui-Min Fu; Tong-Xu Li; Xiao-Yu Gao; Qing Hu; Peng Yan; Jin-Song Guo; Xiao-Wei Xu; You-Peng Chen (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Genome-wide analysis of the papaya bZIP gene family identifies CpbZIP52 as a key regulator of fruit postharvest ripening - Meiling Ding; Shanni Cao; Meng Zeng; Min Zhang; Hongya Tang; Xiaochun Chen; Xianqi Fu; Sicheng Bai; Min Yang; Kaidong Liu (Plant Science, 2026)

Investigating the mechanisms of motion response amplification for a cylindrical FPSO under wave-current coupling - Min Li; Da Li; Shenglei Fu; Yuan Zhuang; Decheng Wan (Ocean Engineering, 2026)

Inhibition and metabolic toxicity regulation of niacin on Staphylococcus aureus and its application in meat product preservation - Lei Tian; Xiangqi Bai; Chunyang Huang; Min Li; Ting Zhou; Chunling Zhang; Ying Yu; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

Mg–K isotopic compositions deciphering mantle heterogeneity beneath southeast Tibet - Qiong Chen; Hao Cheng; Guo-Chun Zhao; Mei-Fu Zhou; Ping-Ping Liu; Wen-Jun Li; Min Sun (Geochimica et Cosmochimica Acta, 2026)

Cryoprotective effect of natural deep eutectic solvent combined with sous-vide cooking treatment on the pre-maturation and freeze-thaw cycle of Penaeus vannamei - Jing-jing Fu; Jie Deng; Bo-yang Tan; Yi-shu Ni; Xiu-ping Dong; Si-min Zhang; Yue-wen Chen (Food Chemistry, 2026)

Dynamic cultivar-soil interactions drive accelerating genetic gains in a dryland wheat system - Yuan Li; Yong-He Zhu; He-Peng Lu; Neng Wang; Fu-Ying Cheng; Yan-Lei Du; Feng-Min Li (Field Crops Research, 2026)

Resolving multi-metal encapsulation in coal gasification slag via an integrated activation and selective-separation strategy - Xiaoye Hong; Min Fu; Yanbing Gong; Qiqi Li; Zhe Sun; Yongfeng Zhang; Yinmin Zhang; Xiang He (Chemical Engineering Journal, 2026)

Contrasting responses of bacterial-mediated soil organic phosphorus transformations to varying rates of nitrogen addition in a Cunninghamia lanceolata plantation - Xiang Zhang; Qiong Zhao; Li-Man Wei; Lin-Hui Wu; Xiang-Min Fang; Yong-Hong Ma; Fu-Sheng Chen (Applied Soil Ecology, 2026)

VHL Suppresses Angiogenesis Through HIF-1a-Mediated Ang/Tie2/AMPK/VEGF Signaling Pathway in Tie-2 Expressed Macrophages (TEMs) - Min-Cheng Zou; Yu-Hao Yang; Yun-Peng Mao; Ya Liu; Hui-Bing Gao; Wen-Dong Liu; Jia Liu; Fu-Yong Zhang (Biochemical Genetics, 2026)

A novel ZNF263-SMOX-ROS-TRIB3 signaling axis drives Wnt/β-catenin activation and metastatic progression in colorectal cancer - Longhe Sun; Youlei Zhang; Xianhu Zhang; Jiajie Zhou; Lili Ji; Ruiqi Li; Shuai Zhao; Yayan Fu; Jie Wang; Min Tang; Wei Wang; Chunhua Qian; et al. (Apoptosis, 2026)

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Neurovascular decoupling is associated with altered glymphatic function as assessed by the DTI-ALPS index in patients on dialysis - Wenbo Yang; Lijun Song; Mingan Li; Xiaoyan Bai; Boyan Xu; Min Li; Zhenghan Yang; Tiantian Ma; Yong Gong; Gang Fu; Wenjing Zhao; Jing Zhao; et al. (Brain Imaging and Behavior, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Interpretable prediction of undrained shear strength in deep-sea soft clays using SHAP and symbolic regression - Gai-Yun Huang; Fu-Ping Gao; Yu-Min Shi; Jian-Tao Liu (Ocean Engineering, 2026)

Digital disaster prevention for ocean engineering: Current progress and future directions - Zhen-Zhong Hu; Yilin Li; Fu-Ping Gao; Jian-Min Zhang (Ocean Engineering, 2026)

Decoding the flavor formation mechanism of the functional microbial community in koji-mediated fish sauce - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Antibacterial and antioxidant tetracycline-functionalized carbon dots nanocomposite films for enhanced fruit preservation - Xueyu Fu; Yao Chen; Kairui Wang; Min Zheng (Food Control, 2026)

Dense planting coupled with optimized irrigation improves rice yield while reducing Cd level in rice grain and CH4 emission from field - Zhiwei Tang; Xin Zhang; Aixing Deng; Jun Zhang; Zhenwei Song; Xiangcheng Zhu; Jin Chen; Min Xie; Fu Chen; Weijian Zhang (Field Crops Research, 2026)

Sulfobetaine-modified palladium nanozyme for alleviating ulcerative colitis via RONS scavenging and microbiome remodeling - Chaoyue Sun; Min Feng; Ting Yang; Hongjia Song; Jinbin Wang; Chang Peng; Haiyan Zhang; Xiangli Zhong; Zhao Fu (Chemical Engineering Journal, 2026)

Crosstalk-free dual-mode electronic skin enabled by selective electrospinning and machine learning-based decoupling - Chu Qin; Qingyin Sun; Chuheng Fu; Keyi Shan; Yuxin Sun; Min Wang (Chemical Engineering Journal, 2026)

The proteomic blueprint of human aging: a 50-year, 13-tissue atlas - Matthew X. Fang; Tian-Min Fu (Science China Life Sciences, 2026)

Gene-Environment Interaction of Rims1 and Adolescent Social Isolation on Schizophrenia-Like Behaviors in Mice - Lian-Hong Lin; Wei-Min Li; Qian-Yun Wu; Shuang-Yan Li; Xu-Xuan Ma; Yuan Xu; Si-Fu Deng; Bin Zhang; Ji-Hong Liu (Neuroscience Bulletin, 2026)

Revisiting the Peripheral Nerve Injury and Regeneration - Zhen-Gang Liu; Yun-Long Zou; Min-Xin Zhang; Fan Yang; Peng-Fu Li; Bo-Yin Zhang (NeuroMolecular Medicine, 2026)

Quantifying soil micro-element state distribution and predicting tillage performance during sodic saline-alkali subsoiling based on mathematical model and DEM simulation approach - Min Liu; Jinchun Sun; Pinyan Lv; Dongyan Huang; Da Qiao; Yingjie Guo; Weizhi Feng; Daping Fu; Limin Jiang; Jingli Wang (Computers and Electronics in Agriculture, 2026)

Strong tri-genic epistasis among natural alleles of the OsMYB2–OsGH18–OsCAD3 module enhances drought tolerance in rice - Mingyue Huo; Shanwen Wang; Fan Zhang; Min Li; Ming Yin; Yuxin Lei; Yanfang Wang; Yanjun Chen; Dapu Liu; Xiuqin Zhao; Binying Fu; Fengyi Hu; et al. (Molecular Plant, 2026)

The enhancing effect of interfacial polymerization on the corrosion resistance and the preparation of PVDF hollow fiber membranes - Min Fang; Wenshuai Fu; Zhenyu Li; Feng Liu; Shusu Shen; Renbi Bai; Xiaoji Zhou (Journal of Water Process Engineering, 2026)

Phosphorus sequestration dynamics in sediments: Performance evaluation of multi-type phosphorus-locking agents under controlled conditions - Qinqin He; Shaojie Fu; Lintao Wang; Guoqing He; Zedong Teng; Xin Zhao; Kuo Pang; Min Li (Journal of Environmental Chemical Engineering, 2026)

The π-π stacking induced strong built-in electric field in g-C3N4/PdTCPP-HOFs S-scheme heterojunction for efficient H2 evolution - Qinghong Cai; Chenghua Zhang; Hongchuan Ye; Youzhou He; Yongcheng Feng; Huiqi Qin; Min Fu; Bowen Lei (Journal of Environmental Chemical Engineering, 2026)

Metabolomic investigation of flavor and metabolite evolutions in the submerged fermentation of miiuy croaker (Miichthys miiuy) surimi induced by Monascus purpureus - Wenjia He; Min Wang; Tao Zhou; Sufang Fu; Kang Chen; Yuting Ding; Xuxia Zhou (Food Chemistry, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Multifunctional gradient SEI design via LUMO-guided assembly toward wide-temperature zinc-ion batteries - Mengyao Shi; Zhengtai Zha; Fu Li; Yuzhu Wang; Jianfei Su; Min Cheng; Tianjiang Sun; Zhanliang Tao (Chemical Engineering Journal, 2026)

Mn-O bond regulated Fe spin state in FePc/MnO2 heterojunction for efficient oxygen reduction reaction - Min Jiang; Yibo Wang; Yilin Han; Xichen Shao; Ruiqi Cheng; Jiao Zhang; Chaopeng Fu (Chemical Engineering Journal, 2026)

Multi-omics analyses reveal a rhamnogalacturonan I (RG-I) from Polygonum aviculare ameliorates nephrolithiasis through regulation of the gut–kidney axis - Yucheng Ma; Shulei Pan; Tao Yang; Banghua Liao; Mengzhu Yang; Yang Fu; Xi Jin; Dongxue Yang; Chuanmin Chu; Kunjie Wang; Min Zhao (Carbohydrate Polymers, 2026)

Deciphering acetate stress responses in methanogen using D2O-Labeled Single-Cell Raman spectroscopy - Min Li; Xiuxia Meng; Erqi Nie; Dongxue Lu; Rongbo Guo; Shanfei Fu; Jianhua Guo (Bioresource Technology, 2026)

Differential microbial communities and metabolite profiles in the rhizosphere and bulk soils of rubber tree (Hevea brasiliensis) infected with red root rot disease - Xiangjia Meng; Haibin Cai; Yongwei Fu; Keyu Bai; Lifang Zou; Cuicui Wang; Yi Zhou; Min Tu (Plant and Soil, 2026)

Population pharmacokinetic modeling and Monte Carlo simulation–based dosing optimization of trimethoprim–sulfamethoxazole in critically ill patients - Min Wang; Chen Li; Xiangxiang Fu; Fangling Wang; Xiaojun Zhou; Bingli Zhang; Wenya Xu; Liqiu Liang; Zhenlin Lei; Hengxing Qu; Ling Xie; Lili Zhong; et al. (European Journal of Clinical Pharmacology, 2026)

The ATG14: multi-layer autophagy control and an emerging therapeutic target in cancer - Wenbo Wang; Chujuan Yu; Fulin Sun; Ruofeng Wang; Weikai Xia; Qinghang Song; Huhu Zhang; Zhenzhen Jia; Min Zhang; Haoran Wang; Zhenxiang Wang; Rong Fu; et al. (Apoptosis, 2026)

Microbial Responses to Warming Reduce Deep Blue Carbon Storage - Leilei Xiao; Jian Liu; Genevieve L. Noyce; Jaehyun Lee; Carlos M. Duarte; Meng Zhou; Min Luo; Ruifeng Sun; Run Dang; Lifeng Zhou; Lirong Zhang; Chuancheng Fu; et al. (Global Change Biology, 2026)
Coastal wetlands are critical blue carbon reservoirs, yet the depth‐resolved impacts of warming on belowground carbon dynamics remain poorly understood. Over the course of an 8‐year in situ experiment, we investigated plant‐derived carbon inputs, soil carbon losses via respiration, and microbially mediated carbon fixation across a 60 cm soil profile under a projected 2°C atmospheric warming scenario. Plant carbon fixation (above‐ and belowground net primary productivity) and soil respiration exhibited synchronized responses to warming, with an initial increase, followed by a decline in the mid‐term, and no significant response in the later stages. Soil and microbial respiration stabilized after prolonged exposure to elevated temperatures, as these processes were constrained by substrate availability. In contrast, phospholipid fatty acid profiling, amino sugar biomarkers, and metagenome‐assembled genomes consistently indicated a greater than one‐third reduction in microbial carbon fixation within subsoils (40–60 cm). Our fully factorial, depth‐stratified warming design reveals the particular vulnerability of deep soil microbial carbon retention to long‐term climate warming, independent of shifts in plant input or respiratory carbon loss. This work highlights underappreciated pathways influencing soil blue carbon dynamics in a changing world.

Novel Models to Predict Pregnancy for Patients Receiving In-Vitro-Fertilization Embryo Transfer: The Significance of Clinical Indicators and Key Gene Expression in the Endometrium - Cheng Shi; Yan-Bin Wang; Huan Shen; Fu-Mei Gao; Min Fu; Xi Chen; Hong-Jing Han (Biochemical Genetics, 2026)

Diversity loss of soil microbiome stimulates soil carbon emissions - Haibo Pan; Yingyi Fu; Hairong Tu; Yongxing Cui; Beibei Chen; Jiejun Qi; Ziheng Peng; Shi Chen; Chunling Liang; Jiai Liu; Xiaomeng Li; Min Gao; et al. (Soil Biology and Biochemistry, 2026)

Construction of metal-free 1D/2D hybrid through engineered structure evolution strategy for boosting photocatalytic hydrogen production - Jiahui Fu; Pingfan Zhang; Lei Wang; Wenli Zhang; Min Zhang; Yun Wang; Chunmei Li; Hongjun Dong (Journal of Water Process Engineering, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

Dynamic remodeling of intramuscular structural proteins and its impact on abalone muscle quality during post-mortem cold storage - Hua Liu; Tian-Bo Zhang; Fu-Hao Zhang; Le-Chang Sun; Duanquan Lin; Tengchuan Jin; Ling-Jing Zhang; Jia-Yin Huang; Min-Jie Cao; Yu-Lei Chen (Food Chemistry, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Dual MOFs-Derived CdS/In2S3 heterojunction photocatalyst for fast and efficient reduction of Cr(VI) - Hong Wu; Zhuoqi Liu; Tianrong Xiong; Xingyan Liu; Ying Chen; Min Fu; Yue Deng; Yongcheng Feng; Yuyu Fang; Bowen Lei; Youzhou He (Environmental Research, 2026)

Tough, electron-ion conductive, and anti-freezing cellulose nanofiber reinforced hydrogels inspired by honeycomb as flexible wearable sensors for intelligent human health monitoring - Zhengshen Guo; Min Wang; Tong Li; Shengling Xiao; Manyu Zhou; Yuhang Li; Changlei Xia; Chunxia Chen; Qiliang Fu; Quanliang Wang; Shuangfei Wang (Chemical Engineering Journal, 2026)

Modulating d-band center to construct Ptδ–Cuδ+ pairs for selective hydrogenation of renewable furfural - Liangmin Ning; Shuai Li; Shiyan Sheng; Jiuheng Ma; Jiawen Wang; Tianyu Zhang; Shun Wang; Jingyi Han; Jiaoyang Wang; Wei Chen; Meng Gao; Kunhua Wang; et al. (Chemical Engineering Journal, 2026)

Modeling Dynamic Fracturing Behavior of Water-Resisting Rock of Tunnel Under Seismicity Based on a Coupled Hydro-Mechanical Discrete Element Method - Fanmeng Kong; Yiguo Xue; Huimin Gong; Xudong Jiang; Kang Fu; Min Han (Rock Mechanics and Rock Engineering, 2026)

Multi-media distribution, partitioning, and risks of tire additives and their transformation products in coastal waters of China - Chao Liu; Shuang Lu; Min Lv; Longwen Fu; Mingsan Man; Yize Du; Jing Ding; Wei Liu; Lingxin Chen (Marine Pollution Bulletin, 2026)

Water lifting aerators control algal growth in drinking water reservoirs: Performance, mechanism and application - Min Fu; Yue Xu; Xiang Liu; Tinglin Huang; Ben Ma; Fengrui Li; Wanting Shi; Haihan Zhang (Water Research, 2026)

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Synergistic dynamics of the thermal-energy-carbon nexus in the Yangtze River Delta: Spatiotemporal measurement, mechanisms, and spatial econometric analysis - Zhonglin Tang; Yaxin Rao; Min Fu (Sustainable Cities and Society, 2026)

A hybrid Conv-LSTM network with skip connections for nonlinear reduced-order modeling of spatiotemporal flow fields - Min Luo; Siqi Zhong; Jiaxin Wu; Jinlong Fu (Ocean Engineering, 2026)

Discovery of a Late Eocene–Early Oligocene ultra-high temperature (UHT) migmatite in the Gangdese batholith at Nyingchi, southern Tibet and its tectonic implications - Hehe Jiang; Xu Chu; Jia-Min Wang; Wei-Qiang Ji; Wenrong Cao; Fangyang Hu; Xiao-Chi Liu; Fu-Yuan Wu (Lithos, 2026)

Occurrence and sources of organic contaminants of emerging concern in indoor dust: A global perspective - Wei Du; Ruijing Hu; Nan Fu; Min Wu; Yang Liu; Yuanchen Chen; Guofeng Shen; Nan Lin; Bo Pan; Shu Tao (Journal of Hazardous Materials, 2026)

Artificial sweeteners and antibiotics enhance the dissemination and diversity of antibiotic resistance genes in a soil-water continuum - Chen-Xi Fu; Qian Xiang; Ran Li; Na-Qi Cui; Bin Guo; Dong Zhu; Min Qiao (Journal of Environmental Chemical Engineering, 2026)

Precise ligand defect nanoarchitectonics in integrity-preserving 2D Zn-TCPP for efficient photocatalytic H2 evolution - Xingyan Liu; Jianjun Pu; Haibo Zhou; Hongwen Zhang; Yafeng Qian; Min Fu; Yuyu Fang; Youzhou He; Siping Wei (Journal of Environmental Chemical Engineering, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

Lactoferrin-low methoxyl pectin (LMP) composite hydrogels: Mechanical and structural properties tailored by LMP and calcium - Chuanrui Jiang; Wenfei Fu; Zhiyao Ma; Jiayin Wang; Min Zhang; Cuina Wang (Food Hydrocolloids, 2026)

Impact of glycosylation position on functional characteristics and interaction mechanisms in pea protein-flavonoid complexes: A comparative study of genistein and its O-glycosides - Zihao Chen; Wuzhen Liu; Min Fu; Yuanrui Xu; Jun Chen; Qin Geng; Ti Li; Taotao Dai (Food Hydrocolloids, 2026)

Regulating carrier pathways from type-II to S-scheme in g-C3N4-based heterojunctions for synchronous tetracycline degradation and hydrogen evolution - Hong Wu; Lijie Zhou; Lang Sun; Jiaxing Liang; Xingyan Liu; Chenghua Zhang; Min Fu; Jianhui Wu; Youzhou He; Siping Wei (Environmental Research, 2026)

Multiscale modeling and swelling behaviors of Wyoming sodium montmorillonite systems - Zhi-jun Zhang; Jin-xiang Deng; Chang-fu Wei; Ya-kun Tian; Lin Hu; Min Wang; Ling-ling Wu; Kai-wen Tong (Computers and Geotechnics, 2026)

Research advances in arbutin-based materials: synthesis, encapsulation, applications, and trends - Yuanyuan Li; Liwen Sun; Yang Li; Anquan Yang; Min Xie; Ranhua Xiong; Yujie Fu; Chaobo Huang (Chemical Engineering Journal, 2026)

Engineering of ethylene glycol (EG)-trophic Escherichia coli enables fast growth on EG for closed-loop PET biodegradation - Jia-Yu Chen; Sheng-Qi Gao; Qing-Song Huang; Xiao-Min Zhao; Qi-Sheng Fu; Kang-Qi Hu; Yan Huang; Jing Wu; Zheng-Fei Yan (Bioresource Technology, 2026)

Assessing the response of terrestrial water storage to climate warming in China by coupling CMIP6 multi-model ensembles, hydrological model, and machine learning algorithms - Xiaoyan Cao; Jiali Ju; Chuanhao Wu; Pat J.-F. Yeh; Min Shi; Ashraf Dewan; Yongze Song; Xueyuan Zhang; Tian Yao; Yufei Jiao; Qiongfang Li; Shanshui Yuan; et al. (Climatic Change, 2026)

Quantifying nitrate dynamics in deep vadose zone under irrigated farmland in the North China Plain: Insights from continuous in-situ monitoring - Hanbing Jiang; Di Geng; Jiawei Fu; Meiying Liu; Yongqing Qi; Leilei Min; Shiqin Wang; Yanjun Shen (Agriculture, Ecosystems & Environment, 2026)

Comparison of cancer risks associated with JAK inhibitors and TNF inhibitors treatment in patients with rheumatoid arthritis: a systematic review and meta-analysis of real-world cohort studies - Fu-Yu Yang; Yu-Chang Liu; Min-You Wu; Yao-Cheng Wu; Cheng-Hsien Hung (Inflammation Research, 2026)

Computer vision-assisted sorting and selective cultivation of high-activity anammox granules - Shi-Jun Li; Haoran Li; Hui-Min Fu; Yi-Cheng Wang; Xun Weng; Wei Wang; You-Peng Chen (Water Research, 2026)

Modified QuEChERS coupled with hybrid mass spectrometry for 322 target pesticides and suspect screening of emerging organic contaminants in agricultural soils - Yu-Hui Chang; Chi-Chieh Hu; Chinn-Yuan Fu; Sichao Wang; Yu-Min Tzou; Shiou-Ruei Lin; Hsiao-Ying Yang; Jerry J. Wu; Cheng-Hua Liu; Ya-Hui Chuang (Journal of Hazardous Materials, 2026)

Metal sulfide-based electrocatalysts for water splitting: From rational design to advanced applications - Yi Liu; Yijun Wu; Xiantuo Chen; Yongmin Ying; Jili Wen; Huanan Wang; Le Chen; Yingsu Qu; Min Li; Jiang Wu; Zaiguo Fu (Fuel, 2026)

Sunlight-driven evolution of the aroma profile in fish sauce fermentation - Jin-Xiu Xu; Xin Zhang; Bai-Feng Fu; Zhao-Rui Li; Min-Bo Li; Zhen-Yu Wang; Xian-Bing Xu; Shu-Zhen Cheng; Ming Du (Food Bioscience, 2026)

Collapse mechanism of stratum induced by subsurface excavation for a shallow buried tunnel in water-rich region - Fu Huang; Yongtao Wang; Min Zhang; Lu Chen (Computers and Geotechnics, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Confinement-desolvation-interfacial matching trilogy boost wide-temperature-range zinc‑iodine batteries - Shang Sun; Hao Luo; Wenjing Zhang; Yu Fu; Fan Li; Min Zhou; Shunyao Li; Chi Chen; Hanna He; Lina Ma (Chemical Engineering Journal, 2026)

Anammox community characteristics and stable relationships centered on anammox bacteria - Yi-Cheng Wang; Hui-Min Fu; Hong-Yuan Liu; Han Wu; Zi-Han Zeng; Jian-Hong He; Meng-Jiao Gao; Peng Yan; Liang Zhang; You-Peng Chen (Chemical Engineering Journal, 2026)

Proteins Associated with Cognition in Amyloid-beta Positive Elders Based on Cerebrospinal Fluid Proteomics - Min Liu; He-Ying Hu; Yan Fu; Hao-Chen Chi; Liang-Yu Huang; Lan Tan; Hao Hu (Molecular Neurobiology, 2026)

Modulating NLRP3 Inflammasome Activity and Enhancing Cortical Synaptic Plasticity: Nanoparticulate Hydrogen’s Role in Relief of Post-traumatic Anxiety-like Behaviors in Rats - Lanxia Wu; Congwen Yang; Yiqin Ding; Xinru Liu; Hao Sun; Xue Li; Yining Lu; Lifen Liu; Qingyang Fu; Min Li; Yingshuai Wang; Yuehan Zhao; et al. (Molecular Neurobiology, 2026)

Species diversity of Amanita in Shanxi Province with five new species revealed by morphological and molecular evidence - Hui-Min Ji; Hao-Yu Fu; Li Fan (Mycological Progress, 2025)

Towards human-centered urbanization: interaction effects of multidimensional environmental factors on walk score in mountain cities’ urban trails - Zhonglin Tang; Yihui Zhao; Min Fu (Environment, Development and Sustainability, 2025)

In-situ recycling of waste ozonation catalysts into N-doped graphitic carbon-alumina structures induces a non-radical pathway towards water purification - Min Li; Xiaoguang Jin; Zhouyang Li; Yu Fan; Yutang Zeng; Liya Fu; Changyong Wu (Water Research, 2025)

Exploring potential mechanisms of artificial sweeteners in polycystic ovary syndrome through network toxicology and molecular docking - Huan He; Yinjuan Lyu; Manquan Fu; Xiaocui Jiang; Jianmin Liu; Min Xiao (Reproductive Toxicology, 2025)

The long transition from deltaic tidal flats to flood plains in the Pearl River delta - Haixian Xiong; Yongqiang Zong; Shuqing Fu; Lu Min; Guangqing Huang (Geomorphology, 2025)

Functional differentiation of Sojae semen Praeparatum: A multi-omics analysis of the effects of Artemisia annua and Mori folium on composition, microorganisms, and functional characteristics - Yingying Cheng; Bing Wang; Qiaoling Ma; Min Sun; Xintong Wang; Ruolan Wang; Hongping Chen; Lin Chen; Youping Liu; Fu Wang; Chuan Zheng; Yuan Hu (Food Research International, 2025)

Light-activated dialdehyde cellulose nanocrystals (DACNC)-erythrosine generates ROS for Vibrio inactivation in whiteleg shrimp - Dewi Nur’aeni Setyowati; Shao-Chen Lu; Yong-Ching Heng; Jia-Wei Zhou; Yi-Min Chen; Shih-Chen Shi; Fu-I Lu (Fish & Shellfish Immunology, 2025)

Machine learning-enhanced meta-analysis unravels the global patterns of microplastic-heavy metal co-toxicity in terrestrial ecosystems - Hai-han Jiang; Tian-Hao Che; Qing Su; Bin Jin; Yan Lu; Han-Xi Zhou; Min-Jie Fu; Jing-Ya Zhou (Environmental Pollution, 2025)

AI-assisted SERS fingerprint of serum omics analysis for precision breast cancer screening - Lingna Wang; Weihua Hong; Jinyong Lin; Chengbin Fu; Yuanmei Chen; Zeyang Liu; Min Fan; Luyun Xu; Jianqing Ye; Chengtao Ruan; Chaobin Huang; Xueliang Lin; et al. (Chemical Engineering Journal, 2025)

An interface-engineered three-channel synapse using staggered transition metal dichalcogenides/ferroelectric heterojunctions - Yuqing Zhou; Qibin Zeng; Xingke Fu; Chao Yang; Feiyan Hou; Chen Ge; Kaiyang Zeng; Huajun Liu; Zheng Chai; Tai Min; Tao Li (Chemical Engineering Journal, 2025)

Impaired endothelial cell-derived CX3CL1-mediated macrophage efferocytosis in hypertrophic cardiomyopathy based on multi-omics analysis - Yan Zhang; Xin Yan; Xiao-lei Fu; Hai-bing Yang; Yi-min Yan; He-fan He; Li Yang (Inflammation Research, 2025)

Pivotal epitopes for islet antigen-specific CD8+ T cell detection improve classification of suspected type 1 diabetes with the HLA-A*0201 allele - Yang Chen; Min Shen; Yong Gu; Xinyu Xu; Lingling Bian; Fan Yang; Shuang Chen; Li Ji; Jin Liu; Jing Zhu; Zheng Zhang; Qi Fu; et al. (Immunologic Research, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Evaluation of EUCAST rapid antimicrobial susceptibility testing (RAST) for carbapenemase-producing Klebsiella pneumoniae with focus on KPC variants - Min Xu; Yuchao Zhang; Yajie Fu; Qiaoling Sun; Haishen Kong; Yiqi Fu (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Dietary factors and colorectal cancer risk in Asian populations: a systematic review and meta-analysis of cohort studies - Hyobin Lee; Linda Ngoun; Sukhong Min; Jialei Fu; Woo-Kyoung Shin; Daehee Kang; Sangah Shin (Cancer Causes & Control, 2025)
Purpose Colorectal cancer (CRC) is the third most common cancer worldwide and a leading cause of cancer-related mortality. Few studies have examined the preventive effects of dietary factors against CRC in Asian populations. Thus, this systematic review and meta-analysis aimed to synthesize and analyze current evidence on the relationships between various dietary components and the risk of CRC, colon cancer, and rectal cancer in Asian populations. Methods We included cohort studies from PubMed, Web of Science, Embase, and Scopus reporting an association between dietary factors and CRC risk in Asian populations. Relative risks (RRs) with 95% confidence intervals (CIs) were used to calculate the pooled risk estimates. Cochran’s Q and I 2 statistics were employed to assess heterogeneity. Funnel plots and Egger’s tests were used to evaluate publication bias. Results Eighty-two publications met the inclusion criteria. The findings indicated that healthy dietary patterns were associated with a reduced risk of colon cancer (RR = 0.85, 95% CI, 0.74–0.97), and calcium intake was linked to a slight reduction in CRC risk (RR = 0.93, 95% CI, 0.86–1.00). Conversely, high total meat consumption was associated with increased risks of CRC (RR = 1.18, 95% CI, 1.03–1.34), and white meat intake was associated with a potential 40% increased risk of rectal cancer (RR = 1.40, 95% CI, 1.00–1.96). Conclusions This review suggested that healthy dietary patterns and calcium intake are associated with a lower risk of CRC in Asian populations. Nonetheless, additional studies are warranted to clarify the associations between dietary patterns and CRC risk.

Spatial-temporal evolution of ecological-economic-disaster synergies and their dynamic response to land use efficiency: evidence from China - Boyi Li; Xing Zhu; Hao Zhu; Ruotong Yuan; Xiaodi Fu; Dongmei Liu; Xugong Jia; Min Tang (Environment, Development and Sustainability, 2025)

Full waveform inversion of cross-hole GPR data using Markov Chain Monte Carlo method based on SE-Resnet - Sheng-chao Wang; Yu-fei Wang; Yi-fei Liu; De-fu Zhang; Hui Sun; Gong-min Chen; Xiang-yu Tan (Applied Geophysics, 2025)

Sample Size and Optimal Timing for Urine Collection Based on Diurnal Variability of Urinary Iodine/Creatinine Ratio in Pregnant Women - Qi Meng; Min Fu; Rui Yang; Fei Li; Junjing Li; Meina Ji; Qi Jin; Mengxin Liu; Hexi Zhang; Wenxing Guo; Wanqi Zhang (Biological Trace Element Research, 2025)

Sulfurized nano zero-valent iron loaded graphene oxide enhances the anaerobic fermentation treatment of swine manure: Insights from microbial community analysis and DFT calculations - Min Zhang; Qilan Huang; Haiyun Liu; Haibin Fu; Liu Cao; Huanhuan Wei; Renjiao Yan; Wenqi Wang; Kunjian Zhang; Qianru Zhang (Journal of Environmental Management, 2025)

Insights into the multi-media spatiotemporal distribution, partitioning, and risks of pharmaceuticals and personal care products in the southern Bohai Sea - Shuang Lu; Han Chen; Min Lv; Peng Zhang; Longwen Fu; Mingsan Man; Wei Zhang; Dongliang Wang; Jing Ding; Wei Liu; Lingxin Chen (Journal of Environmental Management, 2025)

Umami-Transformer: A deep learning framework for high-precision prediction and experimental validation of umami peptides - Baifeng Fu; Min Fan; Junjie Yi; Yingxue Du; Hong Tian; Tao Yang; Shuzhen Cheng; Ming Du (Food Chemistry, 2025)

A novel strategy based on mouse organoid biosensor for detecting umami substances and their synergistic effect - Minbo Li; Min Fan; Baifeng Fu; Zhihui Chang; Junjie Yi; Yingqi Xie; Wenwen Ren; Yu Tian; Qiyue Zhao; Shuzhen Cheng; Xianbing Xu; Ming Du (Food Chemistry, 2025)

Heat-sealable chitosan- DES composite film: performance optimization, multi-mechanism synergistic effect, and extension of bread shelf life - Min Fan; Xiaoxiao Cheng; Yuying Gao; Xiaofang Liu; Yabo Fu; Zhiguo Xiong; Li Li (Chemical Engineering Journal, 2025)

The multimodal anti-tumor effect of cisplatin nanoparticles loaded with bacterial antibodies in combination with radiotherapy: targeting hypoxic tumor and reshaping of the immune microenvironment - Min Wu; Zhouxue Wu; Weizhou Wang; Yunxue Zheng; Hongxia Li; Yuan Huang; Liping Deng; Yingqi Gu; Jinfeng Rong; Xiaoyin Zhang; Wen Yang; Yue Chen; et al. (Chemical Engineering Journal, 2025)

In-situ electropolymerization constructed super durable and highly adaptable pyrene - 4, 5, 9, 10 - tetraone-based organic cathode for aqueous zinc-ion batteries - Fu Li; Zhengtai Zha; Weijia Zhang; Tianjiang Sun; Qiong Sun; Min Cheng; Diantao Li; Haixia Li; Zhanliang Tao (Chemical Engineering Journal, 2025)

Calcium-doped barium titanate (Ba0.8Ca0.2TiO3)-modified piezo-photocatalytic self-cleaning ceramic composite membrane for oily wastewater remediation - Lei Zhang; Weigui Fu; Qianqian Mo; Min Feng; Meixiu Sun; Yiping Zhao; Li Chen (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Injectable GelMA–PEDOT:PSS conductive hydrogel for cardiac-tissue engineering and integrated organic electrochemical transistor–based bioelectronic patch for biosensing and controlled extracellular vesicle release - Chung-Chuan Chou; Yu-Sheng Hsiao; Ming-Fu Hou; Pin-Yu Zhang; Min-Yu Hsieh; Lin-Yang Weng (Chemical Engineering Journal, 2025)

Single nucleotide polymorphisms of the Waxy gene and their relationship with the physicochemical properties of Pueraria lobata (kudzu) starch - Ruiqi Zha; Ying Fan; Yuhao Fu; Chunyan Liu; Haoliang Sun; Jiaxin Wan; Min Wei; Zhixing Jin; Peng Li; Zhongyan Zhu; Jing Wei; Jun Yin; et al. (Carbohydrate Polymers, 2025)

The response of plant-derived lignin phenols accumulation to nutrient addition depends on soil depth in a subtropical plantation - Jin He; Dong Bu; Yuan-Huang Zeng; Shui-Bo Han; Wen-Qing Li; Fu-Sheng Chen; Ying-Ying Zong; Yu-Xin Huang; Yang Zhang; Xiang-Min Fang (Plant and Soil, 2025)

Path analysis and curve fitting of morphometric traits and body weight of juvenile Aspiorhynchus laticeps - Huale Lu; Huimin Hao; Zhulan Nie; Jie Wei; Qing Xiao; Hongmei Fu; Yuren Gong; Min Wang (Journal of Fish Biology, 2025)
In this experiment, correlation analysis, path analysis, regression analysis and curve‐fitting methods were employed to investigate the relationships between the body weight (Y) and morphological variables (X1–X36) of juvenile Aspiorhynchus laticeps (common name: big‐head schizothoracin). These methods were used to identify the main morphological trait indices affecting body weight and further determine the optimal fitting models between four main morphological traits and body weight. The study found that 94% of the morphological traits of juvenile A. laticeps had a highly significant positive correlation with body weight ( p p > 0.05), while other morphological traits had a significant positive correlation ( p R 2 = 0.718), the optimal fitting model of mouth cleft height (X11) and body weight was a power function equation ln(Y) = −9.847 × (1/X11) + 3.065 ( R 2 = 0.560), the optimal fitting model of CI (X30) and body weight was a logarithmic function equation ln(Y) = −36.207 × (1/X30) + 4.308 ( R 2 = 0.881), and the optimal fitting model of the distance from the end of the dorsal fin base to the starting point of the ventral caudal fin (DF, X35) and body weight was a logarithmic function equation ln(Y) = −61.089 × (1/X35) + 3.811 ( R 2 = 0.728). The research results indicate that in the breeding selection of juvenile A. laticeps , CI (X30) should be taken as the main selective trait, supplemented by body width (X3), mouth cleft height (X11) and DF (X35) as references.

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Miconazole alleviates colitis by suppressing colonic senescence, NF-κB Signaling and gut microbiota modulation - Fuxing Li; Shujia Song; Mingming Huang; Yaxing Xu; Bingxiang Zhao; Zhenlin Liu; Bin Fu; Huilai Zhang; Hanying Zou; Min Zhou; Lihua Li; Xiaobo Wang (Toxicology and Applied Pharmacology, 2025)

HySwinFormer: A hybrid deep learning architecture for fine-grained classification of marine microalgae - Jiaxuan Li; Min Fu; Lichi Ding; Jian Qi; Jingqiang Yang; Shimin Yang (Science of The Total Environment, 2025)

Vanadium-driven surface engineering to suppress Sr segregation in perovskite ceramics for nuclear waste immobilization - Yinlin Chang; Tao Liu; Jingyuan Rao; Min Fu; Yijun Guo; Shuliang Zou; Dewen Tang; Zetian Tao (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Dynamic changes in microbiota and metabolome of Kazakh cheese under traditional handicraft” [Food Chem. 483 (2025) 144251] - Fangfang Wang; Qingquan Fu; Tiantian Tang; Zimeng Liu; Xinyi Ma; Yinqi Liu; Min Zhao; Chenqiang Wang; Juan Du; Bin Wang; Xuewei Shi (Food Chemistry, 2025)

Oxalic acid induced synthesis of renewable Ce-MnFe2O4 nanocatalysts with hybrid crystallinity for enhanced ozone decomposition - Xiaotong Li; Lei Zhong; Zhuxu Li; Yitong Fu; Mingzhe Dong; Xin Min; Songjian Zhao (Environmental Research, 2025)

Antinode-centre near-infrared tandem OLEDs enabled by ultrathin emissive layers - Min Song; Zheng Ren; Sheng-Fu Wang; Xiao-Bo Shi; Wei-Zhi Liu; Zi-Qi Feng; Dong-Ying Zhou; Pi-Tai Chou; Liang-Sheng Liao (Chemical Engineering Journal, 2025)

Linking two types of breccias to sediment-hosted stratiform copper (SSC) and iron oxide-copper-gold (IOCG) deposits in the Kangdian metallogenic belt, SW China - Xue-Qing Yin; Xin-Fu Zhao; Zhi-Kun Su; Hai-Tao Lin; Zhi-Min Zhu; Wen-Lei Song; Martin Yan Hei Li; Kui-Dong Zhao (Mineralium Deposita, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

Synthesis of zeolite 4A from low-grade kaolin containing muscovite and quartz via ultrafast Joule heating route: A comparison with conventional calcination - Jiahang Fan; Xianjie Liu; Mengyao Yang; Mingyong Liu; Qianchao Ma; Liangjie Fu; Xin Min; Zhaohui Huang (Applied Clay Science, 2025)

Unveiling city-scale urban roadside charging piles capacity: Geospatial knowledge-assisted small object detection and SDG 7-driven planning - Qin Huang; Teng Zhong; Liangchen Zhou; Rui Zhu; Xiao Fu; Changchang Zhou; Min Chen; Guonian Lü (Sustainable Cities and Society, 2025)

Decoding taste & odor - producing actinobacteria in drinking water reservoir sediments: Community distribution and carbon metabolic preferences - Xiang Liu; Tingting Pei; Tinglin Huang; Danhong Yang; Min Fu; Shengzhao Jing; Ben Ma; Xiaoyan Liu; Jianchao Shi; XinJian Niu; Hongbin Sang; Haihan Zhang (Journal of Water Process Engineering, 2025)

Pressure makes diamonds: Enhanced permeation resistance to petroleum hydrocarbons of a novel in-situ mixed wall material - Zhe-Yuan Jiang; Xian-Lei Fu; Yu-Ling Yang; Wei-Yi Xia; Min Wang; Heng Zhuang; Zi-Han Lu; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Bisphenol A caused abnormal spermatogenesis of Eriocheir sinensis through es-ERR/es-KIF4A pathway with discussion of BPA substitutes - Yu Yang; Di Wu; Tian Lei; Hang-Yuan Zhao; Jun-Jie Yu; Lan-Min Wang; Ding-Xi Liu; Yan-Shuang Zhao; Jia-Hao Ni; Fu-Qing Tan; Wan-Xi Yang (Journal of Hazardous Materials, 2025)

DCNet: Full waveform inversion with difference convolution - Li-Sha Fu; Chang-Yang Hu; Leting Tan; Huawei Liao; Qiang Zhang; Fan Min (Journal of Applied Geophysics, 2025)

Storage evolution in non-volatile and volatile lipid oxidation products of salted large yellow croaker based on targeted lipidomics and GC–MS analysis - Min Zhang; Jing-jing Fu; Jun-long Mao; Xiu-ping Dong; Yue-wen Chen (Food Chemistry, 2025)

Enzymatic preparation of walnut-derived peptides and their neuroprotective effects in a mouse model of early Alzheimer's disease - Zehui Li; Pengju Zhao; Junxi Fu; Yashu Qiao; Weiyu Hou; Chunlei Liu; Weihong Min (Food Bioscience, 2025)

Bio-based ion-conducting hydrogels with tunable mechanical and electralchemical properties via metal ion-regulated cellulose chain assembly for flexible electronics - Haiyue Miao; Gang Huang; Yiyang Liu; Xiaojuan Huang; Chongyang Zheng; Xi Zhang; Changwu Dong; Xiaobin Fu; Hailong Huang; Min Ge; Hongtao Liu; Yuan Qian (Chemical Engineering Journal, 2025)

Interfacial water masking agent: Dynamic synergistic regulation of anode and cathode for ultra-long-life aqueous zinc metal batteries - Bin Xie; Chao Li; Min Li; Lieyuan Zhang; Zhaodan Fu; Yijia Luo; Gehong Su; Xin Tan; Heng Zhang; Qiaoji Zheng; Yu Huo; Jingxin Zhao; et al. (Chemical Engineering Journal, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

Distributed fixed-time cooperative tracking control of networked uncertain underactuated surface vessels with unmeasured velocity and input saturation - Hailun Chen; Yujie Xu; Mingyu Fu; Lijing Dong; Xuyu Min (Ocean Engineering, 2025)

Fate, transport, and plant uptake of ricinine in soils amended with castor cake organic fertilizer - Ya-Hui Chuang; Kai-Xuan Zheng; Siu Chun Wong; Yu-Min Tzou; Sichao Wang; Shiou-Ruei Lin; Hsiao-Ying Yang; Chinn-Yuan Fu; Jerry J. Wu; Cheng-Hua Liu (Journal of Hazardous Materials, 2025)

Scandium and gallium in weathered basalts as unconventional resources - Mei-Fu Zhou; Wen Winston Zhao; Zhenchao Wang; Min Wang; Shengbiao Yang; Lei Meng; Liang Qi; Guangfu Xing; Xiang Li; Dai Zhou (Journal of Asian Earth Sciences, 2025)

The spoilage characteristics and key metabolites of Lactobacillus brevis and Lactobacillus plantarum in ready-to-eat chicken feet - Xin Jia; Peng Gao; Ailian Meng; Yi Fu; Hao Chen; Min Huang (Food Research International, 2025)

Dynamic changes in microbiota and metabolome of Kazakh cheese under traditional handicraft - Fangfang Wang; Qingquan Fu; Tiantian Tang; Zimeng Liu; Xinyi Ma; Yinqi Liu; Min Zhao; Chenqiang Wang; Juan Du; Bin Wang; Xuewei Shi (Food Chemistry, 2025)

Nutrient enrichment weakens the positive feedback of soil organic carbon decomposition to short-term warming in subtropical forests - Ming-Hui Meng; Chao Liang; Jin He; Zi-Yi Shi; Fu-Sheng Chen; Fang-Chao Wang; Xue-Li Jiang; Xiang-Min Fang (Plant and Soil, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Neurotensin receptor1 signaling promotes progression of epithelial–mesenchymal transition in mice with chronic rhinosinusitis through Wnt3a/β-catenin pathway - Yujie Wu; Xiaoyan Zhu; Hongwei Gu; Feida Fu; Qinghua Guo; Ke Liu; Min Yang; Tian Zhang; Xu Wang (Journal of Molecular Histology, 2025)

Sparse spike inversion with parity decomposition and stratal dip constraints - Jian-lei Zhang; Zhi-fang Ran; Fu-min Li; Guo-fa Li (Applied Geophysics, 2025)

Ore-forming fluid for the formation of banded iron formation-hosted high-grade magnetite ores of the North China Craton: Constraints from pyrite trace elements and sulfur isotopes - Yi Wang; Li-Xing Li; Hou-Min Li; Jian-Fei Fu; Yang Dai; Xiao-Hui Wang; Xuan Wu (Journal of Asian Earth Sciences, 2025)

Enhancing containment performance of geosynthetic clay liner to bauxite liquor via composite polymer amendment - Xian-Lei Fu; Zhe-Yuan Jiang; Min Wang; Hao Ni; Yan-Jun Du (Engineering Geology, 2025)

Autofluorescence cascade nanozyme catalyzes in vivo ROS scavenging for precisive anti-neuroinflammation therapy - Xiyu Du; Gang Zhao; Yifei Fu; Yushan Zhou; Li Yang; Zhaoshun Jiang; Songbin Liu; Xixue Zhang; Kaiqi Zhu; Li Wei; Weidong Gu; Han Lu; et al. (Chemical Engineering Journal, 2025)

Two nuclear loci Rf-m1 and Rf-m2 interplay to determine the fertility restoring efficacy of ZD-type CMS soybean - Xiaoxia Yu; Yupeng Feng; Lulu Zhou; Hongye Gao; Hongbin Wang; Yaru Chen; Jiamai Liang; Tianyu Meng; Meng Li; Yihan Yuan; Junping Yu; Hao Liu; et al. (Theoretical and Applied Genetics, 2025)

Assessing and predicting surrounding rock settlement troughs in the subsea tunnel: A case study of Haicang Tunnel - Huimin Gong; Yiguo Xue; Kang Fu; Fanmeng Kong; Min Han; Binghua Zhou; Yanbing Guo (Marine Georesources & Geotechnology, 2025)

Microbial volatile organic compounds produced during the anaerobic digestion process can serve as potential indicators of microbial community stability - Dongxue Lu; Min Li; Erqi Nie; Rongbo Guo; Shanfei Fu (Water Research, 2025)

Pichia kudriavzevii inhibits the growth of Colletotrichum gloeosporioides through 2-PE targeting cell membrane - Min Zhang; Ying Yang; Xingrong Zhang; Maorun Fu; Hui Xu; Cuihong Zhang; Yanhong Huang (Postharvest Biology and Technology, 2025)

Macoligophones A–I, prenylated acetophenone dimers and monomers from Maclurodendron oligophlebium - Jing-Jing Qi; Yu-Nan Qian; Ying Li; Xiang-Yu Liu; Rui-Yao Fu; Zheng-Hui Huang; Jian-Min Yue; Jin-Xin Zhao (Phytochemistry, 2025)

New thiohydantoin derivatives from the roots of Lepidium meyenii - Wen-Xin Liu; Jun Li; Cheng-Juan Liao; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2025)

A systematic review on mechanism and regulation strategy of marine hydrodynamic noise: Advances, challenges, and perspectives - Xin Jin; Hua-long Huang; Yuan Tao; Fu-gui Zhang; Min Luo; Chang-yuan Fan; Tao Tang (Ocean Engineering, 2025)

A global perspective on the development and application of glacio-hydrological model - Chengde Yang; Xin Wang; Shichang Kang; Min Xu; Yong Zhang; Junfeng Wei; Congsheng Fu (Journal of Hydrology, 2025)

Highly efficient photocatalytic removal of NO and synchronous inhibition of NO2 via heterojunction formed by ZnAl-LDH and MXene-Ti3C2-derived TiO2@C - Kaili Wu; Yacen Tang; Yirui Qiu; Haibo Zhou; Xingyan Liu; Panyin Wang; Youzhou He; Shimeng Pan; Yuyu Fang; Min Fu; Siping Wei; Fan Dong (Journal of Hazardous Materials, 2025)

How to balance cadmium immobilization and greenhouse gas emissions when using microbial induced-calcite precipitation (MICP): Regulate the N/Ca molar ratio and dosage - Min Liu; Hongqing Hu; Md. Shoffikul Islam; Xiongfei Rao; Jun Zhu; Linchuan Fang; Qingling Fu (Journal of Environmental Chemical Engineering, 2025)

Field and numerical investigations on linkage failure of the main roof and pumpable supports in the pre-excavation recovery room - Dong Zhang; Jianbiao Bai; Yonghong Guo; Zizheng Zhang; Rui Wang; Zhijun Tian; Shuai Yan; Qiancheng Zhu; Min Deng; Hao Fu; Shuaigang Liu (Engineering Geology, 2025)

Cobalt phthalocyanine modified holey Graphene/Cobalt phosphide for supercapacitor electrodes - Wei Chen; Min Fu; Siyuan Yang; Liangmin Ning; Hao Yu; Meng Gao; Kunhua Wang; Meili Guan; Ruitao Lv; Nan Li; Jianming Pan (Chemical Engineering Journal, 2025)

Vertical distribution and seasonal variations of dicarboxylic acids in urban PM2.5: Insights from multi-level observations on 600 m Canton tower in Guangzhou - Dian Ye; Shengzhen Zhou; Yuxuan Liang; Chunlei Cheng; Chenglei Pei; Yao Li; Min Gao; Xijing Sun; Siqi Chen; Jian Hang; Pingqing Fu; Shaojia Fan (Atmospheric Environment, 2025)

Reversing anther thermotolerance by manipulating the cis-elements in the promoter of a high-temperature upregulated gene Casein Kinase I in upland cotton - Yanlong Li; Yinuo Fu; Yaoyao Li; Rui Zhang; Jing Yang; Huanhuan Ma; Ling Min; Xianlong Zhang (Science China Life Sciences, 2025)

A Year Marked by Extreme Precipitation and Floods: Weather and Climate Extremes in 2024 - Wenxia Zhang; Tianjun Zhou; Wanheng Ye; Tingyu Zhang; Lixia Zhang; Piotr Wolski; James Risbey; Zhuo Wang; Seung-Ki Min; Hamish Ramsay; Michael Brody; Alice Grimm; et al. (Advances in Atmospheric Sciences, 2025)

Impacts of river inputs and aquaculture on nutrient dynamics in Qinglan Bay and adjacent coastal waters in East Hainan, China - Sang Wu; Zuoli Tan; Youfei Fu; Nannan Gao; Silin Ni; Rong Zhao; Penglan Shi; Lili Han; Jianzhong Su; Zhenzhen Zheng; Ehui Tan; Shuh-ji Kao; et al. (Marine Pollution Bulletin, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

The dual-targeted transcription factor BAI1 orchestrates nuclear and plastid gene transcription in land plants - Jing Qin; Yelin Shan; Hao Liu; Zhangzhi Xue; Yike Xie; Guoxin Yuan; Yiming Zou; Xiaonuan Hao; Yunpeng Zhu; Xuan Shen; Meng Li; Xu Wang; et al. (Molecular Plant, 2025)

Environmental factors impacting phytoplankton response to the cold water mass in the Yellow Sea - Lichi Ding; Jiaxuan Li; Qian Zhang; Min Fu; Shimin Yang (Journal of Cleaner Production, 2025)

A critical review of human internal exposure to short-chain chlorinated paraffins and its concerning health risks - Ke Fang; Yi-bin Sun; Run-ming He; Jian-kun Qian; Wen Gu; Yi-fu Lu; Zhao-min Dong; Yi Wan; Chao Wang; Song Tang (Environmental Research, 2025)

Manganese vacancy and shell protection as two-pronged strategies for boosting capacitive deionization of manganese-based prussian blue analog electrodes - Guoxiang Liu; Wei Chen; Liangmin Ning; Hao Yu; Meng Gao; Linzheng Ma; Ruitao Lv; Jianming Pan; Min Fu (Desalination, 2025)

Chlorpyrifos-oxon results in autophagic flux dysfunction contributing to neuronal apoptosis via a ROS/AMPK/CHOP activation pathway - Jui-Ming Liu; Kuan-I Lee; Chin-Chuan Su; Kai-Min Fang; Shing-Hwa Liu; Shih-Chang Fu; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Ya-Wen Chen; Ching-Yao Yang; Chun-Fa Huang (Chemico-Biological Interactions, 2025)

Slowing wind increases soil carbon emissions in a fragmented subtropical forest: a study combining field and model experiments - Hao-Hao Wu; Ling-Ling Zhang; Ai-Min Liao; Hua-Wu Wu; Xiao-Ming Lai; Hai-Xia Zhang; Ye Xia; Yang Cao; Zi-Chun Zhu; Zhen-Ming Ji; Cong-Sheng Fu (Plant and Soil, 2025)

Two new seco-abietane type diterpenoids from the leaves of Isodon serra - Min Wang; Li-Li Zhong; Xiang-Xiang Fu; Jun Chen (Natural Product Research, 2025)

Model test study of punching shear failure mode of the bearing stratum induced by tunneling beneath an existing pile - Fu Huang; Yongtao Wang; Min Zhang; Wangtao Jiang; Hengbo Ji; Qiujing Pan (Tunnelling and Underground Space Technology, 2025)

Two new phenolic glycosides from Cyathula officinalis and their relaxant effects on uterine smooth muscle - Mei-Ji Sun; Rui Zhao; Min Wen; Chun-Wang Meng; Hai-Guo Su; Fu-Xin Mi; Cheng Peng; Juan Liu; Liang Xiong (Phytochemistry Letters, 2025)

Impacts of sulfamethoxazole on heterotrophic nitrification-aerobic denitrification bacteria and its response strategies: Insights from physiology to proteomics - Teng-Fei Ma; Xiao-Yao Yu; Chong-Yang Xing; Hui-Min Fu; Hao-Yang Duan; You-Peng Chen (Journal of Environmental Management, 2025)

Physiological and proteomic insights into silver nanoparticle-induced stress responses and resistance mechanisms in aerobic denitrifying Enterobacter cloacae HNR - Teng-Fei Ma; Hong-Xi Ma; Chong-Yang Xing; Hui-Min Fu; Yu Shen; You-Peng Chen; Xiang-Yang Wei (Journal of Environmental Chemical Engineering, 2025)

Structural characterization of bacterial fucose-containing tetrasaccharide and its potential enhancement on intestinal barrier function - Mengshi Xiao; Luying Tang; Xiaodan Fu; Qingping Liang; Jian Ma; Min Yang; Changliang Zhu; Haijin Mou (Food Bioscience, 2025)

Estimating wastewater emissions and environmental levels of typical organic contaminants based on regionalized modelling - Rui-Xin Qin; Cheng-Zhong Fu; Li Zhuo; Shi-Yi Zhang; Feng-Shan Cai; Kai-Yi Wu; Xiao Yan; Wei-Keng Luo; Min Li; Yun-Gang Shi; Bin Tang (Environmental Research, 2025)

Simultaneous achievement of giant piezoelectric charge and voltage coefficients in holmium-doped Pb(Mg1/3Nb2/3)O3-PbTiO3 single crystals - Min Liang; Kun Zeng; Ruibin Xiong; Bin Su; Jianqun Liu; Shuli Chen; Zujian Wang; Rongbing Su; Ying Liu; Zhengqian Fu; Chao He (Chemical Engineering Journal, 2025)

A novel injectable sodium alginate/chitosan/sulfated bacterial cellulose hydrogel as biohybrid artificial pancreas for real-time glycaemic regulation - Xiang Zhao; Wei Xue; Weixiao Ding; Yalei Qiao; Xuehui Chu; Yudong Qiu; Min Tang; Dongping Sun; Xiao Fu (Carbohydrate Polymers, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

U(VI) removal by zerovalent manganese modified corn straw biochar in acidic wastewater: Efficiency, characteristics and mechanism - Taotao Zeng; Yusong Fu; Min Yang; Qiqi Deng; Shengbin Chen; Yingjiu Liu; Jun Li (Chemosphere, 2025)

Nitrogen utilization dynamics in a tropical estuary: Interplay of temperature and phytoplankton communities - Penglan Shi; Zuoli Tan; Youfei Fu; Min Nina Xu; Rong Zhao; Lihua Shang; Jin-Ming Tang; Lili Han; Shan Sun; Ehui Tan; Zhenzhen Zheng; Shuh-Ji Kao (Marine Environmental Research, 2025)

Exploring the physical disruptions of anammox granular sludge under propylene glycol stress: Implications for nitrogen removal and long-term stability - Hui-Min Fu; Xiao-Wen Jiang; Cai-Ping Sun; Shi-Jun Li; Xun Weng; Meng-Wen Peng; Peng Yan; Xiao-Wei Xu; You-Peng Chen; Yu Shen (Journal of Water Process Engineering, 2025)

Transcriptional and molecular simulation analysis of the response mechanism of anammox bacteria to 3,4-dimethylpyrazole phosphate stress - Cui-Zhong Chen; Jin Wang; Yi-Cheng Wang; Hui-Min Fu; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Hazardous Materials, 2025)

Enhancing NH3-SCR denitrification performance through synergistic A- and B-site effects via CeFe modification of LaMnO3 - Wei Zhang; Qiao Wu; Mengyao Dong; Kang Xie; Yanshan Yin; Yunhe Zhou; Jie Li; Yehao Fu; Yaocheng Liang; Quanbin Song; Min Ruan; Shan Cheng; et al. (Fuel, 2025)

Study on the role of mitophagy and pyroptosis induced by nano-silver in testicular injury - Deyu Zhu; Yingyi Li; Min Liu; Yufen Yang; Jiayu Fu; Liyu Su; Feng Wang; Yuyan Cen; Yanna Zhou; Yan Li (Food and Chemical Toxicology, 2025)

Pull-out capacity and failure mechanism of suction anchors in clay considering trench configuration and local scour effects - Min-Hao Zhang; Zhen-Yu Yin; Yong Fu (Engineering Geology, 2025)

A flexible, antifreezing, and long-term stable cellulose ionic conductive hydrogel via one-step preparation for flexible electronic sensors - Haiyue Miao; Yiyang Liu; Chongyang Zheng; Xiaojuan Huang; Yidan Song; Lulu Tong; Changwu Dong; Xiaobin Fu; Hailong Huang; Min Ge; Hongtao Liu; Yuan Qian (Carbohydrate Polymers, 2025)

Diurnal and seasonal variation of surface heat island of local climate zones using FengYun-4A land surface temperature data - Longteng Fu; Xian-Xiang Li; Rui Xin; Min Min; Lixin Dong (Urban Climate, 2025)

Tidal-driven N2O emission is a stronger resister than CH4 to offset annual carbon sequestration in mangrove ecosystems - Chunwei Fu; Zhibo Shen; Shiheng Tang; Fengying Li; Xin Quan; Yang Wang; Ya Zhuang; Jiasen Zhong; Jianan Liu; Jianzhong Su; Min Xu; Yu Han; et al. (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Gentidelasides A−G: Loganin derivatives from Gentiana delavayi with reducing Aβ secretion via suppressing BACE1 expression - Hai-Hui Guo; Chun-Xu Li; Min Yang; Feng-Feng Li; Hui-Yun Yang; Ming Yin; Jia-Peng Wang; Fu-Sheng Wang (Phytochemistry, 2025)

Nondestructive three-dimensional structure and growth characteristics of anammox granular sludge - Meng-Wen Peng; Ya-Song Chen; You-Peng Chen; Wan Sun; Meng-Meng Liu; Xun Weng; Shuai Wang; Yu Shen; Hui-Min Fu (International Biodeterioration & Biodegradation, 2025)

Coal dust combustion suppression via melamine polyphosphate and silica: Experiment and simulation - Shuang Geng; Ting Zhang; Xin Zhang; Shaoqian Cheng; Guoen Fu; Jianfu Xu; Wen Zhou; Yanhua Lan; Xueqiang Shi; Chi-Min Shu; Weiguo Cao (Fuel, 2025)

High-entropy design of Ruddlesden-Popper structured LNO for enhanced performance in proton solid oxide fuel cells - Mingming Zhang; Yinlin Chang; Weiyuan Xiang; Jiani Liu; Xiangbo Deng; Jing Zhou; Min Fu; Zetian Tao (Fuel, 2025)

Characterization of pea protein-different types of glycoside flavonoid complex interactions and functional properties - Zihao Chen; Min Fu; Jun Chen; Guowen Zhang; Qin Geng; Xing Hu; Yihui Wang; Ti Li; Ruihong Liang; Taotao Dai (Food Research International, 2025)

Highly efficient Z-scheme CeO2/Bi2MoO6 heterojunction strengthened by redox mediator for photoelectrochemical detection of tetracycline with enhanced sensitivity - Li Li; Yanyu Xie; Chuanfa Luo; Guanwei Pen; Zi Min; Xigen Huang; Rumin Fu; Yansha Gao; Zongde Wang; Limin Lu (Food Chemistry, 2025)

Amyloid fibrils for β-carotene delivery – Influence of self-assembled structures on binding and in vitro release behavior - Congying Chen; Haifeng Wang; Qing Wang; Mengting Wang; David W. Everett; Min Huang; Yun Zhai; Teng Li; Yuying Fu (Food Chemistry, 2025)

Vanadium-assisted surface engineering of heterostructured cathode for enhanced protonic ceramic fuel cell performance - Min Fu; Yang Gao; Mingming Zhang; Nai Shi; Zetian Tao; Zongping Shao (Chemical Engineering Journal, 2025)

Protective effect of Apelin-13 on oxygen and glucose deprivation induced-damage in retinal ganglion cells cultured in vitro - Li Dai; Linlin Luo; Ya Zhang; Min Fu; Ling Yu (Journal of Molecular Histology, 2025)

Effects of dietary hydroxy-cinnamic acid derivatives on growth, muscle, and intestinal parameters of Tilapia (Oreochromis niloticus) - Qing Li; Min Fu; Shengqin Zhu; Juan Liu; Yanqing Li; Zhiyong Xue; Zhigang Zhou; Lijuan Yu (Fish Physiology and Biochemistry, 2025)

A Field Trial to Study the Effects of Stenella attenuata Deterrent on the Catch of a Light-Falling Net Fishery - Teng Wang; Jie Li; Lei Yan; Bin Xie; Peng Zhang; Zhongchang Song; Min Li; Weijie Fu; Yu Zhang (Journal of Marine Science and Engineering, 2025)
The incidental capture (bycatch) of protected cetaceans in fishing gear has become a serious problem worldwide. Bycatch has also had many serious consequences for pantropical spotted dolphins (Stenella attenuata) in the light-falling net fishery within this research area. We provided a self-developed acoustic deterrent device and conducted trials to investigate the long-term deterrent effects on Stenella attenuata and assess the influence of external factors on fishing catch. In 2022, 50 deterrence trials were conducted, of which 38 were effective and 12 were ineffective. In 2023, 30 deterrence trials were conducted: 24 effective and 6 ineffective. No dolphin bycatch occurred within a two-year period. Overall, the catch per unit effort (CPUE) of the effective deterrence nights was 4.96 ± 3.06 kg/min, while the CPUE of the ineffective nights was 3.78 ± 3.10 kg/min. There was a significant difference (p = 0.041, >0.05) between the two conditions. On the nights when dolphins did not appear, the average CPUE was 5.04 ± 4.44 kg/min. This CPUE was not different from the night on which deterrence was successful (p = 0.981, >0.05), but was considerably higher than night on which deterrence was unsuccessful (p = 0.028,

Trans-4-hydroxy-L-proline catabolism by Pseudomonadota in the ocean - Yan Wang; Zhen Wang; Wen-Xiao Zhao; Xiao-Jie Yuan; Yang Yu; Peng Wang; Min Wang; Andrew McMinn; Yu-Zhong Zhang; Ming Peng; Hui-Hui Fu; Xiu-Lan Chen (Marine Life Science & Technology, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Natural or man-made disaster? Lessons from the extreme rain and flood disaster in Zhengzhou, China on "2021.7.20″ - Yan Zhu; Yun Liu; Ling Zhu; Min Liu; Zhiqiang Xie; Junxu Chen; Xingfeng Fu; Qisheng Wang; Zhanhui Wang; Qingyun Du (Sustainable Cities and Society, 2025)

Identification of fractionation processes in the Himalayan leucogranites-Case study from the Nyalam region - Lei Yang; Calvin F. Miller; Jia-Min Wang; Xiao-Chi Liu; Fu-Yuan Wu (Lithos, 2025)

Can biodegradable film replace polyethylene film to obtain similar mulching effects on soil functions and maize productivity in irrigation region? A three-year experimental appraisal - Xiao-Bin Xiong; Peng-Yang Wang; Ze-Ying Zhao; Jing Wang; Shu-Tong Liu; Fu-Jian Mei; Wen-Ying Wang; Yi-Bo Wang; Xiang-Wen Fang; Ying Zhu; Jin-Lin Zhang; Ning Wang; et al. (Journal of Cleaner Production, 2025)

Unraveling the resistance mechanism of anammox granular sludge to iron nanoparticles - Xun Weng; Meng-Jiao Gao; Zheng Mao; Hui-Min Fu; Shi-Jun Li; Peng Yan; You-Peng Chen (Journal of Environmental Management, 2025)

Structural characteristics of areca nut seed neutral polysaccharide and its impact on gut microbiota from human feces - Mengfan Zhang; Haining Zhuang; Xiaowei Zhang; Xiaoyu Wang; Xia Fu; Sheng Chen; Lingyun Yao; Huatian Wang; Min Sun; Chuang Yu; Heng Yue; Tao Feng (Food Hydrocolloids, 2025)

Ultra-adhesive iontronic hydrogels strengthened by folded protein for flexible transducer with language recognition capabilities - Mansoor Khan; Luqman Ali Shah; Jun Fu; Fanghua Ning; Hyeong-Min Yoo (Chemical Engineering Journal, 2025)

Cs-Doped BCCF perovskite with enhanced surface proton acid sites for high-performance R-PCECs - Yang Gao; Kechen Liu; Xuan Zhang; Qi Li; Yinling Chang; Min Fu; Zetian Tao (Chemical Engineering Journal, 2025)

Novel Optimal Staggered Grid Finite Difference Scheme Based on Gram–Schmidt Procedure for Acoustic Wave Modelling - Min Zhang; Liming Zhou; Daiguang Fu; Shiqi Dong; Haibo Wu (Pure and Applied Geophysics, 2025)

Why the adventitious roots of poplar are so colorful: RNAseq and metabolomic analysis reveal anthocyanin accumulation in canker pathogens-induced adventitious roots in poplar - Min Li; Yuchen Fu; Jinxin Li; Wanna Shen; Li Wang; Zheng Li; Shiqi Zhang; Huixiang Liu; Xiaohua Su; Jiaping Zhao (Planta, 2025)

Selective Activation of G Protein–Coupled Estrogen Receptor 1 (GPER1) Reduces ER Stress and Pyroptosis via AMPK Signaling Pathway in Experimental Subarachnoid Hemorrhage - Yidan Liang; Wenqiao Fu; Yin Tang; Hongjiang Ye; Yanglingxi Wang; Chao Sun; Yi Xiang; Weiming Xiong; Min Cui; Yuanlin Chen; Ting Wang; Yongbing Deng (Molecular Neurobiology, 2025)

Intermittent fasting shifts the diurnal transcriptome atlas of transcription factors - Min Fu; Siyu Lu; Lijun Gong; Yiming Zhou; Fang Wei; Zhigui Duan; Rong Xiang; Frank J. Gonzalez; Guolin Li (Molecular and Cellular Biochemistry, 2025)

Long-term trend of the tropical cyclone translation speed over the western North Pacific with track change - Kai-Jie Fu; Yi‑Peng Guo; Zhe‑Min Tan (Climate Dynamics, 2025)

Large deformation characteristics and mechanism analysis of excavating shallow buried tunnel in reclamation areas - Huimin Gong; Yiguo Xue; Min Han; Fanmeng Kong; Kang Fu; Xudong Jiang (Bulletin of Engineering Geology and the Environment, 2025)

Organic matter determines the exchange of nutrients at sediment-water interface in coastal bays - Jiasen Zhong; Ehui Tan; Chunwei Fu; Guiyi Ma; Yongkai Chang; Zhixiong Huang; Jingchao Yin; Fengying Li; Jianzhong Su; Min Xu; Zhenzhen Zheng; Jian’an Liu; et al. (Acta Oceanologica Sinica, 2025)

Combined effect of polystyrene nanoparticles and chlorpyrifos to Daphnia magna - Yu-Hang Zhang; Rong-Yao Gao; Few Zhu; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2024)

Open shop scheduling with group and transportation operations by learning-driven hyper-heuristic algorithms - Yifeng Wang; Yaping Fu; Kaizhou Gao; Humyun Fuad Rahman; Min Huang (Swarm and Evolutionary Computation, 2024)

Metabolic engineering of Escherichia coli for upcycling of polyethylene terephthalate waste to vanillin - Yang Li; Xiao-Min Zhao; Si-Qi Chen; Zhao-Yuan Zhang; Qi-Sheng Fu; Shu-Min Chen; Sheng Chen; Jing Wu; Ke-Wei Xu; Ling-Qia Su; Zheng-Fei Yan (Science of The Total Environment, 2024)

Occurrence of legacy and emerging organophosphate flame retardants (OPFRs) on silicone wristbands: Comparison within couples - Jiaying Liu; Fumei Gao; Min Fu; Lei Wang; Huan Shen; Jianying Hu (Science of The Total Environment, 2024)

Investigating the effects of COVID-19 on sperm in male smokers: A prospective integrated proteomic and metabolomic study - ChengLu Wang; JiaCheng Zhang; Fang Gao; Min Zheng; XiaoHua Fu; KeBing Yang (Reproductive Toxicology, 2024)

Assessing the discrepant role of anions in the transformation of reactive oxygen species in H2O2 and PDS system: A comparative kinetic analysis - Ling Li; Min Cheng; Hao Sun; Huan Yi; Shiyu Liu; Mingming Zhang; Yukui Fu; Xuerong Zhou; Fuhang Xu; Dengsheng Ma; Guangming Zeng; Zhengjian Yang; et al. (Journal of Hazardous Materials, 2024)

Antibiotic resistance at environmental multi-media interfaces through integrated genotype and phenotype analysis - Chen-Xi Fu; Chen Chen; Qian Xiang; Yi-Fei Wang; Lu Wang; Feng-Yuan Qi; Dong Zhu; Hong-Zhe Li; Li Cui; Wei-Li Hong; Matthias C. Rillig; Yong-Guan Zhu; et al. (Journal of Hazardous Materials, 2024)

Synthesis of lipophilic vitamin C and evaluation of its antioxidant performance in sunflower seed oil frying - Min Fu; Juan Liu; Qing Li; Shengqin Zhu; Zhiyong Xue; Lijuan Yu; Zhigang Zhou (Food Chemistry, 2024)

Structural properties and antioxidant capacity of different aminated starch-phenolic acid conjugates - Feng-Kun An; Meng-Yun Li; Hai-Lu Luo; Xing-Long Liu; Zhen Fu; Min-Hong Ren (Food Chemistry, 2024)

Biomimetic mineralization synthesis of tricobalt tetraoxide/nitrogen doped carbon skeleton for enhanced capacitive deionization - Guoxiang Liu; Min Fu; Wenbin Wang; Siyuan Yang; Wei Chen; Ruitao Lv; Hao Yu; Dongmei Wang; Jianming Pan (Desalination, 2024)

Low total REE zircon formed in equilibrium with hornblende in granulitized eclogites: Implications for exhumation rates - Jia-Min Wang; Daniela Rubatto; Pierre Lanari; Yu-Lu Tian; Yi Chen; Fu-Yuan Wu (Earth and Planetary Science Letters, 2024)

Ultrasonic-Microwave extraction of glucoside alkaloids from potato peel residue and its antibacterial activity - Zhongliang Guan; Qingmin Chen; Ye Xu; Cong Han; Min Wang; Tao Zhao; Handong Zhao; Maorun Fu (Natural Product Research, 2024)

Advances in carbon sequestration technology using marine microalgae - Zixuan Min; Kui Wang; Hongguang Wang; Weiqi Fu; Bin Wu (Marine Biology Research, 2024)

Autophagy in Acute Lung Injury - Danjuan Liu; Shuoyun Weng; Chunjin Fu; Rongjie Guo; Min Chen; Bingbing Shi; Junting Weng (Cell Biochemistry and Biophysics, 2024)

The critical role of electron donating rate of pyrogenic carbon in mediating the degradation of phenols in the aquatic environment - Liang Zeng; Sizhe Yang; Quan Chen; Wang Fu; Min Wu; Patryk Oleszczuk; Bo Pan; Baoshan Xing (Water Research, 2024)

Tower-based profiles of wintertime secondary organic aerosols in the urban boundary layer over Guangzhou - Yao Li; Hong Ren; Shengzhen Zhou; Chenglei Pei; Min Gao; Yuxuan Liang; Dian Ye; Xijing Sun; Fenghua Li; Jun Zhao; Jian Hang; Shaojia Fan; et al. (Science of The Total Environment, 2024)

Shallow groundwater table fluctuations weaken nitrogen accumulation in the thin layer vadose zone of cropland around plateau lakes, Southwest China - Qingfei Chen; Anqiang Chen; Jinheng Min; Lin Li; Wanli Hu; Chi Wang; Bin Fu; Shufang Guo; Dan Zhang (Science of The Total Environment, 2024)

Rapid and extensive SARS-CoV-2 Omicron variant infection wave revealed by wastewater surveillance in Shenzhen following the lifting of a strict COVID-19 strategy - Yinghui Li; Chen Du; Ziquan Lv; Fuxiang Wang; Liping Zhou; Yuejing Peng; Wending Li; Yulin Fu; Jiangteng Song; Chunyan Jia; Xin Zhang; Mujun Liu; et al. (Science of The Total Environment, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Finite difference solution for contaminant transport through a GCL composite cutoff wall-aquifer system considering semipermeable membrane effect - He-Fu Pu; Sheng-Yi Deng; Ming Min; Yong-Wei Zhou (Journal of Hydrology, 2024)

Innovative upcycling gabions with coal bottom ash for nonpoint source pollution control against climate change - Min Woo Kang; Deok Hyun Moon; Hyun-Seog Roh; Yukwon Jeon; Hailu Fu; Sang Soo Lee (Journal of Cleaner Production, 2024)

Anti-seepage performance and oxygen barrier performance of the three-layered landfill cover system comprising neutralized slag under extreme climate conditions - Ming Min; He-Fu Pu; Xiao He; Sheng-Yi Deng (Engineering Geology, 2024)

NUS1 Variants Cause Lennox-Gastaut Syndrome Related to Unfolded Protein Reaction Activation - Nan-Xiang Shen; Xiao-Chong Qu; Jing Yu; Cui-Xia Fan; Fu-Li Min; Ling-Ying Li; Ming-Rui Zhang; Bing-Mei Li; Jie Wang; Na He; Wei-Ping Liao; Yi-Wu Shi; et al. (Molecular Neurobiology, 2024)

Advantages of targeted ventilation for farrowing houses: An analysis from perspectives of thermal environment, biosecurity and ventilation efficacy - Longhuan Du; Xuan Tao; Lin Zhu; Jinchuan Li; Min Fu; Jingwen Lai; Chaowu Yang; Zhiping He (Computers and Electronics in Agriculture, 2024)

Behavioral impairments and disrupted mitochondrial energy metabolism induced by polypropylene microplastics in zebrafish larvae - Jianghuan Hua; Taotao Zhang; Xianglin Chen; Biran Zhu; Min Zhao; Kaiyu Fu; Yindan Zhang; Huijia Tang; Hao Pang; Yongyong Guo; Jian Han; Lihua Yang; et al. (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local pH variability scenario: Prebiotic synthesis of cyclic dipeptides via prolinamide on the Hadean Earth - Xiaofan Guo; Li Zhang; Min Zhang; Songsen Fu; Yufen Zhao; Jianxi Ying (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

NiFe2O4/N-CNT mediated peroxydisulfate activation via radical and non-radical pathways for water purification - Hongchao Ma; Xinyue Wang; Min Qiao; Zixuan Liu; Md Azharul Hossain; Yinghuan Fu; Guowen Wang; Pengyuan Wang; Guolin Shao (Journal of Environmental Chemical Engineering, 2024)

Cascade–Assembly–Confined Multilevel Supramolecular Assemblies for Multicolor Luminescence Information Storage and Cells Imaging Based on Slipped Pseudo[5]rotaxane - Hong–Guang Fu; Min Liu; Hui–Juan Wang; Xin–Xin Shi; Jing Xu (Chemical Engineering Journal, 2024)

20 Seconds to fabricate high-performance NiFe-based anode for seawater electrolysis via bidirectional pulse current method - Hui Wu; Qiang Zhang; Qianfeng Liu; Min Li; Jiayi Liu; Jie Fu; Erdong Wang (Chemical Engineering Journal, 2024)

The construction of concentration gradient inducing low resistance for Li7La3Zr2O12-based thermal battery - Min Yang; Licai Fu; Jiajun Zhu; Wulin Yang; Lingping Zhou (Chemical Engineering Journal, 2024)

Proton transfer induced persistent triplet charge transfer phosphorescence in molecule-doped polymer systems - Shulin Liu; Chensheng Li; Liyun Liao; Yanping Huo; Zhong-Min Su; Fu-Shun Liang; Yingxiao Mu (Chemical Engineering Journal, 2024)

Identification of transcription factor BnHDG4-A08 as a novel candidate associated with the accumulation of oleic, linoleic, linolenic, and erucic acid in Brassica napus - Ying Fu; Min Yao; Ping Qiu; Maolin Song; Xiyuan Ni; Erli Niu; Jianghua Shi; Tanliu Wang; Yaofeng Zhang; Huasheng Yu; Lunwen Qian (Theoretical and Applied Genetics, 2024)

Gut microbiota dynamics in KK-Ay mice: restoration following antibiotic treatment - Jinni Hong; Tingting Fu; Weizhen Liu; Miao Yu; Yanshan Lin; Cunyun Min; Datao Lin (Folia Microbiologica, 2024)

Aerosol in the subarctic region impacts on Atlantic meridional overturning circulation under global warming - Di Chen; Qizhen Sun; Min Fu (Climate Dynamics, 2024)

Molecular-level insights into dissolved organic matter and its variations of the full-scale processes in a typical petrochemical wastewater treatment plant - Min Li; Zhouyang Li; Liya Fu; Liyan Deng; Changyong Wu (Water Research, 2024)

Effects of climate warming on soil nitrogen cycles and bamboo growth in core giant panda habitat - Dongyao Zhang; Hongbo Yang; Jindong Zhang; Min Xu; Weihua Xu; Jianchao Fu; Bin Feng; Hu Zhang; Qiongyu Huang; Daifu Wu; Zejun Zhang; Melissa Songer; et al. (Science of The Total Environment, 2024)

Preparation and application of cattail residue-based magnetic cellulose composites for tetracycline antibiotics adsorption - Tao Fu; Suqing Wu; Min Zhao; Xiangyong Zheng; Zhiquan Wang; Zhenmin Jin; Chunzhen Fan (Process Safety and Environmental Protection, 2024)

Diffusive and ebullitive methane emissions under tidal fluctuation and climate warming in a nutrient-rich subtropical estuary - Mengting Qi; Xiaofei Li; Ye Li; Yuxuan Fu; Lijun Hou; Min Liu (Journal of Hydrology, 2024)

Versatile applications and mechanisms of genus Exiguobacterium in bioremediating heavy metals and organic pollutants: A review - Min Xiao; Zhong-er Long; Xueqin Fu; Long Zou (International Biodeterioration & Biodegradation, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

MS2/GmAMS1 encodes a bHLH transcription factor important for tapetum degeneration in soybean - Junping Yu; Yan Xu; Yuanyuan Huang; Yuxue Zhu; Lulu Zhou; Yunpeng Zhang; Bingyao Li; Hao Liu; Aigen Fu; Min Xu (Plant Cell Reports, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

Review on the Role of Mitochondrial Dysfunction in Septic Encephalopathy - Chunjin Fu; Shuoyun Weng; Danjuan Liu; Rongjie Guo; Min Chen; Bingbing Shi; Junting Weng (Cell Biochemistry and Biophysics, 2024)

Deep learning-based geological map generation using geological routes - Chaoling Li; Fengdan Li; Chang Liu; Zhen Tang; Si Fu; Min Lin; Xia Lv; Shuang Liu; Yuanyuan Liu (Remote Sensing of Environment, 2024)

Shallow groundwater table fluctuations promote the accumulation and loss of phosphorus from surface soil to deeper soil in croplands around plateau lakes in Southwest China - Qingfei Chen; Wenchao Li; Anqiang Chen; Jinheng Min; Wanli Hu; Chi Wang; Bin Fu; Dan Zhang (Journal of Environmental Management, 2024)

Biochar promotes microbial CO2 fixation by regulating feedback inhibition of metabolites - Xiaodi Zhao; Yundong Liu; Li Xie; Xiaohua Fu; Lei Wang; Min-tian Gao; Jiajun Hu (Bioresource Technology, 2024)

m6A-Mediated Upregulation of lncRNA CHASERR Promotes the Progression of Glioma by Modulating the miR-6893-3p/TRIM14 Axis - Xingwei Wu; Minjie Fu; Chang Ge; Hanyu Zhou; Haoyu Huang; Min Zhong; Mengying Zhang; Hao Xu; Guoping Zhu; Wei Hua; Kun Lv; Hui Yang (Molecular Neurobiology, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

New insights into the influences of firework combustion on molecular composition and formation of sulfur- and halogen-containing organic compounds - Caiqing Yan; Haibiao Chen; Fei Xu; Qinglong Fu; Ying Zhou; Ruizhi Zhou; Ruiyu Li; Mei Zheng; Mingjie Xie; Bin Jiang; Zhisheng Zhang; He Meng; et al. (Science of The Total Environment, 2024)

Transient analytical solution for coupled water–gas transport in unsaturated soil cover of landfill - He-Fu Pu; Ming Min; Sheng-Yi Deng; Xiao-Jun Wen; Jun Xu (Journal of Hydrology, 2024)

Nanobubbles improve peroxymonosulfate-based advanced oxidation: High efficiency, low toxicity/cost, and novel collaborative mechanism - Jun Bo Zhang; Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Xueji You; Min-tian Gao; Jixiang Li; Rongbing Fu; Yalei Zhang; Kah Hon Leong; Xing Song Xu (Journal of Hazardous Materials, 2024)

Interactions between intestinal microbiota and metabolites in zebrafish larvae exposed to polystyrene nanoplastics: Implications for intestinal health and glycolipid metabolism - Biran Zhu; Xianglin Chen; Taotao Zhang; Qianqian Zhang; Kaiyu Fu; Jianghuan Hua; Mengyuan Zhang; Qing Qi; Binbin Zhao; Min Zhao; Lihua Yang; Bingsheng Zhou (Journal of Hazardous Materials, 2024)

Rapid visual detection of sulfur dioxide residues in food using acid-sensitive CdTe quantum dots-loaded alginate hydrogel beads - Wei Lan; Yanmin Rao; Xiangyu Zhao; Yi Zhao; Xinyi Min; Yue Wu; Ziyi Jiang; Ting Li; Yinhua Li; Hengye Chen; Wanjun Long; Yuanbin She; et al. (Food Chemistry, 2024)

Innovative fertilizer management system maintains higher maize productivity with lower environmental costs in the Loess Plateau region of China - Peng Wu; Hua Huang; Qi Wu; Fu Liu; Liangqi Ren; Zihui Zhang; Benzheng Liu; Guoxia Zhou; Bingbing Cao; Kemoh Bangura; Jianfu Xue; Min Sun; et al. (Field Crops Research, 2024)

The construction of Cs3MoxSbyBr9/BiVO4 S-scheme heterojunction photocatalyst for efficient photocatalytic N2 fixation - Zhao-Lei Liu; Han-Ying Luo; Meng-Ran Zhang; Yan-Fei Mu; Fu-Quan Bai; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2024)

Divergent responses of soil microbial community to long-term nitrogen and phosphorus additions in a subtropical Chinese fir plantation - Fangchao Wang; Qiao Liu; Xiaofei Hu; Xiang-Min Fang; Shengnan Wang; Fu-Sheng Chen (CATENA, 2024)

Prokaryotic expression, purification, and the in vitro and in vivo protection study of dehydrin WDHN2 from Triticum aestivum - Hongmei Zhang; Jiafa Wu; Dandan Fu; Min Zhang; Lunji Wang; Minggui Gong (Protoplasma, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Unveiling toxicity profile for food risk components: A manually curated toxicological databank of food-relevant chemicals - Xing-Xing Shi; Fan Wang; Zhi-Zheng Wang; Guang-Yi Huang; Min Li; Jesus Simal-Gandara; Ge-Fei Hao; Guang-Fu Yang (Critical Reviews in Food Science and Nutrition, 2024)

Low temperature acclimation of electroactive microorganisms may be an effective strategy to enhance the toxicity sensing performance of microbial fuel cell sensors - Yazhi Nong; Min Xu; Bingchuan Liu; Jianfeng Li; Dongye He; Chuanfu Li; Pinyi Lin; Yin Luo; Chenyuan Dang; Jie Fu (Water Research, 2024)

Comparison of the osteogenic potential of fibroblasts from different sources - Jiaojiao Li; Liangliang Fu; Qian Lu; Shuling Guo; Si Chen; Ting Xia; Min Wang; Liangwen Chen; Yi Bai; Haibin Xia (Tissue and Cell, 2024)

Ocean eddy detection based on YOLO deep learning algorithm by synthetic aperture radar data - Nannan Zi; Xiao-Ming Li; Martin Gade; Han Fu; Sisi Min (Remote Sensing of Environment, 2024)

The delaying effect of Clausena lansium extract on pear ring rot is related to its antifungal activity and induced disease resistance - Wen-Wu Song; Xiao-Xiang Fu; Duan-Tao Cao; Xiao-Gui Liang; Su-Ling Xiao; Min-Xuan Yuan; Ying-Jin Huang; Qing-Hong Zhou; Hong-Yi Wei; Jun-Wen Wang; Wen-Wen Peng (Postharvest Biology and Technology, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

High H-abstraction efficiency of Ni(II)-Ni(III)-Ni(II) cycle mediated oxidation of aromatic contaminants by peroxydisulfate - Jia Song; Hong-Sen Yi; Jiang-Lei Zhang; Huan-Dong Zhou; Fu-Min Wang; Xu Han; Jun Cao (Journal of Environmental Chemical Engineering, 2024)

Acceleration of the charge transfer rate for efficient photocatalytic hydrogen production via adjusting modulator and introducing electronic bridge dual strategies - Xingyan Liu; Haibo Zhou; Ruolan Li; Maosen Xu; Chenghua Zhang; Zhengsijia Wu; Youzhou He; Xu Zou; Min Fu; Siping Wei (Fuel, 2024)

Correlations of dynamic changes in lipid and protein of salted large yellow croaker during storage - Min Zhang; Jing-jing Fu; Jun-long Mao; Xiu-ping Dong; Yue-wen Chen (Food Research International, 2024)

Bimetallic iron-copper nanozyme for determination and degradation of norfloxacin in foods - Cong Cheng; Min Han; Gang Xiang; Xiaoying Fu; Xianxing Wang; Changfang Lu (Food Chemistry, 2024)

Tissue factor pathway inhibitors disrupt structures of rhabdovirus/ranairidovirus and inhibit viral infection in Chinese perch, Siniperca chuatsi - Baofu Ma; Jingkang Li; Min Zhang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Xia Luo; Lihui Liu; Jianguo Su; Jin Zhou; Ningqiu Li (Fish & Shellfish Immunology, 2024)

Vertically aligned and conformal BN-coated carbon fiber to achieve enhanced thermal conductivity and electrical insulation of a thermal interface material - Min Huang; Zhiqian Wang; Nizao Kong; Biao Li; Chong Ye; Kun Jia; Liqin Fu; Yexin Tian; Donghong Wang; Fei Han (Chemical Engineering Journal, 2024)

Biosynthetic potential of uncultured anammox community bacteria revealed through multi-omics analysis - Yi-Cheng Wang; Hui-Min Fu; Yu Shen; Jin Wang; Nuo Wang; You-Peng Chen; Peng Yan (Bioresource Technology, 2024)

Identification of important gene signatures in schizophrenia through feature fusion and genetic algorithm - Zhixiong Chen; Ruiquan Ge; Changmiao Wang; Ahmed Elazab; Xianjun Fu; Wenwen Min; Feiwei Qin; Gangyong Jia; Xiaopeng Fan (Mammalian Genome, 2024)

Draconibacterium aestuarii sp.nov., a Glycolipid-Producing Bacterium Isolated from Tidal Flat Sediment and Emended Description of the Genus Draconibacterium - Jia-Yan Wang; Sha-Sha Qiu; Yue Su; Wei-Yu Pan; Tao Wang; Wen-Wu Zhang; Ge-Yi Fu; Min Wu (Current Microbiology, 2024)

Molecular Mechanism of Yangshen Maidong Decoction in the Treatment of Chronic Heart Failure based on Network Pharmacology, Molecular Docking, and Molecular Dynamics Simulations - Wei Cheng; Bo-Feng Zhang; Na Chen; Qun Liu; Xin Ma; Xiao Fu; Min Xu (Cell Biochemistry and Biophysics, 2024)

Characteristics of typical intermediate and semi volatile organic compounds in Shanghai during China International Import Expo event - Taikui An; Yingjie Li; Rui Wang; Sheng'ao Jing; Yaqin Gao; Shuyu Liu; Dandan Huang; Min Zhou; Haixia Dai; Cheng Huang; Jun Lu; Hongli Wang; et al. (Chemosphere, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Swimming short fibrous nasal drops achieving intraventricular administration - Juan Wang; Qiuyun Wang; Yifei Fu; Min Lu; Liang Chen; Zhiheng Liu; Xiaohan Fu; Xiyu Du; Buwei Yu; Han Lu; Wenguo Cui (Science Bulletin, 2024)

Garnet and zircon petrochronology reveal coherent subduction and exhumation of eclogites and associated schists in the Changning–Menglian orogenic belt, southeast Tibet - Ying Zhou; Hao Cheng; Zhi-min Peng; Yu-zhen Fu; Kai-Yang Du (Lithos, 2024)

Corrigendum to “Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients” [J. Trace Elem. Med. Biol. 83 (2024) 127415] - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

Arsenic exposure and pulmonary function decline: Potential mediating role of TRAIL in chronic obstructive pulmonary disease patients - Ying Liu; Feng-Min Zhu; Juan Xu; You-Peng Deng; Jing Sun; Qi-Yuan He; Zhen-Yu Cheng; Min-Min Tang; Jin Yang; Lin Fu; Hui Zhao (Journal of Trace Elements in Medicine and Biology, 2024)

The role of superoxide anion to Cr(VI) reduction by pine biochar - Wang Fu; Min Wu; Quan Chen; Yundie Liang; Hongbo Peng; Liang Zeng; Bo Pan (Journal of Hazardous Materials, 2024)

6PPDQ induces cardiomyocyte senescence via AhR/ROS-mediated autophagic flux blockage - Baoqiang Fu; Tao Chen; Bin Jiang; Haobin Feng; Ziyu Zhu; Min Li; Guoxing Zhang; Yan Jiang (Environmental Pollution, 2024)

A novel mycelial pellet applied to remove polycyclic aromatic hydrocarbons: High adsorption performance & its mechanisms - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Min-tian Gao; Yalei Zhang; Kah Hon Leong; Rongbing Fu; Lang Zhou (Science of The Total Environment, 2024)

Identification of Indian crustal melting beneath Gangdese arc during India-Asia collision - Shao-Xiong He; Christopher J. Spencer; Xiao-Chi Liu; Fangyang Hu; Jia-Min Wang; Wei-Qiang Ji; Fu-Yuan Wu (Lithos, 2024)

Petrogenetic link between leucogranite and spodumene pegmatite in Lhozhag, eastern Himalaya: Constraints from U–(Th)–Pb geochronology and Li–Nd–Hf isotopes - Lei Yang; Jia-Min Wang; Xiao-Chi Liu; Fang-Yang Hu; Kang-Shi Hou; Jian-Gang Fu; Guang-Ming Li; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2024)

Analysis of novel In2S3/polyimide Z-scheme heterojunctions with enhanced photocatalytic target compound degradation efficiency - Min Fu; Mei Yang; Jinwu Bai; Yi Li; Meng Fang; Peng Lu; Xue Kuang (Journal of Environmental Chemical Engineering, 2024)

Silurian–Devonian construction of active continental margin in the southwestern Paleo-Asian Ocean witnesses the modification of fluvial system by early land plants - Yan Xu; Bo Liu; Yuyang Liu; Bao-Fu Han; Hao Sun; Chaoqiang Chen; Min Qin (Gondwana Research, 2024)

Modelling of sulfur chemistry in a fog episode in northern China and implication for the efficacy of SO2 emission control - Leyi Yuan; Mingxu Liu; Xinyi Dang; Hao Wu; Fang Shang; Lianfang Wei; Pingqing Fu; Yu Song; Min Hu (Atmospheric Environment, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Effect and identification of different allele combinations of SSIIa and Wx on rice eating and cooking quality - Siqi Zhang; Aoqiu Fu; Min Guo; Jinxuan Li; Zhiqing Tan; Tao Guo; Hua Zhou; Guili Yang (Euphytica, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Motility behavior and physiological response mechanisms of aerobic denitrifier, Enterobacter cloacae strain HNR under high salt stress: Insights from individual cells to populations - Meng Cheng; Hui-Min Fu; Zheng Mao; Peng Yan; Xun Weng; Teng-Fei Ma; Xiao-Wei Xu; Jin-Song Guo; Fang Fang; You-Peng Chen (Science of The Total Environment, 2024)

Pathological and genome assembly of transcriptome sequencing data implied multiple relationships between bean common mosaic virus (BCMV), Batocera lineolata and aphids in Populus alba var. pyramidalis - Min Li; Jinxin Li; Yanxia Yao; Rui Yang; Yuchen Fu; Li Wang; Wanna Shen; Huixiang Liu; Ya Liu; Jiaping Zhao (Physiological and Molecular Plant Pathology, 2024)

Selective enrichment of virulence factor genes in the plastisphere under antibiotic and heavy metal pressures - Lu Wang; Tian-Lun Zhang; Qian Xiang; Chen-Xi Fu; Min Qiao; Long-Jun Ding; Dong Zhu (Journal of Hazardous Materials, 2024)

Complementary imaging of nanoclusters interacting with mitochondria via stimulated emission depletion and scanning transmission electron microscopy - Dan Zhao; Lu Gao; Xiaoyu Huang; Gang Chen; Beibei Gao; Jing Wang; Min Gu; Fu Wang (Journal of Hazardous Materials, 2024)

Use of model substitution in the inversion of dispersion curves in weak subsurface layers - Daiguang Fu; Shuangxi Zhang; Mengkui Li; Liming Zhou; Min Zhang (Journal of Applied Geophysics, 2024)

Sandwich assay for β-lactoglobulin in infant food formula based on a hierarchically architectured antifouling capture probe and fluorescent recognition probe - Huan Li; Donghui Jia; Jiangbing Shuai; Xiaofeng Zhang; Shunyu Wang; Min Wang; Ke Li; Linglin Fu (Food Chemistry, 2024)

Exosome-shuttled FTO from BM-MSCs contributes to cancer malignancy and chemoresistance in acute myeloid leukemia by inducing m6A-demethylation: A nano-based investigation - Ruirui Kou; Tian Li; Caizhu Fu; Duanfeng Jiang; Yue Wang; Jie Meng; Ruilan Zhong; Changjiu Liang; Min Dong (Environmental Research, 2024)

Formation of lithium-rich pegmatites via rapid crystallization and shearing – case study from the South Tibetan Detachment, Himalaya - Xiao-Chi Liu; Matthew J. Kohn; Jia-Min Wang; Shao-Xiong He; Ru-Cheng Wang; Fu-Yuan Wu (Earth and Planetary Science Letters, 2024)

Constructing light-insensitive Ag(I) sites by in situ integration of nanoheaters for efficient adsorptive desulfurization - Jun Liu; Zhen Fu; Peng Tan; Min Li; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Enhanced removal of Cd2+ from water by a bacterioferritin from Candidatus Kuenenia stuttgartiensis within engineering bacteria - Jin Wang; Cui-Zhong Chen; Yi-Cheng Wang; Hui-Min Fu; Peng Yan; You-Peng Chen (Chemical Engineering Journal, 2024)

Iron oxide nanoclusters formed by acid-induced in situ calcium ion cross-linking for targeted magnetic resonance imaging of glioblastoma - Ruoxi Xie; Shengxiang Fu; Guannan Zhu; Hua Ai; Bin Song; Su Lui; Gaocan Li; Yunbing Wang; Min Wu (Chemical Engineering Journal, 2024)

Genetic lineage tracing identifies adaptive mechanisms of pancreatic islet β cells in various mouse models of diabetes with distinct age of initiation - Qi Fu; Yu Qian; Hemin Jiang; Yunqiang He; Hao Dai; Yang Chen; Zhiqing Xia; Yucheng Liang; Yuncai Zhou; Rui Gao; Shuai Zheng; Hui Lv; et al. (Science China Life Sciences, 2024)

One-pot synthesized Au@Pt nanostars-based lateral flow immunoassay for colorimetric and photothermal dual-mode detection of SARS-CoV-2 nucleocapsid antibody - Jinyue Zhu; Gengchen Guo; Jianting Liu; Xiang Li; Xianning Yang; Min Liu; Chunhui Fu; Jingbin Zeng; Jingwen Li (Analytica Chimica Acta, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Kelp breeding in China: Challenges and opportunities for solutions - Zi‐Min Hu; Ti‐Feng Shan; Quan‐Sheng Zhang; Fu‐Li Liu; Alexander Jueterbock; Gaoge Wang; Zhong‐Min Sun; Xiang‐Yu Wang; Wei‐Zhou Chen; Alan T. Critchley; Nai‐Hao Ye (Reviews in Aquaculture, 2024)
Breeding has played an important role in the mariculture and industrialization of kelp in China. However, the current kelp breeding systems in China have encountered some problems relating to germplasm diversity, management, technological innovations, and regional co‐operation. This review summarizes the main challenges, such as top‐down and fragmented management of germplasm libraries, as well as private industry breeding without government regulations, inter‐cultivar accidental admixing and genetic erosion, loss of heterozygosity due to repeated selection and self‐crossing. We outline multiple potential approaches to breed cultivars with improved qualitative/quantitative traits which can be subjected to changing environments, for example: (i) establishing a national germplasm repository to enhance integrative collection and preservation of kelp resources; (ii) planning and implementing kelp breeding programmes according to strategic priorities and goal‐orientations; (iii) optimizing a hybridization‐based breeding pipeline to produce robust cultivars through the introgression of novel alleles and thus the expression of hybrid vigour; (iv) enriching the high‐quality annotated reference genomes and functional analysis of trait‐associated markers/loci to develop DNA‐based breeding technologies; (v) developing new priming‐based (e.g., thermal and disease resistance) bio‐engineering breeding strategies to meet future unpredictable climate change; and (vi) breeding towards an ecological kelp‐microbiome interaction‐based technique to produce cultivars with enhanced performance and adaptability to environmental scenarios. Collectively, the lessons learned from kelp breeding in China and the solutions proposed here may not only potentially improve or re‐invigorate the Chinese kelp industry, but will also assist other developing countries in taking corrective actions to develop a sustainable future kelp farming industry.

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Aluminum-based ozone catalysts prepared by mixing method: Characteristics, performance and carbon emissions - Yingming Hu; Panxin Wang; Yin Yu; Min Li; Hongbo Xi; Liya Fu; Changyong Wu (Chemosphere, 2024)

Mono-2-ethylhexylphthalate (MEHP) is a potent agonist of human TRPA1 channel - Megan Goh; Lin Fu; Wei-Guang Seetoh; Ann Koay; Huang Hua; Shi Min Tan; Shermaine Huiping Tay; Elaine Chin Jinfeng; Nimo Abdullah; Shi Yan Ng; Manikandan Lakshmanan; Prakash Arumugam (Chemosphere, 2024)

Numerical simulation method and deterioration analysis of load-bearing performance of tunnel linings containing cold joints in plain concrete - Huang-Shi Deng; He-Lin Fu; Yi-Min Wu; Yi-Bo Zhao; Hai-Dong Yi (Tunnelling and Underground Space Technology, 2024)

Can deep fertilization in spring maize fields improve soil properties and their distribution in soil profile? - Peng Wu; Qi Wu; Hua Huang; Fu Liu; Kemoh Bangura; Tie Cai; Jian Fu; Min Sun; Jianfu Xue; Peng Zhang; Zhiqiang Gao; Zhikuan Jia (Journal of Environmental Management, 2024)

Metatranscriptomic insights into the microbial metabolic activities during an Ulva prolifera green tide in coastal Qingdao areas - Xinyi Wang; Hao Yu; Yan Li; Qianru Fu; Hongbing Shao; Hui He; Min Wang (Environmental Pollution, 2024)

Ultrathin RhCu bimetallenes for the selective electro-oxidation of glycerol - Qing-Ling Hong; Yue Zhao; Xuan Ai; Yu Ding; Fu-Min Li; Pei Chen; Pu-Jun Jin; Yu Chen (Chemical Engineering Journal, 2024)

In situ dual-interface layer enabling lower resistance of Ta-doped Li7La3Zr2O12-based thermal battery - Min Yang; Lingping Zhou; Jiajun Zhu; Wulin Yang; Licai Fu (Chemical Engineering Journal, 2024)

Eco-friendly and stable triclosan removal from groundwater using peroxyacetic acid activated with biochar produced from saccharification residues - Wang Kai Tong; Chaomeng Dai; Chenyan Jia; Jiajun Hu; Min-tian Gao; Jixiang Li; Jun Bo Zhang; Han Tang; Yucang Liang; Wei Teng; Zhi Li; Shuguang Liu; et al. (Chemical Engineering Journal, 2024)

Cuprotosis clusters predict prognosis and immunotherapy response in low-grade glioma - Wenjun Zhu; Ziqi Chen; Min Fu; Qianxia Li; Xin Chen; Xiaoyu Li; Na Luo; Wenhua Tang; Feng Yang; Yiling Zhang; Yuanyuan Zhang; Xiaohong Peng; et al. (Apoptosis, 2024)
Cuprotosis, an emerging mode of cell death, has recently caught the attention of researchers worldwide. However, its impact on low-grade glioma (LGG) patients has not been fully explored. To gain a deeper insight into the relationship between cuprotosis and LGG patients’ prognosis, we conducted this study in which LGG patients were divided into two clusters based on the expression of 18 cuprotosis-related genes. We found that LGG patients in cluster A had better prognosis than those in cluster B. The two clusters also differed in terms of immune cell infiltration and biological functions. Moreover, we identified differentially expressed genes (DEGs) between the two clusters and developed a cuprotosis-related prognostic signature through the least absolute shrinkage and selection operator (LASSO) analysis in the TCGA training cohort. This signature divided LGG patients into high- and low-risk groups, with the high-risk group having significantly shorter overall survival (OS) time than the low-risk group. Its predictive reliability for prognosis in LGG patients was confirmed by the TCGA internal validation cohort, CGGA325 cohort and CGGA693 cohort. Additionally, a nomogram was used to predict the 1-, 3-, and 5-year OS rates of each patient. The analysis of immune checkpoints and tumor mutation burden (TMB) has revealed that individuals belonging to high-risk groups have a greater chance of benefiting from immunotherapy. Functional experiments confirmed that interfering with the signature gene TNFRSF11B inhibited LGG cell proliferation and migration. Overall, this study shed light on the importance of cuprotosis in LGG patient prognosis. The cuprotosis-related prognostic signature is a reliable predictor for patient outcomes and immunotherapeutic response and can help to develop new therapies for LGG.

Unveiling the crucial role of soil microorganisms in carbon cycling: A review - Haowei Wu; Huiling Cui; Chenxi Fu; Ran Li; Fengyuan Qi; Zhelun Liu; Guang Yang; Keqing Xiao; Min Qiao (Science of The Total Environment, 2024)

Synthesis and application of wetland plant-based functional materials for aqueous antibiotics removal - Tao Fu; Linna Du; Suqing Wu; Min Zhao; Xiangyong Zheng; Zhiquan Wang; Yejian Zhang; Chunzhen Fan; Wen Wang; Fuyuan Ran; Ping Lin; Chunjie Zhong (Science of The Total Environment, 2024)

A novel eco-friendly strategy for removing phenanthrene from groundwater: Synergism of nanobubbles and rhamnolipid - Wang Kai Tong; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Xueji You; Xin Ru Feng; Zhi Li; Lang Zhou; Yalei Zhang; Xiaoying Lai; Long Kahon; et al. (Science of The Total Environment, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Buchan-type metamorphic decarbonation during the upward expansion of the South Tibetan Detachment System: A new carbon source in the Himalaya - Jia-Min Wang; Kyle Patrick Larson; Jin-Jiang Zhang; Liang Zhao; Fu-Yuan Wu (Lithos, 2024)

Bridging the sustainable circular economy in cosmetic cross-supply chain practices under uncertainties: A data-driven influential model - Kuo-Jui Wu; Min Fu; Mohd Helmi Ali; Ming K. Lim; Ming-Lang Tseng (Journal of Cleaner Production, 2024)

Fluorescent and smartphone imaging detection of tetracycline residues based on luminescent europium ion-functionalized the regular octahedral UiO-66-NH2 - Xiaoyue Yue; Long Fu; Jingwen Zhou; Yan Li; Min Li; Yawen Wang; Yanhong Bai (Food Chemistry, 2024)

Regulating the crystallinity and hydrophobicity of cobalt boride nanosheet for enhanced CO2 photoreduction performance - Xinyan Xiao; Zheyang Liu; Min Zhou; Wei Zhang; Xiaohong Fu; Huaming Li; Zhifeng Jiang (Chemical Engineering Journal, 2024)

Exploring recharge mechanisms of soil water in the thick unsaturated zone using water isotopes in the North China Plain - Huawu Wu; Fan Song; Leilei Min; Jing Li; Yanjun Shen; Yanan Huang; Hongxiang Fan; Jinzhao Liu; Congsheng Fu (CATENA, 2024)

Metabolic engineering of Paenibacillus polymyxa for effective production of 2,3-butanediol from poplar hydrolysate - Jikun Zhang; Jianzhi Zhao; Quanbin Fu; Haiyang Liu; Min Li; Zhongyue Wang; Wei Gu; Xueming Zhu; Rongshan Lin; Li Dai; Kai Liu; Chengqiang Wang (Bioresource Technology, 2024)

Simvastatin ameliorates synaptic plasticity impairment in chronic mild stress-induced depressed mice by modulating hippocampal NMDA receptor - Xu-Ben Yu; Kai-Long Zhong; Chuang Chen; Jing Fu; Fang Chen; Hong-Min Zhou; Xiu-Hua Zhang; Kwonseop Kim; Jing-Ye Pan (Psychopharmacology, 2024)

Involvement and Possible Mechanism of Autophagy in Postharvest Tomato Fruit Resistance Against Botrytis cinerea - Dedong Min; Xiaodong Fu; Maratab Ali; Jiong Liu; Wenwen Sun; Meiqi Li; Fujun Li; Xiaoan Li; Xinhua Zhang (Journal of Plant Growth Regulation, 2024)

Staphylococcus warneri strain XSB102 exacerbates psoriasis and promotes keratinocyte proliferation in imiquimod-induced psoriasis-like dermatitis mice - Wenhao Si; Min Li; Kuan Wang; Jialin Li; Mengke Xu; Xiaoyue Zhou; Jie Bai; Zhiyuan Qu; Guoyan Song; Xueya Wu; Yuqi Guo; Hua Hu; et al. (Archives of Microbiology, 2024)

Spatially resolved transcriptomics reveals distinct pulmonary immune responses during influenza virus and SARS-CoV-2 infections - Min Zhao; Fei Shao; Zhen Liu; Jiangwen Ma; Dou Yu; Hangjie Zhang; Lianpan Dai; Kun Xu; Xin Zhao; Mengli Zheng; George Fu Gao; Shuo Wang (Science Bulletin, 2023)

Fate of iron nanoparticles in anammox system: Dissolution, migration and transformation - Xun Weng; Hui-Min Fu; Zheng Mao; Peng Yan; Xiao-Wei Xu; Yu Shen; You-Peng Chen (Journal of Environmental Management, 2023)

Lipidomics reveals the relationship between lipid oxidation and flavor formation of basic amnio acids participated Low-Sodium cured large yellow croaker - Min Zhang; Jing-Jing Fu; Jun-Long Mao; Xiu-Ping Dong; Yue-Wen Chen (Food Chemistry, 2023)

Multifunctional 0D@2D (Mox-Mn)Sy-NPs@MXene hybrid electrode with high rate-capability and ultra-long cycling life for Li-ion battery and all Molybdenum-MXene-based 1.9 (V) asymmetric supercapacitor - Ghuzanfar Saeed; Asrar Alam; Shufeng Bo; Jun Su; Min Chang Kim; Liguo Zhang; Youngjoong Choi; Shrikant Sadavar; Hao Fu; Ho Seok Park; Kwang Ho Kim (Chemical Engineering Journal, 2023)

Influence of ship emissions on PM2.5 in Shanghai: From COVID19 to OMICRON22 lockdown episodes - Yusen Duan; Meng Wang; Yin Shen; Min Yi; Qingyan Fu; Jia Chen; Guangli Xiu (Atmospheric Environment, 2023)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

Unveiling the impact of digital industrialization on synergistic governance of pollution and carbon reduction in China: a geospatial perspective - Jiachao Peng; Min Zhou; Ming Yi; Shuke Fu (Environmental Science and Pollution Research, 2023)

Effects of simulated warming on soil properties and bacterial community composition in the Bashania faberi ecosystem - Jianchao Fu; Jun Wu; Min Xu; Jing Ma; Lulu Long; Chao Chen; Gang Yang; Chun Song; Xiaohong Zhang; Hongbo Yang; Jindong Zhang (Applied Soil Ecology, 2023)

Factors affecting the accumulation of organotins by wild fish: A case study in the Three Gorges Reservoir, China - Jun-min Gao; Jia You; Jing-cheng Wu; Jin-song Guo; Ping-ting Fu; Li-xia Zhang (Environmental Science and Pollution Research, 2023)

Cretaceous Nb-enriched basalts in the western Gan-Hang belt, South China: A response to slab window opening during the Paleo-Pacific ridge subduction - Qiong Chen; Mei-Fu Zhou; Min Sun; Hao Cheng; Ping-Ping Liu (Lithos, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Flavor characteristics of semi-dried yellow croaker (Pseudosciaena crocea) with KCl and ultrasound under sodium-reduced conditions before and after low temperature vacuum heating - Junlong Mao; Jingjing Fu; Zhengyu Zhu; Zhenzhi Cao; Min Zhang; Yanwei Yuan; Tingting Chai; Yuewen Chen (Food Chemistry, 2023)

Arsenic exposure and lung function decline in chronic obstructive pulmonary disease patients: The mediating influence of systematic inflammation and oxidative stress - Yun-Feng Liu; Min-Min Tang; Jing Sun; Jia-Fei Li; Ya-Lin Jiang; Hui Zhao; Lin Fu (Food and Chemical Toxicology, 2023)

Long-term anthropogenic field management enhanced wheat productivity and resource utilization in the Loess Plateau region of China - Peng Wu; Gang Zhao; Qi Wu; Hua Huang; Peng Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; Shangzhong Li; Lei Wang; Wanli Cheng; Jian Fu; et al. (European Journal of Agronomy, 2023)

Learning-Based personal models for joint optimization of thermal comfort and energy consumption in flexible workplaces - Min Deng; Bo Fu; Carol C. Menassa; Vineet R. Kamat (Energy and Buildings, 2023)

Analytical solutions for contaminant transport through a GMB/CCL composite liner system considering effective porosity and thermodiffusion - Jin-Wei Qiu; Lu-Sha Jiang; He-Fu Pu; Ding-Bao Song; Ming Min; Jun Tong (Computers and Geotechnics, 2023)

Effect of the inoculation of Phanerochaete chrysosporium on nitrogen migration and organic matter conversion during electrolytic manganese residue composting - Xiangyu Peng; Ming Yan; Qingqing Xie; Lan Gao; Xiaojuan Pu; Yukui Fu; Hanwen Liu; Min Cheng; Piao Xu; Danlian Huang; Lin Tang (Bioresource Technology, 2023)

Transcriptome Analysis Revealed the Differential Molecular Response Mechanisms of Roots, Stems, and Leaves in Mung Bean to Cadmium Stress - Ping-min Wu; Yan Leng; Shi-Weng Li; Yu-Lin Wang; Fu-Jun Qiao (Journal of Plant Growth Regulation, 2023)

Carbon emissions induced by land use and land cover change amid rapid urbanization in Chengdu-Chongqing economic circle, China: efficiency, transfer and process - Zhonglin Tang; Shan Ma; Min Fu; Yuting Wang; Jingyue Xue; Yuanfu Yin; Yang Xiao (Environment, Development and Sustainability, 2023)

p-coumaric acid prevents Colletotrichum gloeosporioides by inhibiting membrane targeting and organic acid metabolism - Jingjing Hu; Jingjing Wu; Min Wang; Wenxiao Jiao; Qingmin Chen; Yamin Du; Xin Chen; Xiaoying Yang; Maorun Fu (Postharvest Biology and Technology, 2023)

Emergence and ecological transition of the Mesozoic marine reptiles: Evidence from the Early Triassic Chaohu and the Middle Triassic Xingyi Faunas - Da-yong Jiang; Min Zhou; Ryosuke Motani; Andrea Tintori; Nicholas C. Fraser; Jian-dong Huang; Olivier Rieppel; Cheng Ji; Wan-lu Fu; Zuo-yu Sun; Hao Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Improvement of streamflow simulation by combining physically hydrological model with deep learning methods in data-scarce glacial river basin - Chengde Yang; Min Xu; Shichang Kang; Congsheng Fu; Didi Hu (Journal of Hydrology, 2023)

Profiling of the spatiotemporal distribution, risks, and prioritization of pharmaceuticals and personal care products in coastal waters of the northern Yellow Sea, China - Xiaotong Guo; Min Lv; Lehui Song; Jing Ding; Mingsan Man; Longwen Fu; Shuang Lu; Lijun Hou; Lingxin Chen (Journal of Hazardous Materials, 2023)

Optimizing soil and fertilizer management strategy to facilitate sustainable development of wheat production in a semi-arid area: A 12-year in-situ study on the Loess Plateau - Peng Wu; Gang Zhao; Hua Huang; Qi Wu; Kemoh Bangura; Tie Cai; Min Sun; Jianfu Xue; Jianjun Zhang; Yi Dang; Shuying Wang; Gang Zhou; et al. (Field Crops Research, 2023)

Loading rate effect on the strength of granular material considering particle rotation - Lihong Tong; Li Fu; Changjie Xu; Haibin Ding; Min Xiao (Computers and Geotechnics, 2023)

Novel protection systems for the improvement in soil and water stability of expansive soil slopes - Shao-kun Ma; Ben-fu He; Min Ma; Zhen Huang; Sheng-jia Chen; Huan Yue (Journal of Mountain Science, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Boosting electrochemical CO2 reduction via valence state and oxygen vacancy controllable Bi–Sn/CeO2 nanorod - Jing Xue; Xiangmin Fu; Shuo Geng; Keliang Wang; Ziwei Li; Min Li (Journal of Environmental Management, 2023)

Efficient electrochemical CO2 reduction via CuAg doped CeO2 - Mei Luo; Xiangmin Fu; Shuo Geng; Ziwei Li; Min Li (Fuel, 2023)

Facile synthesis of flower-like sandwich-structured molecularly imprinted polymers for efficient recognition of target protein from egg white - Lirui Zhang; Zhenzhen Feng; Min Fu; Renhe Huang; Wei Chen (Food Chemistry, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Constitutively Synergistic Multiagent Drug Formulations Targeting MERTK, FLT3, and BCL-2 for Treatment of AML - James M. Kelvin; Juhi Jain; Aashis Thapa; Min Qui; Lacey A. Birnbaum; Samuel G. Moore; Henry Zecca; Ryan J. Summers; Jeffrey M. Switchenko; Emma Costanza; Biaggio Uricoli; Xiaodong Wang; et al. (Pharmaceutical Research, 2023)

PPARɑ Ligand Caudatin Improves Cognitive Functions and Mitigates Alzheimer’s Disease Defects By Inducing Autophagy in Mice Models - Senthilkumar Krishnamoorthi; Ashok Iyaswamy; Sravan Gopalkrishnashetty Sreenivasmurthy; Abhimanyu Thakur; Karthick Vasudevan; Gaurav Kumar; Xin-Jie Guan; Kejia Lu; Isha Gaurav; Cheng-Fu Su; Zhou Zhu; Jia Liu; et al. (Journal of Neuroimmune Pharmacology, 2023)

Large‐scale exploration of nitrogen utilization efficiency in Asia region for rice crop: Variation patterns and determinants - Yuming Sun; Limin Gao; Xusheng Meng; Jian Huang; Junjie Guo; Xuan Zhou; Guohai Fu; Yang Xu; Leslie G. Firbank; Min Wang; Ning Ling; Xumeng Feng; et al. (Global Change Biology, 2023)
Improving rice nitrogen utilization efficiency (NUtE) is imperative to maximizing future food productivity while minimizing environmental threats, yet knowledge of its variation and the underlying regulatory factors is still lacking. Here, we integrated a dataset with 21,571 data compiled by available data from peer‐reviewed literature and a large‐scale field survey to address this knowledge gap. The overall results revealed great variations in rice NUtE, which were mainly associated with human activities, climate conditions, and rice variety. Specifically, N supply rate, temperature, and precipitation were the foremost determinants of rice NUtE, and NUtE responses to climatic change differed among rice varieties. Further prediction highlighted the improved rice NUtE with the increasing latitude or longitude. The indica and hybrid rice exhibited higher NUtE in low latitude regions compared to japonica and inbred rice, respectively. Collectively, our results evaluated the primary drivers of rice NUtE variations and predicted the geographic responses of NUtE in different varieties. Linking the global variations in rice NUtE with environmental factors and geographic adaptability provides valuable agronomic and ecological insights into the regulation of rice NUtE.

Inhibitory Mechanism of EGCG on Advanced Glycation End Products Formation During Low-Temperature Vacuum Heating of Russian Sturgeon - Yue-Wen Chen; Min Zhang; Jing-Jing Fu; Jian-Ling Wei; Wen-Qiang Cai; Xiu-Ping Dong (Journal of Aquatic Food Product Technology, 2023)

Integrative analysis uncovers the mechanism underlying the environmental adaptation of an indigenous crucian carp (Carassius auratus gibelio) in Dong's Rice Fish Duck System - Mingkun Luo; Xianbo Zhang; Wenbin Zhu; Qianwen Min; Jinli Hu; Jianjun Fu; Xiulan Shi; Bingjie Jiang; Yating Gong; Lanmei Wang; Ting Liu; Zaijie Dong (Aquaculture, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Combined effect of simulated microgravity and low-dose ionizing radiation on structure and antibiotic resistance of a synthetic community model of bacteria isolated from spacecraft assembly room - Yueying Lu; Yifan Fu; Letian Chen; Jingjing Cui; Min Huang; Yuming Fu; Hong Liu (Life Sciences in Space Research, 2023)

An ultra-light sustainable sponge for elimination of microplastics and nanoplastics - Jianxin Fu; Nuan Liu; Yunxi Peng; Guoqing Wang; Xiaokun Wang; Qiaoning Wang; Min Lv; Lingxin Chen (Journal of Hazardous Materials, 2023)

An improved time–depth dual porosity evolution model and a new parameter for tight sandstone reservoir quality evaluation - Zhen Zhao; Zhen Liu; Faqi He; Wei Zhang; Min Li; Yingjie Hou; Sheng Fu; Maolin Zhu (Journal of Asian Earth Sciences, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Numerical investigation on the pull-out capacity of suction anchors in sand considering torsional and mooring line effects - Min-Hao Zhang; Zhen-Yu Yin; Yong Fu (Computers and Geotechnics, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Long-term hypoxia stress-induced oxidative stress, cell apoptosis, and immune response in the intestine of Pelteobagrus vachelli - Min Wang; Shujia Liao; Xuechun Zang; Zhineng Fu; Shaowu Yin; Tao Wang (Fish Physiology and Biochemistry, 2023)

Integrative Bioinformatics Analysis of mRNA Expression Profiles of Mice to Explore the Key Genes Involved in Crim1 Mutation-Induced Congenital Cataracts - Ziran Zhang; Fanke Meng; Jing Zhou; Zhihan Zhang; Xiaotian Liang; Meijun Meng; Guoguo Yi; Min Fu (Biochemical Genetics, 2023)
Crim1 has been implicated in cataracts in mice and is of great importance in the development of the eye in both humans and mice. Therefore, we aimed to clarify how Crim1 mutations affect lens development and the molecular mechanism of cataracts in mice through comprehensive bioinformatics analysis. The microarray chip was downloaded from the GEO database to obtain the gene expression profile data set. Differentially expressed genes (DEGs) were screened using the limma package. GO and KEGG analyses of DEGs were performed using the DAVID database. Then, we established the protein–protein interaction (PPI) network in Cytoscape. Next, we used MCODE to analyze the data. We obtained 750 DEGs in total, including 407 upregulated DEGs and 343 downregulated DEGs. GO analysis showed that the DEGs were mainly related to biological processes, such as apoptosis, cell translation and the immune system. KEGG analysis showed that the enriched functions and pathways were related to the processing and presentation of ribosomes, lysosomes, and antigens. We identified 18 HUB genes, among which four core genes, C1qa, C1qb, C1qc, and Cd74, were closely related to congenital cataracts induced by Crim1 mutation. This study reveals the molecular pathogenesis of congenital cataracts induced by Crim1, and this information is expected to facilitate clinical genetic testing, molecular diagnosis, prognosis, and individualized chemotherapy for congenital cataracts (CC).

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

DCC-GAN-based channel emulator for underwater wireless optical communication systems - Huanxin Huo; Min Fu; Xuefeng Liu; Bing Zheng (Frontiers in Marine Science, 2023)
The complex and variable oceanic environment challenges channel modeling of Underwater Wireless Optical Communication (UWOC) systems. Most of the classical modeling methods focus mainly on the water environment and ignore the effect of communication equipment on signal transmission, thus making it difficult to model the UWOC channel’s complicated characteristics comprehensively. In this work, a UWOC channel emulator based on Deep Convolutional Conditional Generative Adversarial Networks is established and verified to address the challenge, which can effectively learn the characteristics of channel response and generate emulated signals with randomness like a real UWOC system in a practical application environment. Compared with the approaches based on multi-layer perceptron and convolutional neural network, the experimental results of the proposed method indicate outstanding performances in time domain, frequency domain and universality with different turbidity levels, respectively. This approach provides a new idea for applying deep learning techniques to the field of UWOC channel modeling.

A sustainable process for selective recovery of metals from gallium-bearing waste generated from LED industry - Yifan Yang; Xiaohong Zheng; Tianyi Tao; Fu Rao; Wenfang Gao; Zhaohui Huang; Guoqin Leng; Xin Min; Boli Chen; Zhi Sun (Waste Management, 2023)

Numerical investigation of pull-out capacity and failure mechanism of suction anchors with mooring line in sand - Min-Hao Zhang; Zhen-Yu Yin; Yong Fu (Ocean Engineering, 2023)

Comparation of mesophilic and thermophilic anaerobic co-digestion of food waste and waste activated sludge driven by biochar derived from kitchen waste - Rong Zhang; Min Zhang; Huaqian Mou; Zijing An; Hailu Fu; Xiaomei Su; Chongjun Chen; Jianrong Chen; Hongjun Lin; Faqian Sun (Journal of Cleaner Production, 2023)

Can the mix-charged NF membrane directly obtained by the interfacial polymerization of PIP and TMC? - Qiu-Yu Zhu; Zi-Yun Xu; Jie-Han Fu; Jie Huang; Zhen-Liang Xu; Min Tong; En-Chao Li; Yong-Jian Tang (Desalination, 2023)

Near unity broadband emissivity and ultralow thermal conductivity from yttrium niobate-based ceramics - Guoliang Chen; Benzhi Min; Haoyang Fu; Siqi Ma; Ke Li; Shuqi Wang; Yaming Wang; Jianyun Cao; Jun Qiu; Yong Shuai; Shuzhou Li; Yongchun Zou; et al. (Chemical Engineering Journal, 2023)

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Daphnia magna uptake and excretion of luminescence‐labelled polystyrene nanoparticle as visualized by high sensitivity real-time optical imaging - Yu-Hang Zhang; Rong-Yao Gao; Ze-Jun Wang; Qian-Qian Shao; Ya-Wen Hu; Hua-Bing Jia; Xiao-Jing Liu; Feng-Qin Dong; Li-Min Fu; Jian-Ping Zhang (Chemosphere, 2023)

Unraveling the structure and function of bacterioferritin in Candidatus Kuenenia stuttgartiensis: Iron storage sites maintain cellular iron homeostasis - Jin Wang; Que Wang; Yu-Jiao Tang; Hui-Min Fu; Fang Fang; Jin-Song Guo; Peng Yan; You-Peng Chen (Water Research, 2023)

Colletotrins A-C, three new sesquiterpenes from the endophytic fungus Colletotrichum iris strain S11 - Ning Chen; Shi-Yu Qiu; Song-Mei Lu; Shi-Wei Chen; Ji-Rui Wei; Fu-Wen Yang; Hui-Chun Geng; Min Zhou (Phytochemistry Letters, 2023)

pH drives the spatial variation of antibiotic resistance gene profiles in riparian soils at a watershed scale - Chenxi Fu; Yuan Qin; Qian Xiang; Min Qiao; Yongguan Zhu (Environmental Pollution, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Identification and Pathogen Stimulation Patterns of Neuronal Nitric Oxide Synthase (nNOS) in Black Rockfish (Sebastes schlegelii) - Xu Yan; Ningning Wang; Min Cao; Chao Li; Ning Yang; Ting Xue; Qiang Fu; Lin Song (Journal of Ocean University of China, 2023)

Capacitively coupled effect and capacitive decoupling of multichannel controlled-source audio magnetotellurics observations - Da Lei; Qi-hui Zhen; Ruo Wang; Chang-min Fu; Hao Ren (Applied Geophysics, 2023)

Cell cycle of microalga Isochrysis galbana arrested by neurotoxin β-N-methylamino-l-alanine and corresponding molecular mechanisms - Aifeng Li; Jianwei Liu; Jiangbing Qiu; Guixiang Wang; Xianyao Zheng; Ying Ji; Guowang Yan; Peng Zhao; Xizhen Wu; Wenhui Yan; Lei Zhang; Min Li; et al. (Science of The Total Environment, 2023)

Survival of whole-rock Sm–Nd isotope system from REE redistribution and mineral-scale isotopic resetting amid hydrothermal alteration in REE-rich Fe-Cu deposit - Zhi-Kun Su; Xin-Fu Zhao; Christina Yan Wang; Zhi-Min Zhu; Wen-Lei Song; Carl Spandler (Geochimica et Cosmochimica Acta, 2023)

Tree mycorrhizal type controls over soil water-extractable organic matter quantity and biodegradation in a subtropical forest of southern China - Hui-Min Chen; Fu-Xi Shi; Jia-Wen Xu; Xing-Ping Liu; Rong Mao (Forest Ecology and Management, 2023)

Di-(2-ethylhexyl) phthalate impairs angiogenesis and hematopoiesis via suppressing VEGF signaling in zebrafish - Yang-Xi Hu; Bo-Wen Hu; Ya-Sha Chen; Hong-Min You; Mei-Rong Bai; Lu-Jun Zhang; Zhi-Fu Guo; Chun Liang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Metatranscriptomic insights into the microbial electrosynthesis of acetate by Fe2+/Ni2+ addition - Jie Zhang; He Liu; Yan Zhang; Bo Fu; Chao Zhang; Min-Hua Cui; Ping Wu; Zi-Wei Guan (World Journal of Microbiology and Biotechnology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Microbial species from multiple maternal body sites shape the developing giant panda ( Ailuropoda melanoleuca ) cub gut microbiome - Wei Guo; Ke Ren; Ruihong Ning; Caiwu Li; Yu Zhang; Yunong Gan; Xiaoyan Fu; Cenjun Xiao; Yaoyu Pang; Lei Cheng; Siyuan Zhang; Desheng Li; et al. (Molecular Ecology, 2023)
The gut microbiome of the giant panda ( Ailuropoda melanoleuca ) plays a vital role in nutrient acquisition from its specialized bamboo diet. Giant panda cubs harbour significantly different gut microbiota during their growth and development when feeding on milk before switching to bamboo. The fetal gut is sterile, and following birth, mother‐to‐infant microbial transmission has been implicated as a seeding source for the infant gut microbiota. Details of this transmission in giant pandas remain unclear. In this study, faecal samples were collected from seven panda mother–cub pairs when the cubs were 4–16 months old. Additional samples from the cubs' diet, soil and drinking water, and multiple body sites of the mothers were collected. Bacterial 16S rRNA gene sequencing and shotgun metagenomic sequencing were performed to determine the source and potential transmission routes of the cub gut microbiome. Source tracking analysis showed that maternal vagina, milk and faeces were the primary contributory sources of microbes, shaping the cub gut microbiome. Bacterial species from maternal faeces persisted the longest in the cub gut. Bacterial species in the diet contributed to the microbial community. Metagenomics analysis indicated that the predicted metabolic pathways of the gut microbiome also varied at different growth stages. Gut colonization with bacteria from various body sites of the mothers provides a foundational microbial community that is beneficial in fulfilling the evolving dietary needs of the cubs. This study suggests that mother‐to‐cub transmission is indispensable in shaping the gut microbiome of the developing panda cub.

Canopy height, rather than neighborhood effects, shapes leaf herbivory in a tropical rainforest - Shuang Zhang; Guo‐Rui Xu; Yu‐Xin Zhang; Wen‐Fu Zhang; Min Cao (Ecology, 2023)
Factors shaping the interspecific variations in herbivory have puzzled ecologists for decades and several hypotheses have been proposed to explain interspecific variation in leaf herbivory. In a tropical rainforest in Yunnan Province, China, we collected 6732 leaves from 129 species with canopy heights ranging from 1.6 to 65.0 m above the ground. We tested the role of canopy height, the diversity, composition and structural heterogeneity of neighbors and leaf traits in shaping the interspecific variations in herbivory. Results show that leaf herbivory decreased with canopy height and specific leaf area (SLA) and increased with leaf size. However, neighboring species' diversity, composition, and structural heterogeneity showed no association with herbivory. Therefore, neither the visual apparency effect nor the associational resistance effect was detected in this hyperdiverse tropical rainforest. These findings highlight the importance of vertical structure in shaping herbivory patterns in natural communities.

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Source identification of PCBs in Antarctic air by compound-specific isotope analysis of chlorine (CSIA-Cl) using HRGC/HRMS - Pu Wang; Wenying Meng; Weiwei Zhang; Min Fu; Yingming Li; Ruiqiang Yang; Qinghua Zhang; Guibin Jiang (Journal of Hazardous Materials, 2023)

Regulating the reaction pathway of nZVI to improve the decontamination performance through magnetic spatial confinement effect - Hai-Yuan Chi; Xiao-Xia Zhou; Min-Rong Wu; Wan-yu Shan; Jing-fu Liu; Jin-quan Wan; Bing Yan; Rui Liu (Journal of Hazardous Materials, 2023)

Urea-mediated warm ponds: Prebiotic formation of carbamoyl amino acids on the primordial Earth - Dingwei Gan; Yeting Guo; Xiangmin Lei; Min Zhang; Songsen Fu; Jianxi Ying; Yufen Zhao (Earth and Planetary Science Letters, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Reducing the water residence time is inadequate to limit the algal proliferation in eutrophic lakes - Yingying Huang; Min Fu; Guiqin Chen; Jieyun Zhang; Ping Xu; Liping Pan; Xiaohan Zhang; Xuechu Chen (Journal of Environmental Management, 2023)

Boosting the photocatalytic hydrogen evolution and NO removal via synergistic effects of in-situ Pt NPs formation and titanium integration in Zr-Porphyrin MOFs - Ruolan Li; Zongqian Wu; Ya Chen; Xingyan Liu; Weiwei Guo; Yumin Huang; Min Fu; Youzhou He (Fuel, 2023)

Denitrification efficiency, microbial communities and metabolic mechanisms of corn cob hydrolysate as denitrifying carbon source - Yingping Long; Yongwen Ma; Jinquan Wan; Yan Wang; Min Tang; Hao Fu; Jianye Cao (Environmental Research, 2023)

CRISPR/Cas9-mediated knockin of IRES-tdTomato at Ins2 locus reveals no RFP-positive cells in mouse islets - Xueling Zhou; Qi Fu; Tao Yang; Min Sun (Functional & Integrative Genomics, 2023)
Using the CRISPR/Cas9 genomic editing technology, we constructed a transgenic mouse model to express specific fluorescent protein in pancreatic β cells, which harbor tdTomato exogenous gene downstream of the Ins2 promoter in C57BL/6 J mice. The Ins2-specific single-guide RNA-targeted exon2 was designed for the CRISPR/Cas9 system and Donor vector was constructed at the same time. Then Cas9, sgRNA, and Donor vector were microinjected in vitro into the mouse zygotes that were implanted into pseudo-pregnant mice. We obtained homozygotes through mating heterozygotes, and verified the knockin effect through genotype identification, in vivo imaging, and frozen section. Six F0 mice and stable inherited Ins2-IRES-tdTomato F1 were obtained. Genome sequencing results showed that the knockin group had no change in the Ins2 exon compared with the control group, while only the base sequence of tdTomato was added and no base mutation occurred. However, in vivo imaging and frozen section did not observe the expression of red fluorescent protein (RFP), and the protein expression of knockin gene tdTomato was negative. As a result, the expressions of tdTomato protein and fluorescence intensity were low and the detection threshold was not reached. In the CRISP/Cas9 technique, the exogenous fragment of IRES connection would affect the transcription level of the preceding gene, which in turn would lead to low-level expression of the downstream gene and affect the effect of gene insertion.

Chlorpyrifos induces neuronal cell death via both oxidative stress and Akt activation downstream-regulated CHOP-triggered apoptotic pathways - Jhe-Wei Lin; Shih-Chang Fu; Jui-Ming Liu; Shing-Hwa Liu; Kuan-I Lee; Kai-Min Fang; Ren-Jun Hsu; Chun-Fa Huang; Kun-Min Liu; Kai-Chih Chang; Chin-Chuan Su; Ya-Wen Chen (Toxicology in Vitro, 2023)

Methionine sulfoxide reductase B5 plays vital roles in tomato fruit defense response against Botrytis cinerea induced by methyl jasmonate - Xiaodong Fu; Xiaoan Li; Maratab Ali; Xiuming Zhao; Dedong Min; Jiong Liu; Fujun Li; Xinhua Zhang (Postharvest Biology and Technology, 2023)

Two new terpenoids and other constituents from Salvia cavaleriei and their antibacterial activities - Yu-Min Zhao; Ke Li; Han-Fei Liu; Jin-Yu Li; Jian Fu; Hua-Yong Lou; Wei-Dong Pan (Phytochemistry Letters, 2023)

A new phragmalin-type limonoid from the roots of Trichilia sinensis - Shou-Bai Liu; Jin-Ling Yang; Hui-Qin Chen; Cheng-min Yang; Hao Wang; Cai-Hong Cai; Jing-Zhe Yuan; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2023)

Impact of high pressure homogenization on the properties of potato flour film-forming dispersions and the resulting films - Shao-xiang Guo; Zong-qiang Fu; Xu Yao; Xue-ying Wang; Min Wu (Journal of Food Engineering, 2023)

Parental and transgenerational impairments of thyroid endocrine system in zebrafish by 2,4,6-tribromophenol - Yuxi Zhou; Juanjuan Fu; Min Wang; Yongyong Guo; Lihua Yang; Jian Han; Bingsheng Zhou (Journal of Environmental Sciences, 2023)

Improving ACE inhibitory activity of hazelnut peptide modified by plastein: Physicochemical properties and action mechanism - Wentian Song; Junxi Fu; Qi Zeng; Hongyan Lu; Ji Wang; Li Fang; Xiaoting Liu; Weihong Min; Chunlei Liu (Food Chemistry, 2023)

Molecular characterization and expression analysis of immunoglobulins (IgM and IgT) heavy chains in black rockfish (Sebastes schlegelii) that response to bacterial challenge - Min Cao; Qi Li; Xiantong Liu; Qiang Fu; Chao Li (Fish & Shellfish Immunology, 2023)

Analytical solution for coupled water–gas transport in unsaturated landfill cover system with different root architectures - Ming Min; He-Fu Pu; Song Feng; Jin-Wei Qiu; Xiao-Jun Wen (Computers and Geotechnics, 2023)

Activating the photocatalytic activity of insulator barium silicate: A liquid-phase alkalized tetracycline photosensitizer and its self-destruction - Xueli Hu; Peng Lu; Min Fu; Yongheng Zhang; Xinyu Cao; Jiabo Chen; Shutao Lin; Juanjuan Yao; Zhi Zhang (Chemical Engineering Journal, 2023)

Insights into reactive species generation and organics selective degradation in Fe-based heterogeneous Fenton-like systems: A critical review - Ling Li; Zhuo Yin; Min Cheng; Lei Qin; Shiyu Liu; Huan Yi; Mingming Zhang; Yukui Fu; Xiaofeng Yang; Xuerong Zhou; Guangming Zeng; Cui Lai (Chemical Engineering Journal, 2023)

A gas permeable membrane electrode for selective and durable H2S production from SO2 - Hui Liu; Xudong Liu; Zhujiang Wang; Huimin Yi; Yingxue Fu; Lin Wu; Fenghua Shen; Pingshan Wang; Min Liu; Zhang Lin; Kaisong Xiang; Liyuan Chai (Chemical Engineering Journal, 2023)

Low 15d-PGJ2 status is associated with oxidative stress in chronic obstructive pulmonary disease patients - Shi-Xue Ma; Guo-Fang Xie; Pu Fang; Min-Min Tang; You-Peng Deng; Yu-Jin Lu; Wei Cao; Lin Fu (Inflammation Research, 2023)

Histone Deacetylation Modifier Induced One New Resorcylic Acid Lactone 7′(Z)-zeaenol from the Zoanthid-Derived Fungus Cochliobolus lunatus - Zhenkun Zhang; Jiaxiang Wang; Fei Cao; Xiaojian Zhou; Jingshuai Wu; Xiumei Fu; Min Chen; Changyun Wang (Journal of Ocean University of China, 2023)

Unique bacterial communities and lifestyles in deep ocean blue holes: Insights from the Yongle Blue Hole (South China Sea) - Shun Zhou; Jiwen Liu; Peng Yao; Liang Fu; Zuosheng Yang; Yulin Zhang; Rui Du; Chao Jia; Lin Chen; Jinchang Liang; Xiaolei Wang; Xiaochong Shi; et al. (Frontiers in Marine Science, 2023)
Deep ocean blue holes possess steep physicochemical gradients, especially low dissolved oxygen concentration, which shape the extraordinary microbial communities. However, the environmental responses of microorganisms with different lifestyles and knowledge of culturable microorganisms in the blue holes are still unknown. Here, we investigated the bacterial community structure with different lifestyles of the world’s deepest blue hole - the Yongle Blue Hole (YBH) in the South China Sea using both culture-dependent and -independent methods. YBH can be divided by oxygen content into an oxic zone, a suboxic zone and two anoxic zones. The abundance of bacteria, archaea, genes dsrB and soxB were all higher in the free-living (FL) lifestyle than in the particle-associated (PA) lifestyle, yet the diversity and richness of PA bacteria were higher than that of FL bacteria. More Gammaproteobacteria and less Alphaproteobacteria , Chloroflexi and Nitrospinae were observed within the FL fraction than within the PA fraction. The relative abundance of sulfur-oxidizing bacteria (SOB) was dominant between 100-140 m (anoxic zone I) in YBH, with a maximum of 90.0% (140 m FL fraction). The SOB in YBH were mainly colorless sulfur bacteria and purple non-sulfur bacteria, of which Thiomicrorhabdus and Sulfurimonas were the main representatives. In addition, a total of 294 bacterial strains were isolated on a variety of media and culture conditions, and 22.2% (18/81) of anaerobic strains were identified as potential novel species. Our study reveals a distinction between FL and PA bacteria in YBH. It contributes to further understanding of the bacterial community in deep ocean blue holes, and provides bacterial resources for subsequent studies on their adaptation to extreme marine environments.

Stochastic analysis on the lateral buckling of a HPHT pipeline considering the spatial variability of seabed - Yu-Min Shi; Ning Wang; Fu-Ping Gao (Ocean Engineering, 2023)

Carboniferous mafic-ultramafic intrusions in the Eastern Pontides (Pulur Complex): Implications for the source of coeval voluminous granites - Gültekin Topuz; Rainer Altherr; Osman Candan; Jia-Min Wang; Aral I. Okay; Fu-Yuan Wu; Ali Ergen; Thomas Zack; Wolfgang Siebel; Cosmas K. Shangh; Winfried H. Schwarz; Hans-Peter Meyer; et al. (Lithos, 2023)

Strengthen the purification of eutrophic water and improve the characteristics of sediment by functional ecological floating bed suspended calcium peroxide and sponge iron jointly - Zheng Zhu; Yi Wang; Xue-Yi Han; Wen-Huai Wang; Hao-Min Li; Zi-Qi Yue; Wei Chen; Fu-Rong Xue (Journal of Environmental Management, 2023)

A carbothermic hybrid synthesized using waste halogenated plastic in sub/supercritical CO2 and its application for lithium recovery - Cong-Cong Zhang; Fu-Shen Zhang; Neng-min Zhu; Xiao-Hui Yue (Environmental Research, 2023)

A meta-analysis of environmental responses to freshwater ecosystem restoration in China (1987–2018) - Hong Fu; Jun Xu; Huan Zhang; Jorge García Molinos; Min Zhang; Megan Klaar; Lee E. Brown (Environmental Pollution, 2023)

Can phosphobacteria simultaneously achieve phosphorus recovery and Pb2+ removal from wastewater by biomineralization? - Pei Zhang; Yi-Min Ding; Tian-Lei Zhao; Yu-Han Wang; Qi-Zhi Yao; Sheng-Quan Fu; Gen-Tao Zhou (Chemical Engineering Journal, 2023)

Scalable anti-infection polyurethane catheters with long-acting and autoclavable properties - Zongpeng Xiu; Meiping Yang; Ruonan Wu; Chengyue Lei; Hui-Min Ren; Bingran Yu; Shuai Gao; Shun Duan; Dimeng Wu; Fu-Jian Xu (Chemical Engineering Journal, 2023)

Expression profile of long non-coding RNAs in the intestine of black rockfish Sebastes schlegelii in response to Edwardsiella tarda infection - Xu Yan; Min Cao; Qiang Fu; Ning Yang; Ningning Wang; Lin Song; Chao Li (Journal of Oceanology and Limnology, 2023)

Effects of the neurotoxin β-N-methylamino-L-alanine (BMAA) on the early embryonic development of marine shellfish and fish - Yilei Fu; Aifeng Li; Jiangbing Qiu; Wenhui Yan; Chen Yan; Lei Zhang; Min Li (Frontiers in Marine Science, 2022)
The neurotoxin β - N -methylamino- L -alanine (BMAA) produced by cyanobacteria and diatoms can accumulate in diverse aquatic organisms through the food web. In the present study, embryos of mussel Mytilus galloprovincialis (Lamarck, 1819), oyster Magallana gigas (Thunberg, 1793), and marine medaka Oryzias melastigma (McClelland, 1839) were exposed to BMAA dissolved in seawater and monitored for early developmental effects. Results demonstrated that the embryonic development of mussels and oysters were significantly inhibited when BMAA concentrations were above 100 μg BMAA·HCl/L (0.65 µM) and 800 μg BMAA·HCl/L (5.18 µM), respectively. The shell growth of mussel embryos was also markedly inhibited by BMAA ≥ 100 μg BMAA·HCl/L (0.65 µM). Based on the dose-response curves related to the modified malformation rate of embryos, the median effective concentration (EC 50 ) values of mussel (48 h) and oyster (24 h) embryos were 196 μg BMAA·HCl/L (1.27 µM) and 1660 μg BMAA·HCl/L (10.7 μM), respectively. A sustained and dose-dependent decrease in heart rate was apparent in marine medaka embryos at 9-days post fertilization following BMAA exposure. However, no obvious effect on ATP concentration was noted in these marine medaka embryos. The current study contributes to our understanding of the sublethal effects of BMAA on the early embryonic development of marine bivalves and medaka. Further research examining the long-term effects of BMAA on the early development of marine organisms is necessary to determine seawater quality criteria for protection.

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Inhibition of Microglial NLRP3 with MCC950 Attenuates Microglial Morphology and NLRP3/Caspase-1/IL-1β Signaling In Stress-induced Mice - Qing Liu; Man-Man Zhang; Min-Xia Guo; Qiu-Ping Zhang; Na-Zhi Li; Jie Cheng; Shi-Le Wang; Guang-Hui Xu; Cheng-Fu Li; Ji-Xiao Zhu; Li-Tao Yi (Journal of Neuroimmune Pharmacology, 2022)

Tobacco smoke exposure and mitochondrial DNA copy number on neurobehavioural performance: A community study - Huimin Wang; Mengmeng Fu; Yifei Ma; Chenjuan Liu; Min Wu; Jisheng Nie (Environmental Science and Pollution Research, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

mTORC1/C2 regulate spermatogenesis in Eriocheir sinensis via alterations in the actin filament network and cell junctions - Zhen-Fang Li; Shuang-Li Hao; Lan-Min Wang; Hong-Yu Qi; Jia-Ming Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2022)

Transcriptome-Based Analysis of the Response Mechanism of Leopard Coralgrouper Liver at Different Flow Velocities - Min Yang; Jin Gao; Hongji Ke; Yongbo Wang; Jinye Liu; Xin Wen; Shuyuan Fu; Jiang Wang (Fishes, 2022)
The velocity of water can cause differences in the growth of inhabitant fish, thereby functioning as an important aquatic environmental factor. In order to explore the response mechanism of Leopard Coralgrouper (Plectropomus leopardus) under different flow velocities, P. leopardus fish of the same sizes were fed in water characterized by three different flow rates (5 cm/s, 10 cm/s, and 20 cm/s) for 150 d, after which the differences in growth and the levels of liver oxidative stress kinase were analyzed. Additionally, potential underlying regulatory pathways were explored using comparative transcriptomic approaches. The results showed that in the feeding environment involving a flow rate of 10 cm/s, the weight increase of P. leopardus and its liver contents of glutathione peroxidase (GPX), alanine aminotransferase (ALT), and superoxide dismutase (T-SOD) were significantly higher than for the other two groups. After matching the comparative transcriptomic results between group pairs (5 cm/s and 10 cm/s, 5 cm/s and 20 cm/s, and 10 cm/s and 20 cm/s), a total of 225 common differential gene expressions were screened. The KEGG pathway enrichment analysis showed that these genes were mainly involved in protein processing in the endoplasmic reticulum, the TGF-β signaling pathway, fatty acid metabolism, fatty acid synthesis, and other pathways. These results not only provide a theoretical basis for the selection of flow velocity in the culture environment of P. leopardus, but also reveal its potential means of adaption to different flow velocities.

Improving pre-harvest sprouting resistance in rice by editing OsABA8ox using CRISPR/Cas9 - Kai Fu; Weihan Song; Cheng Chen; Changling Mou; Yunshuai Huang; Fulin Zhang; Qixian Hao; Ping Wang; Tengfei Ma; Yaping Chen; Ziyan Zhu; Min Zhang; et al. (Plant Cell Reports, 2022)

Cavitation–Silt Erosion Behavior and Failure Mechanism of an HVOF-Sprayed WC-Cr3C2-Ni Coating for Offshore Hydraulic Machinery - Jinran Lin; Sheng Hong; Yuan Zheng; Wei Sun; Zhengwei Zhang; Min Kang; Xiuqing Fu (Journal of Marine Science and Engineering, 2022)
WC-Cr3C2-Ni coatings are a vital class of hard ceramic/cermet coatings with potential applications as wear-resistant materials. However, their erosion wear behavior in 3.5 wt.% sodium chloride medium (SCM) remains largely unexplored. The present study investigated the cavitation–silt erosion (CSE) behavior in 3.5 wt.% SCM of WC-Cr3C2-Ni coatings sprayed with high-velocity oxygen–fuel (HVOF) under different flow velocities (FVs) and sand concentrations (SCs). Comparing the WC-Cr3C2-Ni coating with the 1Cr18Ni9Ti stainless steel, the first possessed superior CSE resistance in 3.5 wt.% SCM in a full range of FV and SC. Meanwhile, the coating appeared more influenced by FV and less influenced by SC, which was indicated by the fact that the amplification of VLR value (377.1%) when the FV ranged from 23.4 to 41.9 m·s−1 was larger than that (129.8%) when the SC increased from 10 kg·m−3 to 35 kg·m−3. With increasing FV and SC, the CSE process of the WC-Cr3C2-Ni coating in 3.5 wt.% SCM mainly included the discontinuous corrosion product films, erosion pits, fracturing of hard-phase grains, and micro-cutting of soft binder matrix, as well as crater formation and coating spalling.

Horizontal and vertical heterogeneity of sediment microbial community in Site F cold seep, the South China Sea - Xinyi Zhai; Xiaochong Shi; Haojin Cheng; Peng Yao; Bin Zhao; Lin Chen; Jiwen Liu; Lei Cao; Minxiao Wang; Lulu Fu; Xiao-Hua Zhang; Min Yu (Frontiers in Marine Science, 2022)
Site F is the most vigorous cold seep known on the continental slope of the northern South China Sea. Up to now, the microbial community structures in sediments of Site F based on the high-throughput sequencing of the 16S rRNA genes have been studied extensively. However, few studies investigated the microbial community structures at fine vertical scales of Site F and control stations outside Site F. In this study, a comprehensive investigation of microbial communities in sediments of Site F along the depths varying from 0 to 24 cm below sea floor (cmbsf) of four sampling sites—SRS (Southern Reduced Sediment), NRS (Northern Reduced Sediment), Control 1 (close to Site F), and Control 2 (far from Site F)—was carried out. The high relative abundances of anaerobic methanotrophic archaea (ANME), Desulfobacterota [sulfate-reducing bacteria (SRB)], and Campylobacteria [sulfur-oxidizing bacteria (SOB)] in SRS and NRS indicated that these two sites were newborn cold seep sites compared with non-seep sites, Control 1, and Control 2. A positive correlation between ANME-1b, ANME-2, and SEEP-SRB and an enrichment of Sulfurovum and Methlomonadaceae were found in the surface sediments of both SRS and NRS, indicating that the processes of anaerobic oxidation of methane (AOM), sulfur oxidation, and sulfate reduction might occur in seep sites. SRS was enriched with ANME-1b and SEEP-SRB2 with a proposed sulfate-methane transition zone (SMTZ) approximately located at 8 cmbsf. The high abundance of ANME in SRS may due to the high concentration of methane. NRS was enriched with ANME-2, Desulfatiglans , Sulfurovum , and Methanosarcinaceae with a proposed SMTZ at about 10 cmbsf. According to the analyses of microbial community structure and environmental factors, NRS could be described as a notable cold seep reduced sediment site with low sulfate and high H 2 S that nourished abundant SEEP-SRB1, ANME-2, Methanosarcinales , and Sulfurovum , which showed similar distribution pattern. Our study expands the current knowledge on the differences of microbial communities in cold seep sites and non-seep sites and sheds light on the horizontal and vertical heterogeneity of sediment microbial community in Site F.

Gaming strategies within a green supply chain considering consumers’ concern about the greenness and conformance quality of products - Yongxi Yi; Min Yang; Chunyan Fu; Yuqiong Li (Environmental Science and Pollution Research, 2022)

Potential millennial‐scale avian declines by humans in southern China - Feng Dong; Qiang Zhang; Yi‐Lin Chen; Fu‐Min Lei; Shou‐Hsien Li; Fei Wu; Xiao‐Jun Yang (Global Change Biology, 2022)
Mounting observational records demonstrate human‐caused faunal decline in recent decades, while accumulating archaeological evidence suggests an early biodiversity impact of human activities during the Holocene. A fundamental question arises concerning whether modern wildlife population declines began during early human disturbance. Here, we performed a population genomic analysis of six common forest birds in East Asia to address this question. For five of them, demographic history inference based on 25–33 genomes of each species revealed dramatic population declines by 4‐ to 48‐fold over millennia (e.g. 2000–5000 thousand years ago). Nevertheless, summary statistics detected nonsignificant correlations between these population size trajectories and Holocene temperature variations, and ecological niche models explicitly predicted extensive range persistence during the Holocene, implying limited demographic consequence of Holocene climate change. Further analyses suggest high negative correlations between the reconstructed population declines and human disturbance intensities and indicate a potential driver of human activities. These findings provide a deep‐time and large‐scale insight into the recently recognized avifaunal decline and support an early origin hypothesis of human effects on biodiversity. Overall, our study sheds light on the current biodiversity crisis in the context of long‐term human–environment interactions and offers a multi‐evidential framework for quantitatively assessing the ecological consequences of human disturbance.

A novel R3H protein, OsDIP1, confers ABA-mediated adaptation to drought and salinity stress in rice - Liping Huang; WenXuan Fu; E. Ji; Mohsin Tanveer; Sergey Shabala; Min Yu; Mingyi Jiang (Plant and Soil, 2022)

Influence of asymmetric blockage of the drainage system of a deep-buried tunnel on water gushing - He-lin Fu; Peng-tao An; Yi-min Wu; Jie Li; Long Chen (Journal of Mountain Science, 2022)

Optimizing Hard Clam Production in Taiwan by Accounting for Nonlinear Effects of Stocking Density and Feed Costs on Farm Output of Clams - Jie-Min Lee; Sheng-Hung Chen; Yi-Chung Lee; Jung-Fu Huang; Christian Schafferer; Chun-Yuan Yeh; Ti-Wan Kung (Fishes, 2022)
Despite mass mortality, hard clams remain among the main cultured shellfish in Taiwan. Using cross-sectional data, this study applies threshold regression modeling with stocking density and feed costs as the threshold variables to explore the nonlinear relationship between input and output factors. The findings show that the production output levels may be increased by different combinations of factor inputs and variations in input factors. More specifically, the higher output levels may be achieved by increasing labor input while reducing capital input factors in farming households with a higher stocking density (HSD > 1,087,870 inds/ha) or higher feed cost (HFC > 13,889 NTD/ha). Farming households with a lower stocking density (LSD ≤ 1,087,870 inds/ha) may enhance production output levels by increasing feed input while reducing capital inputs. Moreover, the maximum output level of HSD and HFC farming households was estimated to reach 9255 kg/ha and 9807 kg/ha, respectively. Results of the production output simulation suggest that the feeding cost per hectare in LSD households should not exceed 25,119 NTD to avoid overfeeding, which may cause culture deterioration and lower survival rates. As such, farmers are advised to adjust their feed costs according to the stocking density to maximize production output.

Decreasing spring persistent rainfall over the Yangtze‐Huai River Valley of China during 1960–2019 and its possible causes - Weian Tang; Yunfei Fu; Xujia Wang; Yanyu Lu; Min Xu; Wusan Xie; Awei Song (International Journal of Climatology, 2022)
Based on the observations, reanalysis and sea surface temperature (SST) data sets, the spatio‐temporal distribution characteristics of the decreasing spring persistent rainfall (SPR) over the Yangtze‐Huai River Valley (YHRV) of China during 1960–2019 are revealed, and corresponding causes of the first leading two modes from the empirical orthogonal function (EOF) analysis on the SPR are also explored. Results indicate that the SPR decreases northwards and exhibits spatially consistent declining trends over the YHRV, with the maximum along the middle and lower reaches of the Yangtze River, attributing to the decrease in total spring rainfall over the YHRV. The first EOF mode of the SPR (EOF‐1) over the YHRV shows a spatial mono‐sign pattern, while the South Indian Ocean dipole plays an important role in modulating its variability. Among them, the warming SST in the southwestern Indian Ocean is more important for the spatially consistent decrease of the SPR over the YHRV. The second EOF mode of the SPR (EOF‐2) over the YHRV exhibits a spatial distribution of north–south dipole pattern, while the North Atlantic Oscillation (NAO) contributes to the variation of EOF‐2. The inter‐decadal decreases of SPR at different rates are attributed to the transition between the first leading two EOF modes of SPR associated with the inter‐decadal changes of the external forcing factors and atmospheric circulations. From mid‐1970s to 1990s when the southern Indian Ocean SST increases rapidly, a mono‐sign pattern of the SPR is observed with a rapid decrease SPR over the whole YHRV. Since the mid‐1980s, when the NAO gradually reaches a predominantly positive phase, the SPR exhibits an increasing trend over the south of the YHRV, while a decreasing trend over the north part, causing the overall slowing of the precipitation decreasing trend.

Correction to: Publication characteristics, topic trends and knowledge domains of karst ecological restoration: a bibliometric and knowledge mapping analysis from 1991 to 2021 - Kehui Liu; Xiaojin Guan; Guangluan Li; Min Duan; Yi Li; Yanyan Hong; Meimei Lin; Rongxin Fu; Fangming Yu (Plant and Soil, 2022)

Publication characteristics, topic trends and knowledge domains of karst ecological restoration: a bibliometric and knowledge mapping analysis from 1991 to 2021 - Kehui Liu; Xiaojin Guan; Guangluan Li; Min Duan; Yi Li; Yanyan Hong; Meimei Lin; Rongxin Fu; Fangming Yu (Plant and Soil, 2022)

Regulation of Sugar Metabolism by Methyl Jasmonate to Improve the Postharvest Quality of Tomato Fruit - Jiaozhuo Li; Dedong Min; Zilong Li; Xiaodong Fu; Xiuming Zhao; Jihan Wang; Xinhua Zhang; Fujun Li; Xiaoan Li; Yanyin Guo (Journal of Plant Growth Regulation, 2022)

Community Competition Is the Microorganism Feedback to Sedimentary Carbon Degradation Process in Aquaculture Tidal Flats - Min Zhou; Fu-Tao Fang; Cong Zeng; Li-Hong Zhang; Cheng-Xu Zhou; Zhuo-Yi Zhu (Frontiers in Marine Science, 2022)
How the microbial community response to carbon degradation is unclear, while it plays an essential role in predicting microbial community shift and determining carbon cycling. Surface sediments in two contrasting aquacultural tidal flat sites in Fujian Province, China, were collected in October, 2020. In addition to 16s rRNA gene high-throughput sequencing for determining bacteria and archaea biodiversity, an amino acids-based molecular degradation index DI was used to quantify the carbon degradation status. The results revealed that the microorganism response to DI at the family level was community competition. Specifically, the winning microbes that grew under carbon degradation (i.e., operational taxa unit numbers negatively related with the degradation index) accounted for only 18% of the total family number, but accounted for 54% of the total operational taxa unit numbers. Network analysis confirmed the oppressive relation between winners and the rest (losers + centrists), and further suggested the losers survival strategy as uniting the centrists. These findings shed new light on microorganism feedback to carbon degradation, and provide a scientific basis for the explanation of microbial community shift under progressive carbon degradation.

Rapid onset hazards, fault-controlled landslides and multi-method emergency decision-making - Fu-yun Guo; Xing-min Meng; Tian-jun Qi; Tom Dijkstra; Jarsve Kristine Thorkildsen; Dong-xia Yue; Guan Chen; Yi Zhang; Xiao-dong Dou; Peng-qing Shi (Journal of Mountain Science, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

Hemecitones A and B: two phenanthrenes with cytotoxicity from Hemerocallis fulva (L.) L - Rao Fu; Xia Wang; Biao Zhao; Min Yang; Jing Gou; Chang-Ying Tian (Natural Product Research, 2022)

LncRNA PVT1 facilitates DLBCL development via miR-34b-5p/Foxp1 pathway - Shi Tao; Yu Chen; Min Hu; Lu Xu; Cai-Bo Fu; Xin-Bao Hao (Molecular and Cellular Biochemistry, 2022)

Effect of paeonol against bacterial growth, biofilm formation and dispersal of Staphylococcus aureus and Listeria monocytogenes in vitro - Qiao Zeng; Yuting Fu; Min Yang; Ting Wang; Ying Wang; Shenghua Lv; Weidong Qian (Biofouling, 2022)

Synthesis, antifungal activity and 3D-QSAR study of novel acyl thiourea compounds containing gem-dimethylcyclopropane ring - Mei Huang; Min Huang; Xiu Wang; Wen-Gui Duan; Gui-Shan Lin; Fu-Hou Lei (Molecular Diversity, 2022)

Comparative Transcriptome Analysis of Spleen Reveals Potential Regulation of Genes and Immune Pathways Following Administration of Aeromonas salmonicida subsp. masoucida Vaccine in Atlantic Salmon (Salmo salar) - Qiang Fu; Yuqing Li; Hao Zhang; Min Cao; Lu Zhang; Chengbin Gao; Xin Cai; Defeng Chen; Ziying Yang; Jie Li; Ning Yang; Chao Li (Marine Biotechnology, 2022)

Bimetallic atomic site catalysts for CO2 reduction reactions: a review - Junwei Fu; Kang Liu; Hongmei Li; Junhua Hu; Min Liu (Environmental Chemistry Letters, 2022)

Complete genome sequencing and evolutionary analysis of hepatitis C virus subtype 6a, including strains from Guangdong Province, China - Ru Xu; Hao Wang; Jieting Huang; Min Wang; Qiao Liao; Zhengang Shan; Huishan Zhong; Xia Rong; Yongshui Fu (Archives of Virology, 2022)

Investment Evaluation and Partnership Selection Model in the Offshore Wind Power Underwater Foundations Industry - Min-Yuan Cheng; Yung-Fu Wu (Journal of Marine Science and Engineering, 2021)
With a plan to achieve a target of 5.7 GW offshore wind power capacity in 2025, Taiwan anticipates building a 36-billion USD industry, which makes Taiwan a center of attention in the global marketplace of civil engineering construction. Aimed at Taiwan’s underwater foundations industries, this study is the first to develop an investment evaluation model (IEM) by applying FPR to obtain risk factor weights and calculate the overall investment risk value with a numerical scoring method. In a context where no precedent exists for reference, this study provides auxiliary and supportive tools to help builders to make the decision, based on objective indicators, whether to undertake an investment. To date, no research has been conducted to introduce a reasonable mathematical model that discusses the issue of partner selection in the field of offshore wind power. This study is the first paper to construct a SWARA-FTOPSIS partner selection model, which enables underwater foundations builders to take specific Taiwanese characteristics into account in their selection of the best partners to meet transportation, construction, and installation requirements. Finally, the study uses the case of the Taipower Offshore Wind Power Project (2nd phase) to verify the feasibility of this model.

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

A single nucleotide polymorphism in an R2R3 MYB transcription factor gene triggers the male sterility in soybean ms6 (Ames1) - Junping Yu; Guolong Zhao; Wei Li; Ying Zhang; Peng Wang; Aigen Fu; Limei Zhao; Chunbao Zhang; Min Xu (Theoretical and Applied Genetics, 2021)
Key message Identification and functional analysis of the male sterile gene MS6 in Glycine max . Abstract Soybean ( Glycine max (L.) Merr . ) is an important crop providing vegetable oil and protein. The male sterility-based hybrid breeding is a promising method for improving soybean yield to meet the globally growing demand. In this research, we identified a soybean genic male sterile locus, MS6 , by combining the bulked segregant analysis sequencing method and the map-based cloning technology. MS6 , highly expressed in anther, encodes an R2R3 MYB transcription factor (GmTDF1-1) that is homologous to Tapetal Development and Function 1, a key factor for anther development in Arabidopsis and rice. In male sterile ms6 (Ames1), the mutant allele contains a missense mutation, leading to the 76th leucine substituted by histidine in the DNA binding domain of GmTDF1-1. The expression of soybean MS6 under the control of the AtTDF1 promoter could rescue the male sterility of attdf1 but ms6 could not. Additionally, ms6 overexpression in wild-type Arabidopsis did not affect anther development. These results evidence that GmTDF1-1 is a functional TDF1 homolog and L76H disrupts its function. Notably, GmTDF1-1 shows 92% sequence identity with another soybean protein termed as GmTDF1-2, whose active expression also restored the fertility of attdf1 . However, GmTDF1-2 is constitutively expressed at a very low level in soybean, and therefore, not able to compensate for the MS6 deficiency. Analysis of the TDF1-involved anther development regulatory pathway showed that expressions of the genes downstream of TDF1 are significantly suppressed in ms6 , unveiling that GmTDF1-1 is a core transcription factor regulating soybean anther development.

Responses of leaf litter decomposability to nitrogen and phosphorus additions are associated with cell wall carbohydrate composition in a subtropical plantation - Xiang-Min Fang; Xiu-Lan Zhang; Ying-Ying Zong; Wen-Qing Li; Jian-Jun Li; Li-Ping Guo; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

Landslide mapping and analysis along the China-Pakistan Karakoram Highway based on SBAS-InSAR detection in 2017 - Xiao-jun Su; Yi Zhang; Xing-min Meng; Dong-xia Yue; Jin-hui Ma; Fu-yun Guo; Zi-qiang Zhou; Mohib Ur Rehman; Zainab Khalid; Guan Chen; Run-qiang Zeng; Fu-meng Zhao (Journal of Mountain Science, 2021)

Transcriptomics and targeted metabolomics reveal the regulatory network of Lilium davidii var. unicolor during bulb dormancy release - Xinyue Fan; Yue Yang; Min Li; Linlan Fu; Yuqing Zang; Chunxia Wang; Tianyou Hao; Hongmei Sun (Planta, 2021)

A Survey on How Ocular Surface Demodex Infestation Interactively Associates with Diabetes Mellitus and Dry Eye Disease - Chang Huang; Shuze Chen; Sheng Fu; Yingli Li; Zhenhao Li; Siqi Li; Xiaoqian Liang; Zihong Wang; Zhoucheng Wang; Yifan Chen; Qixin Deng; Guoguo Yi; et al. (Acta Parasitologica, 2021)
Purpose Prevention of ocular surface (OS) Demodex infestation plays an important role in OS hygiene and variety of factors may be associated with it, in which diabetes mellitus (DM) or dry eye disease (DED) has caught the attention of most scholars. However, there has been no research on whether there was a potential interaction between DM and DED in the process of OS Demodex infestation. This cross-sectional study was implemented in Zhujiang Hospital of Southern Medical University. Methods Ophthalmologic interviews, questionnaires, and examinations were conducted. Factors including general information, DM status, dry eye condition, etc. were collected to study the correlation of DM and DED on OS Demodex infestation. Results After statistical analysis, we found that both DM ( P P = 0.013 R = 0.197, P R = 0.299, P P Conclusion This study provides a new evidence-based basis for clinical prevention and management of OS Demodex infestation.

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Deformation of the Zhangjiazhuang high-speed railway tunnel: an analysis of causal mechanisms using geomorphological surveys and D-InSAR monitoring - Xing-min Meng; Tian-jun Qi; Yan Zhao; Tom Dijkstra; Wei Shi; Yin-fei Luo; Yuan-zhao Wu; Xiao-jun Su; Fu-meng Zhao; Jin-hui Ma; Yi Zhang; Guan Chen; et al. (Journal of Mountain Science, 2021)

Cysteiniphilum marinum sp. nov., isolated from coastal seawater - Hai-Min Luo; Jun-Hui Feng; Liang-Hui Li; Meng-Meng Li; Ru-Qin Liu; Fu Chen; Ying Lin; Wen-Jun Li; Ping-Hua Qu; Min Xiao (Antonie van Leeuwenhoek, 2021)

Agarose-based spheroid culture enhanced stemness and promoted odontogenic differentiation potential of human dental follicle cells in vitro - Min Li; Tiwei Fu; Sen Yang; Lanlan Pan; Jing Tang; Meng Chen; Panpan Liang; Zhi Gao; Lijuan Guo (In Vitro Cellular & Developmental Biology - Animal, 2021)

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

B3GNT3 acts as a carcinogenic factor in endometrial cancer via facilitating cell growth, invasion and migration through regulating RhoA/RAC1 pathway-associated markers - Ji-Shui Wang; Fang Ruan; Li-Zhu Guo; Feng-Ge Wang; Fu-Ling Wang; Hong-Min An (Genes & Genomics, 2021)

Tweety-Homolog 1 Facilitates Pain via Enhancement of Nociceptor Excitability and Spinal Synaptic Transmission - Wen-Juan Han; Sui-Bin Ma; Wen-Bin Wu; Fu-Dong Wang; Xiu-Li Cao; Dong-Hao Wang; Hai-Ning Wu; Rou-Gang Xie; Zhen-Zhen Li; Fei Wang; Sheng-Xi Wu; Min-Hua Zheng; et al. (Neuroscience Bulletin, 2021)

RepID-deficient cancer cells are sensitized to a drug targeting p97/VCP segregase - Sang-Min Jang; Christophe E. Redon; Haiqing Fu; Fred E. Indig; Mirit I. Aladjem (Molecular & Cellular Toxicology, 2021)
Background The p97/valosin-containing protein (VCP) complex is a crucial factor for the segregation of ubiquitinated proteins in the DNA damage response and repair pathway. Objective We investigated whether blocking the p97/VCP function can inhibit the proliferation of RepID-deficient cancer cells using immunofluorescence, clonogenic survival assay, fluorescence-activated cell sorting, and immunoblotting. Result p97/VCP was recruited to chromatin and colocalized with DNA double-strand breaks in RepID-deficient cancer cells that undergo spontaneous DNA damage. Inhibition of p97/VCP induced death of RepID-depleted cancer cells. This study highlights the potential of targeting p97/VCP complex as an anticancer therapeutic approach. Conclusion Our results show that RepID is required to prevent excessive DNA damage at the endogenous levels. Localization of p97/VCP to DSB sites was induced based on spontaneous DNA damage in RepID-depleted cancer cells. Anticancer drugs targeting p97/VCP may be highly potent in RepID-deficient cells. Therefore, we suggest that p97/VCP inhibitors synergize with RepID depletion to kill cancer cells.

Multi-GNSS real-time precise clock estimation considering the correction of inter-satellite code biases - Liang Chen; Min Li; Ying Zhao; Zhigang Hu; Fu Zheng; Chuang Shi (GPS Solutions, 2021)

In vitro anti-biofilm efficacy of sanguinarine against carbapenem-resistant Serratia marcescens - Yuting Fu; Wanting Liu; Miao Liu; Jianing Zhang; Min Yang; Ting Wang; Weidong Qian (Biofouling, 2021)

Litter addition and understory removal influenced soil organic carbon quality and mineral nitrogen supply in a subtropical plantation forest - Xiang-Min Fang; G. Geoff Wang; Zhi-Jun Xu; Ying-Ying Zong; Xiu-Lan Zhang; Jian-Jun Li; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

Spatiotemporal characteristics of sea ice transport in the Baffin Bay and its association with atmospheric variability - Weifu Sun; Haibo Bi; Min Fu; Xi Liang; Yunhe Wang; Yu Liang; Jue Huang; Haijun Huang; Liwen Yan; Qinglong Yu; Shuang Liang (Acta Oceanologica Sinica, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Quantitatively determine the dominant driving factors of the spatial—temporal changes of vegetation NPP in the Hengduan Mountain area during 2000–2015 - Shu-ting Chen; Bing Guo; Rui Zhang; Wen-qian Zang; Cui-xia Wei; Hong-wei Wu; Xiao Yang; Xiao-yan Zhen; Xing Li; Da-fu Zhang; Bao-min Han; Hai-ling Zhang (Journal of Mountain Science, 2021)

Piwi-interacting RNAs (piRNAs) as potential biomarkers and therapeutic targets for cardiovascular diseases - Min Li; Yanyan Yang; Zhibin Wang; Tingyu Zong; Xiuxiu Fu; Lynn Htet Htet Aung; Kun Wang; Jian-xun Wang; Tao Yu (Angiogenesis, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Geographical and interspecific variation in susceptibility of three common thrips species to the insecticide, spinetoram - Yong-Fu Gao; Ya-Jun Gong; Li-Jun Cao; Jin-Cui Chen; Yu-Lin Gao; Majid Mirab-balou; Min Chen; Ary A. Hoffmann; Shu-Jun Wei (Journal of Pest Science, 2021)

Safety of protease inhibitors and Arbidol for SARS-CoV-2 pneumonia in Zhejiang Province, China - Yong-zheng Guo; Kai-jin Xu; Yong-tao Li; Jia-dan Fu; Min Xu; Ling Yu; Ji-fang Sheng; Biao Zhu (Journal of Zhejiang University-SCIENCE B, 2020)

Can Dominant Canopy Species Leaf Litter Determine Soil Nutrient Heterogeneity? A Case Study in a Tropical Rainforest in Southwest China - Anjana J. Atapattu; Shang-wen Xia; Min Cao; Wen-fu Zhang; Sandhya Mishra; Xiaodong Yang (Journal of Soil Science and Plant Nutrition, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Development of a pro-arrhythmic ex vivo intact human and porcine model: cardiac electrophysiological changes associated with cellular uncoupling - Joseph Brook; Min-young Kim; Simos Koutsoftidis; David Pitcher; Danya Agha-Jaffar; Annam Sufi; Catherine Jenkins; Konstantinos Tzortzis; Suofeiya Ma; Richard J. Jabbour; Charles Houston; Balvinder S. Handa; et al. (Pflügers Archiv - European Journal of Physiology, 2020)
We describe a human and large animal Langendorff experimental apparatus for live electrophysiological studies and measure the electrophysiological changes due to gap junction uncoupling in human and porcine hearts. The resultant ex vivo intact human and porcine model can bridge the translational gap between smaller simple laboratory models and clinical research. In particular, electrophysiological models would benefit from the greater myocardial mass of a large heart due to its effects on far-field signal, electrode contact issues and motion artefacts, consequently more closely mimicking the clinical setting. Porcine ( n = 9) and human ( n = 4) donor hearts were perfused on a custom-designed Langendorff apparatus. Epicardial electrograms were collected at 16 sites across the left atrium and left ventricle. A total of 1 mM of carbenoxolone was administered at 5 ml/min to induce cellular uncoupling, and then recordings were repeated at the same sites. Changes in electrogram characteristics were analysed. We demonstrate the viability of a controlled ex vivo model of intact porcine and human hearts for electrophysiology with pharmacological modulation. Carbenoxolone reduces cellular coupling and changes contact electrogram features. The time from stimulus artefact to (-dV/dt) max increased between baseline and carbenoxolone (47.9 ± 4.1–67.2 ± 2.7 ms) indicating conduction slowing. The features with the largest percentage change between baseline and carbenoxolone were fractionation + 185.3%, endpoint amplitude − 106.9%, S-endpoint gradient + 54.9%, S point − 39.4%, RS ratio + 38.6% and (-dV/dt) max − 20.9%. The physiological relevance of this methodological tool is that it provides a model to further investigate pharmacologically induced pro-arrhythmic substrates.

Post-Orogenic Tectonic Evolution of the Jiangnan-Xuefeng Orogenic Belt: Insights from Multiple Geochronometric Dating of the Mufushan Massif, South China - Chuanbo Shen; Di Hu; Kyoungwon Min; Chaoqun Yang; Xiaowei Zeng; Hongyang Fu; Xiang Ge (Journal of Earth Science, 2020)

Campus Vibration in Nanwangshan Campus, China University of Geosciences at Wuhan Monitored by Short-Period Seismometers - Lihui Wu; Dun Wang; Ziguang Lei; Jing Fu; Shuai Min; Xianbing Xu; Sarina Bao (Journal of Earth Science, 2020)

The antiviral protein viperin interacts with the viral N protein to inhibit proliferation of porcine epidemic diarrhea virus - Jiaqi Wu; Heng Chi; Yali Fu; Aiping Cao; Jingxuan Shi; Min Zhu; Lilin Zhang; Deping Hua; Jinhai Huang (Archives of Virology, 2020)

Decadal characteristics of the floating Ulva and Sargassum in the Subei Shoal, Yellow Sea - Jie Xiao; Shiliang Fan; Zongling Wang; Mingzhu Fu; Hongjun Song; Xiao Wang; Chao Yuan; Min Pang; Xiaoxiang Miao; Xuelei Zhang (Acta Oceanologica Sinica, 2020)

Further evidence for paternal DNA transmission in gynogenetic grass carp - Zhuangwen Mao; Yeqing Fu; Shi Wang; Yude Wang; Kaikun Luo; Chun Zhang; Min Tao; Shaojun Liu (Science China Life Sciences, 2020)

KIF3A regulates the Wnt/β-catenin pathway via transporting β-catenin during spermatogenesis in Eriocheir sinensis - Ya-Jing Liang; Jia-Hao Ni; Lan-Min Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2020)

A new 5α,8α-epidioxysterol with immunosuppressive activity from the South China Sea soft coral Sinularia sp. - Min Yang; Lin-Fu Liang; Heng Li; Wei Tang; Yue-Wei Guo (Natural Product Research, 2020)

SNX-2112, an Hsp90 inhibitor, suppresses cervical cancer cells proliferation, migration, and invasion by inhibiting the Akt/mTOR signaling pathway - Liang-Shun Fu; Hong-Hong Qiu; Min Liu; Liu-Bing Hu; Yan Wang; Peng-Chao Zhang; Man-Mei Li; Yi-Fei Wang; Zhong Liu (Medicinal Chemistry Research, 2020)

Seed Priming with Spermidine and Trehalose Enhances Chilling Tolerance of Rice via Different Mechanisms - Yuying Fu; Zhihao Zhang; Jun Liu; Min Chen; Ronghui Pan; Weimin Hu; Yajing Guan; Jin Hu (Journal of Plant Growth Regulation, 2020)

Isolation and Neuroprotective Activity of Phenolic Derivatives from the Marine-Derived Fungus Penicillium janthinellum - Yaoyao Zheng; Xu Chen; Lumin Chen; Li Shen; Xiumei Fu; Qiuxia Chen; Min Chen; Changyun Wang (Journal of Ocean University of China, 2020)

The Complete Genome of Emcibacter congregatus ZYLT, a Marine Bacterium Encoding a CRISPR-Cas 9 Immune System - Zhe Zhao; Rui-an Zhang; Ge-yi Fu; Ran Zhang; Yan-fang Nie; Cong Sun; Min Wu (Current Microbiology, 2020)

The Potential Role of Marine Protein Hydrolyzates in Elevating Nutritive Values of Diets for Largemouth Bass, Micropterus salmoides - Min Dai; Songlin Li; Cefeng Fu; Hongjie Qiu; Naisong Chen (Frontiers in Marine Science, 2020)

Perfusion Changes of Unexplained Early Neurological Deterioration After Reperfusion Therapy - Jingjing Fu; Ying Zhou; Qingqing Li; Genlong Zhong; Sheng Zhang; Ruiting Zhang; Chang Liu; Minming Zhang; Min Lou (Translational Stroke Research, 2020)

Combined GWAS and QTL analysis for dissecting the genetic architecture of kernel test weight in maize - Xiaoxiang Zhang; Zhongrong Guan; Lei Wang; Jun Fu; Yinchao Zhang; Zhaoling Li; Langlang Ma; Peng Liu; Yanling Zhang; Min Liu; Peng Li; Chaoying Zou; et al. (Molecular Genetics and Genomics, 2020)

A practicable method to prepare nitrated proteins with peroxynitrite and low concentration of sodium hydroxide - Nan Zhang; Xiaochen Gao; Weijia Zhang; Doaa Higazy; Ke Wang; Zhenfang Fu; Min Cui (Molecular Biology Reports, 2020)

Acute response of Pacific white shrimp Litopenaeus vannamei to high-salinity reductions in osmosis-, metabolism-, and immune-related enzyme activities - Min Shen; Yanting Cui; Renjie Wang; Tiantian Dong; Haibin Ye; Shusheng Wang; Ranghui Fu; Yuquan Li (Aquaculture International, 2020)

Does pipelaying method affect the development of pipeline geohazards and maintenance cost? A case study of Zhongxian-Wuhan gas pipeline, China - Qinglu Deng; Min Fu; Xingwei Ren (Bulletin of Engineering Geology and the Environment, 2020)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

GPS satellite inter-frequency clock bias estimation using triple-frequency raw observations - Lei Fan; Chuang Shi; Min Li; Cheng Wang; Fu Zheng; Guifei Jing; Jun Zhang (Journal of Geodesy, 2019)

Autopolyploid induction via somatic embryogenesis in Lilium distichum Nakai and Lilium cernuum Komar - Linlan Fu; Yingying Zhu; Min Li; Chunxia Wang; Hongmei Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Progranulin alleviates podocyte injury via regulating CAMKK/AMPK-mediated autophagy under diabetic conditions - Di Zhou; Meng Zhou; Ziying Wang; Yi Fu; Meng Jia; Xiaojie Wang; Min Liu; Yan Zhang; Yu Sun; Yabin Zhou; Yi Lu; Wei Tang; et al. (Journal of Molecular Medicine, 2019)

Effects of nutrient addition on foliar phosphorus fractions and their resorption in different-aged leaves of Chinese fir in subtropical China - Fang-Chao Wang; Xiang-Min Fang; G. Geoff Wang; Rong Mao; Xiao-Fan Lin; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2019)

NFIC promotes the vitality and osteogenic differentiation of rat dental follicle cells - Fuping Zhang; Min Liang; Chuanjiang Zhao; Yun Fu; Shaojie Yu (Journal of Molecular Histology, 2019)

Spatiotemporal variation and influencing factors of vegetation cover in the ecologically fragile areas of China from 2000 to 2015: a case study in Shaanxi Province - Dingrao Feng; Jinman Wang; Meichen Fu; Guangchao Liu; Min Zhang; Rongbin Tang (Environmental Science and Pollution Research, 2019)

A simple and reliable method for creating PCR-detectable mutants in Arabidopsis with the polycistronic tRNA–gRNA CRISPR/Cas9 system - Liangliang Hui; Min Zhao; Junqi He; Yingying Hu; Yanshuang Huo; Houyan Hao; Yaqi Hao; Weining Zhu; Yuhua Wang; Min Xu; Aigen Fu (Acta Physiologiae Plantarum, 2019)
To develop an easy and robust method for creating genetically stable and easily detectable Arabidopsis mutants, we adopted the polycistronic tRNA–gRNA CRISPR/Cas9 (PTG/Cas9) system, a multiplex gene-editing tool in rice, with PTOX as the reporter gene. The PTG/Cas9 system has a great potential in generating large deletions detectable by PCR, which greatly simplifies the laborious work of mutant screening. We constructed a PTOX –PTG/Cas9 system with five gRNAs and introduced it into Arabidopsis . At T1 generation, 24.4% of transgenic plants were chimeric with PCR-detectable deletions in PTOX locus, but no homozygous mutant was found, indicating that gene editing occurred predominantly in somatic cells. After a self-cross propagation, 60% of T1 chimeric plants were able to produce homozygous, heterozygous, or bi-allelic ptox offsprings. Inheritable homozygous ptox mutants without Cas9 gene can be obtained earliest at T2 generation. We further targeted five other genes using the same procedure and achieved homozygous Cas9-free mutants with large deletions for all genes within three generations. We established a standard and reliable protocol to generate stable inherited deletion mutants in 2–3 generations along with simple PCR screening methods. We conclude that the rice PTG/Cas9 system is an efficient, easy, and rapid tool to edit genes in Arabidopsis . We propose that it could be applied to other genes in Arabidopsis , and it might have the potential to edit genes in other plant species as well.

African Orphan Crops Consortium (AOCC): status of developing genomic resources for African orphan crops - Prasad S. Hendre; Samuel Muthemba; Robert Kariba; Alice Muchugi; Yuan Fu; Yue Chang; Bo Song; Huan Liu; Min Liu; Xuezhu Liao; Sunil Kumar Sahu; Sibo Wang; et al. (Planta, 2019)

The effects of simulated deposited nitrogen on nutrient dynamics in decomposing litters across a wide quality spectrum using a 15N tracing technique - Xue-Min Ye; Yang Zhang; Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Xiao-Fan Lin; Song-Ze Wan; Ping He (Plant and Soil, 2019)

The Core Role of Bacillus subtilis and Aspergillus fumigatus in Pile-Fermentation Processing of Qingzhuan Brick Tea - Qian Xu; Min Sun; Jingming Ning; Shimao Fang; Ziling Ye; Junhai Chen; Ruiyan Fu (Indian Journal of Microbiology, 2019)

Identification of sugar response complex in the metallothionein OsMT2b gene promoter for enhancement of foreign protein production in transgenic rice - Chia-Yu Chang; Kuo-Wei Lee; Chung-Shen Wu; Yu-Hsing Huang; Ho-Chun Chang; Chien-Lung Chen; Chen-Tung Li; Min-Jeng Li; Chung-Fu Chang; Peng-Wen Chen (Plant Cell Reports, 2019)

Design and synthesis of novel 2-(6-thioxo-1,3,5-thiadiazinan-3-yl)-N′-phenylacethydrazide derivatives as potential fungicides - Xiaobin Wang; Xincan Fu; Jinghua Yan; An Wang; Mengqi Wang; Min Chen; Chunlong Yang; Yimin Song (Molecular Diversity, 2019)

Spatial-temporal variability of throughfall in a subtropical deciduous forest from the hilly regions of eastern China - Hai-xia Zhang; Hua-wu Wu; Jing Li; Bin He; Jiu-fu Liu; Niu Wang; Wei-li Duan; Ai-min Liao (Journal of Mountain Science, 2019)

Progressive multifocal leukoencephalopathy in a renal transplant patient - Tsu-Chen Lin; Mei-Yi Wu; Hui-Tzung Luh; Shiou-Fu Lin; Chien-Min Lin; Ying-Chi Tseng; Yung-Ching Liu; Mai-Szu Wu (Journal of NeuroVirology, 2019)

Hepatitis C virus 3b strains in injection drug users in Guangdong Province, China, may have originated in Yunnan Province - Min Wang; Qiao Liao; Ru Xu; Dandan Song; Jieting Huang; Qingzhu You; Zhengang Shan; Ke Huang; Xia Rong; Yongshui Fu (Archives of Virology, 2019)

Identification and Characterization of ATP/ADP Isopentenyltransferases (ATP/ADP PpIPTs) Genes in Peach - Min-ji Li; Qin-ping Wei; Fu-tian Peng; Wen Yu; Jing-jing Luo; Yong-fei Zhao (Journal of Plant Growth Regulation, 2019)

Characterization of a novel victorivirus isolated from the phytopathogenic fungus Botryosphaeria dothidea - Mengmeng Yang; Lifeng Zhai; Feng Xiao; Yashuang Guo; Min Fu; Ni Hong; Guoping Wang (Archives of Virology, 2019)

Mitochondrial Gene Heterogeneity and Population Genetics of Haemaphysalis longicornis (Acari: Ixodidae) in China - Zhong-Bo Li; Yi-Tian Fu; Tian-Yin Cheng; Guo-Min Yao; Qiang-Hong Hou; Fen Li; Yu Zhao; Feng-Cai Zou; Guo-Hua Liu (Acta Parasitologica, 2019)

Anti-oxidant and anti-inflammatory activities of ultrasonic-assistant extracted polyphenol-rich compounds from Sargassum muticum - Yuan Yu; Le Wang; Xiaoting Fu; Lei Wang; Xiaodan Fu; Min Yang; Zhenlian Han; Haijin Mou; You-Jin Jeon (Journal of Oceanology and Limnology, 2019)

Nitrogen deposition effect on forest litter decomposition is interactively regulated by endogenous litter quality and exogenous resource supply - Fu-Sheng Chen; G. Geoff Wang; Xiang-Min Fang; Song-Ze Wan; Yang Zhang; Chao Liang (Plant and Soil, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

The niches of nuthatches affect their lineage evolution differently across latitude - Yu‐Chi Chen; Masoud Nazarizadeh; Fu‐Min Lei; Xiao‐Jun Yang; Cheng‐Te Yao; Feng Dong; Lu Dong; Fa‐Sheng Zou; Sergei V. Drovetski; Yang Liu; Chun‐Cheng Huang; Chih‐Ming Hung (Molecular Ecology, 2019)
Ecological niche evolution can promote or hinder the differentiation of taxa and determine their distribution. Niche‐mediated evolution may differ among climatic regimes, and thus, species that occur across a wide latitudinal range offer a chance to test these heterogeneous evolutionary processes. In this study, we examine (a) how many lineages have evolved across the continent‐wide range of the Eurasian nuthatch ( Sitta europaea ), (b) whether the lineages’ niches are significantly divergent or conserved and (c) how their niche evolution explains their geographic distribution. Phylogenetic reconstruction and ecological niche models (ENMs) showed that the Eurasian nuthatch contained six parapatric lineages that diverged within 2 Myr and did not share identical climatic niches. However, the niche discrepancy between these distinct lineages was relatively conserved compared with the environmental differences between their ranges and thus was unlikely to drive lineage divergence. The ENMs of southern lineages tended to cross‐predict with their neighbouring lineages whereas those of northern lineages generally matched with their abutting ranges. The coalescence‐based analyses revealed more stable populations for the southern lineages than the northern ones during the last glaciation cycle. In contrast to the overlapping ENMs, the smaller parapatric distribution suggests that the southern lineages might have experienced competitive exclusion to prevent them from becoming sympatric. On the other hand, the northern lineages have expanded their ranges and their current abutting distribution might have resulted from lineages adapting to different climatic conditions in allopatry. This study suggests that niche evolution may affect lineage distribution in different ways across latitude.

Satellite-observed trends in the Arctic sea ice concentration for the period 1979–2016 - Yunhe Wang; Haibo Bi; Haijun Huang; Yanxia Liu; Yilin Liu; Xi Liang; Min Fu; Zehua Zhang (Journal of Oceanology and Limnology, 2019)

Microbiota transplantation reveals beneficial impact of berberine on hepatotoxicity by improving gut homeostasis - Chenjie Qin; Huilu Zhang; Linghao Zhao; Min Zeng; Weijian Huang; Gongbo Fu; Weiping Zhou; Hongyang Wang; Hexin Yan (Science China Life Sciences, 2018)

Down-regulation of microRNA-216a confers protection against yttrium aluminium garnet laser-induced retinal injury via the GDNF-mediated GDNF/GFRα1/RET signalling pathway - Xi-Bin Hu; Shu-Hua Fu; Qi Luo; Jian-Zhong He; Yan-Fei Qiu; Wei Lai; Min Zhong (Journal of Biosciences, 2018)

Different CO2 acclimation strategies in juvenile and mature leaves of Ottelia alismoides - Wen Min Huang; Hui Shao; Si Ning Zhou; Qin Zhou; Wen Long Fu; Ting Zhang; Hong Sheng Jiang; Wei Li; Brigitte Gontero; Stephen C. Maberly (Photosynthesis Research, 2018)

Shifts in the structure and function of the microbial community in response to metal pollution of fresh water sediments in Finland - Xue-Ping Chen; Hao-Yu Chen; Jing Sun; Xu Zhang; Chi-Quan He; Xiao-Yan Liu; Xin Huang; Min Yang; Fu-Shun Wang; Kristiina Väänänen (Journal of Soils and Sediments, 2018)

Recent satellite-derived sea ice volume flux through the Fram Strait: 2011–2015 - Haibo Bi; Yunhe Wang; Wenfeng Zhang; Zehua Zhang; Yu Liang; Yi Zhang; Wenmin Hu; Min Fu; Haijun Huang (Acta Oceanologica Sinica, 2018)

Biological floating bed and bio-contact oxidation processes for landscape water treatment: simultaneous removal of Microcystis aeruginosa, TOC, nitrogen and phosphorus - Jun feng Su; Dong hui Liang; Le Fu; Li Wei; Min Ma (Environmental Science and Pollution Research, 2018)

Agromyces mangrovi sp. nov., a Novel Actinobacterium Isolated from Mangrove Soil - Ruijun Wang; Can Chen; Yue Su; Xiaoyun Yu; Chongya Zhang; Geyi Fu; Shuaibo Han; Xianmao Pan; Junming Qiu; Xiaopin Li; Min Wu (Current Microbiology, 2018)

Lateral instability and tunnel erosion of a submarine pipeline: competition mechanism - Yu-min Shi; Fu-ping Gao (Bulletin of Engineering Geology and the Environment, 2018)

Plantar blood flow response to accumulated pressure stimulus in diabetic people with different peak plantar pressure: a non-randomized clinical trial - Fang Pu; Weiyan Ren; Hongyuan Fu; Xuan Zheng; Min Yang; Yih-Kuen Jan; Yubo Fan (Medical & Biological Engineering & Computing, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Functional Role of Matrix gla Protein in Glioma Cell Migration - Mu-Hui Fu; Chih-Yen Wang; Yun-Ti Hsieh; Kuan-Min Fang; Shun-Fen Tzeng (Molecular Neurobiology, 2018)

PGC-1α coordinates with Bcl-2 to control the cell cycle in U251 cells through reducing ROS - Kun Yao; Xu-feng Fu; Xing Du; Yan Li; Shan-shan Yang; Min Yu; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2018)

Periodic Variation of AAK1 in an Aβ1–42-Induced Mouse Model of Alzheimer’s Disease - Xue Fu; Meiling Ke; Weihua Yu; Xia Wang; Qian Xiao; Min Gu; Yang Lü (Journal of Molecular Neuroscience, 2018)

Crystal structure of Psb27 from Arabidopsis thaliana determined at a resolution of 1.85 Å - Cheng Xingxing; Liu Jiuyang; Zhang Huan; Li Fudong; Zhang Shuya; Xu Min; Ruan Ke; Wang Yuhua; Fu Aigen (Photosynthesis Research, 2018)

Microarray expression profiling and co-expression network analysis of circulating LncRNAs and mRNAs associated with neurotoxicity induced by BPA - Wei Pang; Fu-Zhi Lian; Xue Leng; Shu-min Wang; Yi-bo Li; Zi-yu Wang; Kai-ren Li; Zhi-xian Gao; Yu-gang Jiang (Environmental Science and Pollution Research, 2018)

Synthesis and biological evaluation of N-alkyl-1,4-dihydroquinoline prodrugs of scutellarin methyl ester as neuroprotective agents - Yongxi Dong; Li Dong; Jinglei Chen; Min Luo; Xiaozhong Fu; Chunhua Qiao (Medicinal Chemistry Research, 2018)

Isolation and identification of bovine nasopharyngeal mucosal epithelial cells and establishment of cell models of acute infection by foot-and-mouth disease virus - Wan-fu Bai; Lu Li; Ting Zhang; Xiao-hu Su; Yong-wei Wang; Bing-wu Zhao; Tao Zhang; Huan-min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2018)

Geological effects influence population genetic connectivity more than Pleistocene glaciations in the water strider Metrocoris sichuanensis (Insecta: Hemiptera: Gerridae) - Zhen Ye; Juanjuan Yuan; Min Li; Jakob Damgaard; Pingping Chen; Chenguang Zheng; Haibin Yu; Siying Fu; Wenjun Bu (Journal of Biogeography, 2018)
Aim Palaeoclimatic and palaeogeological events have been identified as two main factors that influence the genetic structuring of extant organisms. We studied a montane stream‐dwelling insect, Metrocoris sichuanensis , to explore the relative roles played by these two factors in population genetic connectivity. Location Sichuan Basin, China. Methods Mitochondrial ( COI , COII , Cytb, 16S) and nuclear ( EF ‐1α, ITS 1) markers were sequenced from 208 individuals. Suitable habitat shifts from the Last Glacial Maximum ( LGM ) to the present were predicted through fine‐tuned ecological niche modelling ( ENM ). Phylogenetic and phylogeographical analyses were conducted to reveal the population genetic structure. Intraspecific divergence and expansion times were estimated using beast . Finally, the least cost path ( LCP ) method coupled with migrate analysis was used to identify possible dispersal corridors and estimate the asymmetric gene flow. Results Our ENM results suggested that population habitat connectivity did not change both in the LGM and current conditions. Whole haplotypes were separated into four highly supported clades/haplogroups that exhibited strong geographical structure. The splitting events between the four lineages likely date back to the Early Pleistocene. Bayesian skyline plot ( BSP ) indicated a moderate demographic growth from the LGM to the present. A putative dispersal corridor was detected along the Longmen Mountains thrust belt, with unidirectional gene flow from north to south. Main conclusion Our findings support the geographical isolation of the genetic lineages and a deep early Pleistocene split in M. sichuanensis . Landscape connectivity analysis incorporating the genetic data and the ENM prediction revealed that population genetic connectivity was strongly associated with stable climatic habitats shaped by complex topography. The drainage system might have assisted the rapid movement of populations along the Longmen Mountains thrust belt. A strategy for researching the population genetic connectivity of narrow endemics, such as M. sichuanensis , in global biodiversity hotspots is proposed and discussed in this paper.

Physical interactions and mutational analysis of MoYpt7 in Magnaporthe oryzae - Lu-yao Huang; Min Wu; Xiao-yun Yu; Lin Li; Fu-cheng Lin; Xiao-hong Liu (Journal of Zhejiang University-SCIENCE B, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

Aestuarium zhoushanense gen. nov., sp. nov., Isolated from the Tidal Flat - Xiao-Yun Yu; Jing-Yu Zhai; Ge-Yi Fu; Xia Shen; Zhe Zhao; Min Wu; Xin-Qi Zhang (Current Microbiology, 2017)

Increasing winter conductive heat transfer in the Arctic sea-ice-covered areas: 1979–2014 - Xieyu Fan; Haibo Bi; Yunhe Wang; Min Fu; Xuan Zhou; Xiuli Xu; Haijun Huang (Journal of Ocean University of China, 2017)

Characterization of a novel botybirnavirus isolated from a phytopathogenic Alternaria fungus - Jun Xiang; Min Fu; Ni Hong; Lifeng Zhai; Feng Xiao; Guoping Wang (Archives of Virology, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Monazite behaviour during isothermal decompression in pelitic granulites: a case study from Dinggye, Tibetan Himalaya - Jia-Min Wang; Fu-Yuan Wu; Daniela Rubatto; Shi-Ran Liu; Jin-Jiang Zhang; Xiao-Chi Liu; Lei Yang (Contributions to Mineralogy and Petrology, 2017)

Aquatic animals promote antibiotic resistance gene dissemination in water via conjugation: Role of different regions within the zebra fish intestinal tract, and impact on fish intestinal microbiota - Jialun Fu; Dong Yang; Min Jin; Weili Liu; Xin Zhao; Chenyu Li; Tianyu Zhao; Jingfeng Wang; Zhixian Gao; Zhiqiang Shen; Zhigang Qiu; Jun‐Wen Li (Molecular Ecology, 2017)
The aqueous environment is one of many reservoirs of antibiotic resistance genes ( ARG s). Fish, as important aquatic animals which possess ideal intestinal niches for bacteria to grow and multiply, may ingest antibiotic resistance bacteria from aqueous environment. The fish gut would be a suitable environment for conjugal gene transfer including those encoding antibiotic resistance. However, little is known in relation to the impact of ingested ARG s or antibiotic resistance bacteria ( ARB ) on gut microbiota. Here, we applied the cultivation method, qPCR , nuclear molecular genetic marker and 16S rDNA amplicon sequencing technologies to develop a plasmid‐mediated ARG transfer model of zebrafish. Furthermore, we aimed to investigate the dissemination of ARG s in microbial communities of zebrafish guts after donors carrying self‐transferring plasmids that encode ARG s were introduced in aquaria. On average, 15% of faecal bacteria obtained ARG s through RP 4‐mediated conjugal transfer. The hindgut was the most important intestinal region supporting ARG dissemination, with concentrations of donor and transconjugant cells almost 25 times higher than those of other intestinal segments. Furthermore, in the hindgut where conjugal transfer occurred most actively, there was remarkable upregulation of the mRNA expression of the RP 4 plasmid regulatory genes, trbBp and trfAp . Exogenous bacteria seem to alter bacterial communities by increasing Escherichia and Bacteroides species, while decreasing Aeromonas compared with control groups. We identified the composition of transconjugants and abundance of both cultivable and uncultivable bacteria (the latter accounted for 90.4%–97.2% of total transconjugants). Our study suggests that aquatic animal guts contribute to the spread of ARG s in water environments.

Genome-wide analysis of GDSL-type esterases/lipases in Arabidopsis - Chia-Ping Lai; Li-Min Huang; Long-Fang O. Chen; Ming-Tsair Chan; Jei-Fu Shaw (Plant Molecular Biology, 2017)

Global changes of 5-hydroxymethylcytosine and 5-methylcytosine from normal to tumor tissues are associated with carcinogenesis and prognosis in colorectal cancer - Yi-ping Tian; Ai-fen Lin; Mei-fu Gan; Hao Wang; Dan Yu; Chong Lai; Dan-dan Zhang; Yi-min Zhu; Mao-de Lai (Journal of Zhejiang University-SCIENCE B, 2017)

Long-term fertilization increases soil nutrient accumulations but decreases biological activity in navel orange orchards of subtropical China - Song-Ze Wan; Han-Jiao Gu; Qing-Pei Yang; Xiao-Fei Hu; Xiang-Min Fang; Anand Narain Singh; Fu-Sheng Chen (Journal of Soils and Sediments, 2017)

Field testing of the surface electromagnetic prospecting system - Qing-Yun Di; Chang-Min Fu; Zhi-Guo An; Cheng Xu; Ya-Lu Wang; Zhong-Xing Wang (Applied Geophysics, 2017)

Increasing acidity of rain in subtropical tea plantation alters aluminum and nutrient distributions at the root-soil interface and in plant tissues - Xiao-Fei Hu; Fu-Sheng Chen; Michael L. Wine; Xiang-Min Fang (Plant and Soil, 2017)

Deletion of a target gene in Indica rice via CRISPR/Cas9 - Ying Wang; Lizhao Geng; Menglong Yuan; Juan Wei; Chen Jin; Min Li; Kun Yu; Ya Zhang; Huaibing Jin; Eric Wang; Zhijian Chai; Xiangdong Fu; et al. (Plant Cell Reports, 2017)

Novel adefovir mono L-amino acid ester, mono bile acid ester derivatives: Design, synthesis, biological evaluation, and molecular docking study - Ya Chen; Wen Zheng Zhang; Jing Li; Tao Xiao; Jiang Xia Liu; Min Luo; Hang Su; Xiao-Zhong Fu; Ting Liu; Yong-Xi Dong; Yong-Long Zhao; Bin He; et al. (Medicinal Chemistry Research, 2017)

Developing the science product algorithm testbed for Chinese next-generation geostationary meteorological satellites: Fengyun-4 series - Min Min; Chunqiang Wu; Chuan Li; Hui Liu; Na Xu; Xiao Wu; Lin Chen; Fu Wang; Fenglin Sun; Danyu Qin; Xi Wang; Bo Li; et al. (Journal of Meteorological Research, 2017)

An economic analysis of hard clam (Meretrix meretrix) farmer polyculture with milkfish (Chanos chanos), silver sea bream (Rhabdosargus sarba), and shrimps at different hard clam stocking densities: a case study of Yunlin County, Taiwan - Chun-Yuan Yeh; Jung-Fu Huang; Jie-Min Lee; Christian Schafferer (Aquaculture International, 2017)

Effects of starvation and feeding on blood chemistry, fatty acid composition and expression of vitellogenin and fatty acid-binding protein genes in female swimming crab Portunus trituberculatus broodstock - Liyun Ding; Huiyun Fu; Yingmei Hou; Min Jin; Peng Sun; Qicun Zhou (Fisheries Science, 2017)

Erratum to: Down-regulation of miR-181a can reduce heat stress damage in PBMCs of Holstein cows - Kun-Lin Chen; Yuan-Yuan Fu; Min-Yan Shi; Hui-Xia Li (In Vitro Cellular & Developmental Biology - Animal, 2017)

Association of oral endothelin receptor antagonists with risks of cardiovascular events and mortality: meta-analysis of randomized controlled trials - Yu Pan; Chun Hu; Pei Hua Chen; Yan Hong Gu; Qing Yan Qiao; Li Hua Pan; Dong Chi Zhou; Hui Fang Gu; Shun Kun Fu; Hui Min Jin (European Journal of Clinical Pharmacology, 2017)

Effects of zinc application rate and zinc distribution relative to root distribution on grain yield and grain Zn concentration in wheat - Dun-Yi Liu; Wei Zhang; Li-Li Pang; Yue-Qiang Zhang; Xiao-Zhong Wang; Yu-Min Liu; Xin-Ping Chen; Fu-Suo Zhang; Chun-Qin Zou (Plant and Soil, 2017)

Tornado hazards on June 23 in Jiangsu Province, China: preliminary investigation and analysis - Hai-Min Lyu; Guo-Fu Wang; Wen-Chieh Cheng; Shui-Long Shen (Natural Hazards, 2017)

Permeability of novel 4′-N-substituted (aminomethyl) benzoate-7-substituted nicotinic acid ester derivatives of scutellarein in Caco-2 cells and in an in vitro model of the blood-brain barrier - Yu Ou; Min Luo; Yong-Xi Dong; Hang Su; Xiao-Zhong Fu; Yu-Feng Cha; Shun Zhang; Yong-Long Zhao; Yong-Jun Li; Yong-Lin Wang (Medicinal Chemistry Research, 2016)

Probabilistic integrated risk assessment of human exposure risk to environmental bisphenol A pollution sources - Keng-Yen Fu; Yi-Hsien Cheng; Chia-Pin Chio; Chung-Min Liao (Environmental Science and Pollution Research, 2016)

Multienzymatic cascade synthesis of fucosyloligosaccharide via a two-step fermentation strategy in Escherichia coli - Hui-Min Qin; Songtao Li; Yu-Fu Zhang; Jian-Wen Wang; Jixuan Li; Shiyi Song; Fuping Lu; Yu Li (Biotechnology Letters, 2016)

Comparison of the immunogenicity of two inactivated recombinant rabies viruses overexpressing the glycoprotein - Muhammad Tariq Navid; Yingying Li; Ming Zhou; Min Cui; Zhen F. Fu; Lijun Tang; Ling Zhao (Archives of Virology, 2016)

Arctic sea ice thickness changes in terms of sea ice age - Haibo Bi; Min Fu; Ke Sun; Yilin Liu; Xiuli Xu; Haijun Huang (Acta Oceanologica Sinica, 2016)

Down-regulation of miR-181a can reduce heat stress damage in PBMCs of Holstein cows - Kun-Lin Chen; Yuan-Yuan Fu; Min-Yan Shi; Hui-Xia Li (In Vitro Cellular & Developmental Biology - Animal, 2016)

Role of methylenetetrahydrofolate reductase 677C→T polymorphism in the development of myocardial infarction: evidence from an original study and updated meta-analysis - Wenbin Zhang; Min Wang; Pei Zhang; Zhimin Xue; Guosheng Fu; Junbo Ge; Yi Luan (Genes & Genomics, 2016)

Serum uric acid levels in patients with infections of central nervous system - Jia Liu; Min Li; Xuan Wang; Huan Yi; Li Xu; Xiu-feng Zhong; Fu-hua Peng (Acta Neurologica Belgica, 2016)

Three new 2,5-diketopiperazines from the fish intestinal Streptomyces sp. MNU FJ-36 - Yi-xin Ou; Jia-fu Huang; Xiu-min Li; Qian-jin Kang; Yu-tian Pan (Natural Product Research, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Simulation for the Spatial–Time Characteristics of High Arch Dam - Lichun Zou; Shenghong Chen; Guojin Wang; Shaojun Fu; Xianliang Tang; Qing Xu; Zhiyong Zhao; Weiming Wang; Min Xie; Ji He (Geotechnical and Geological Engineering, 2016)

Levels, congener profile and inventory of polychlorinated biphenyls in sediment from the Songhua River in the vicinity of cement plant, China: a case study - Song Cui; Qiang Fu; Yi-Fan Li; Wen-long Li; Tian-xiao Li; Min Wang; Zhen-xiang Xing; Lu-ji Zhang (Environmental Science and Pollution Research, 2016)

Degradation of litter quality and decline of soil nitrogen mineralization after moso bamboo (Phyllostachys pubscens) expansion to neighboring broadleaved forest in subtropical China - Qing-ni Song; Ming Ouyang; Qing-pei Yang; Hui Lu; Guang-yao Yang; Fu-sheng Chen; Jian-Min Shi (Plant and Soil, 2016)

Effect of Lactobacillus Strains on Intestinal Microflora and Mucosa Immunity in Escherichia coli O157:H7-Induced Diarrhea in Mice - Xin Bian; Ting-ting Wang; Min Xu; Smith Etareri Evivie; Guang-Wen Luo; Hong-zhang Liang; Shang-fu Yu; Gui-Cheng Huo (Current Microbiology, 2016)

Melittin, the Major Pain-Producing Substance of Bee Venom - Jun Chen; Su-Min Guan; Wei Sun; Han Fu (Neuroscience Bulletin, 2016)

Genome-wide identification of WRKY family genes in peach and analysis of WRKY expression during bud dormancy - Min Chen; Qiuping Tan; Mingyue Sun; Dongmei Li; Xiling Fu; Xiude Chen; Wei Xiao; Ling Li; Dongsheng Gao (Molecular Genetics and Genomics, 2016)

CHD3 chromatin-remodeling factor PICKLE regulates floral transition partially via modulating LEAFY expression at the chromatin level in Arabidopsis - Xing Fu; Chaonan Li; Qing Liang; Yangyang Zhou; Hang He; Liu-Min Fan (Science China Life Sciences, 2016)

The effects of price changes on oyster farmers in Changhua County, Taiwan, who cultivate oysters at low and high densities - Li-Ming Ho; Jung-Fu Huang; Jie-Min Lee (Aquaculture International, 2016)

Sunfleck limits the small-scale distribution of endangered Kingdonia uniflora in the natural habitat of subalpine forest proved by its photosynthesis - Chen-Guang Zhang; Xiao Liu; Yi-Lei Fan; Mao Wang; Yong-Fu Chai; Peng-Cheng Wan; Ya-Min Wang; Ming Yue (Acta Physiologiae Plantarum, 2016)

Transcriptome sequencing discovers genes related to fatty acid biosynthesis in the seeds of Eucommia ulmoides - Yan-zhi Feng; Lu Wang; Jian-min Fu; Ta-na Wuyun; Hong-yan Du; Xiao-feng Tan; Feng Zou; Fang-dong Li (Genes & Genomics, 2016)

The potential function of prohibitin during spermatogenesis in Chinese fire-bellied newt Cynops orientalis - Jia-Min Jin; Cong-Cong Hou; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2016)

Assessment of intraseasonal variabilities in China Ocean Reanalysis (CORA) - Min Zhang; Lei Zhou; Hongli Fu; Lianghong Jiang; Xiangming Zhang (Acta Oceanologica Sinica, 2016)

PGC-1α regulates the cell cycle through ATP and ROS in CH1 cells - Xu-feng Fu; Kun Yao; Xing Du; Yan Li; Xiu-yu Yang; Min Yu; Mei-zhang Li; Qing-hua Cui (Journal of Zhejiang University-SCIENCE B, 2016)

CDK6 mediates the effect of attenuation of miR-1 on provoking cardiomyocyte hypertrophy - Weiwei Yuan; Chunmei Tang; Wensi Zhu; Jiening Zhu; Qiuxiong Lin; Yongheng Fu; Chunyu Deng; Yumei Xue; Min Yang; Shulin Wu; Zhixin Shan (Molecular and Cellular Biochemistry, 2016)

Effects of reconstructed magnetic field from sparse noisy boundary measurements on localization of active neural source - Hui-min Shen; Kok-Meng Lee; Liang Hu; Shaohui Foong; Xin Fu (Medical & Biological Engineering & Computing, 2016)

Standardized application of yeast bioluminescent reporters as endocrine disruptor screen for comparative analysis of wastewater effluents from membrane bioreactor and traditional activated sludge - Jun Wang; Melanie Eldridge; Fu-min Menn; Todd Dykes; Gary Sayler (Ecotoxicology, 2015)

The diversity changes of soil microbial communities stimulated by climate, soil type and vegetation type analyzed via a functional gene array - Fu Chen; Min Tan; Yongjun Yang; Jing Ma; Shaoliang Zhang; Gang Li (World Journal of Microbiology and Biotechnology, 2015)

The small GTP ase MoYpt 7 is required for membrane fusion in autophagy and pathogenicity of M agnaporthe oryzae - Xiao‐Hong Liu; Si‐Miao Chen; Hui‐Min Gao; Guo‐Ao Ning; Huan‐Bin Shi; Yao Wang; Bo Dong; Yao‐Yao Qi; Dong‐Mei Zhang; Guo‐Dong Lu; Zong‐Hua Wang; Jie Zhou; et al. (Environmental Microbiology, 2015)
Summary R ab GTP ases are required for vesicle–vacuolar fusion during vacuolar biogenesis in fungi. To date, little is known about the biological functions of the R ab small GTP ase components in M agnaporthe oryzae . In this study, we investigated MoYpt 7 of M . oryzae , a homologue of the small R as‐like GTP ase Ypt7 in S accharomyces cerevisiae . Cellular localization assays showed that MoYpt 7 was predominantly localized to vacuolar membranes. Using a targeted gene disruption strategy, a Δ MoYPT7 mutant was generated that exhibited defects in mycelial growth and production of conidia. The conidia of the Δ MoYPT7 mutant were malformed and defective in the formation of appressoria. Consequently, the Δ MoYPT7 mutant failed to cause disease in rice and barley. Furthermore, the Δ MoYPT7 mutant showed impairment in autophagy, breached cell wall integrity, and higher sensitivity to both calcium and heavy metal stress. Transformants constitutively expressing an active MoYPT7 allele ( MoYPT7 ‐ CA , G ln67 L eu) exhibited distinct phenotypes from the Δ MoYPT7 mutant. Expression of MoYPT7 ‐ CA in MoYpt 7 reduced pathogenicity and produced more appressoria‐forming single‐septum conidia. These results indicate that MoYPT7 is required for fungal morphogenesis, vacuole fusion, autophagy, stress resistance and pathogenicity in M . oryzae .

Distribution and phylogenetic analysis of Culex flavivirus in mosquitoes in China - Wenkai Liang; Xiaoxia He; Guifang Liu; Shaobai Zhang; Shihong Fu; Min Wang; Weixin Chen; Ying He; Xiaoyan Tao; Hongyue Jiang; Xiaojuan Lin; Xiaoyan Gao; et al. (Archives of Virology, 2015)

Therapeutic potential of human umbilical cord blood mesenchymal stem cells on erectile function in rats with cavernous nerve injury - Jian-Qiang Zhu; Hong-Kai Lu; Zhi-Qiang Cui; Yong-Chuan Wang; Yong-Hui Li; Weixin Zhao; Qiang Fu; Yue-Min Xu; Yong Xu; Lu-Jie Song (Biotechnology Letters, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Surface Properties and In Vitro Bioactivity of Fluorapatite/TiO2 Coatings Deposited on Ti Substrates by Nd:YAG Laser Cladding - Chi-Sheng Chien; Yu-Sheng Ko; Tsung-Yuan Kuo; Tze-Yuan Liao; Huan-Chang Lin; Tzer-Min Lee; Ting-Fu Hong (Journal of Medical and Biological Engineering, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

Major modes of short-term climate variability in the newly developed NUIST Earth System Model (NESM) - Jian Cao; Bin Wang; Baoqiang Xiang; Juan Li; Tianjie Wu; Xiouhua Fu; Liguang Wu; Jinzhong Min (Advances in Atmospheric Sciences, 2015)
A coupled earth system model (ESM) has been developed at the Nanjing University of Information Science and Technology (NUIST) by using version 5.3 of the European Centre Hamburg Model (ECHAM), version 3.4 of the Nucleus for European Modelling of the Ocean (NEMO), and version 4.1 of the Los Alamos sea ice model (CICE). The model is referred to as NUIST ESM1 (NESM1). Comprehensive and quantitative metrics are used to assess the model’s major modes of climate variability most relevant to subseasonal-to-interannual climate prediction. The model’s assessment is placed in a multi-model framework. The model yields a realistic annual mean and annual cycle of equatorial SST, and a reasonably realistic precipitation climatology, but has difficulty in capturing the spring-fall asymmetry and monsoon precipitation domains. The ENSO mode is reproduced well with respect to its spatial structure, power spectrum, phase locking to the annual cycle, and spatial structures of the central Pacific (CP)-ENSO and eastern Pacific (EP)-ENSO; however, the equatorial SST variability, biennial component of ENSO, and the amplitude of CP-ENSO are overestimated. The model captures realistic intraseasonal variability patterns, the vertical-zonal structures of the first two leading predictable modes of Madden-Julian Oscillation (MJO), and its eastward propagation; but the simulated MJO speed is significantly slower than observed. Compared with the T42 version, the high resolution version (T159) demonstrates improved simulation with respect to the climatology, interannual variance, monsoon-ENSO lead-lag correlation, spatial structures of the leading mode of the Asian-Australian monsoon rainfall variability, and the eastward propagation of the MJO.

Regional integrated environmental modeling system: development and application - Shuyu Wang; Congbin Fu; Helin Wei; Yun Qian; Zhe Xiong; Jinming Feng; Deming Zhao; Li Dan; Zhiwei Han; Bingkai Su; Ming Zhao; Yaocun Zhang; et al. (Climatic Change, 2015)

Association of an Exon SNP of SLC2A9 Gene with Hyperuricemia Complicated with Type 2 Diabetes Mellitus in the Chinese Male Han Population - Shi-Chao Xing; Xu-Fu Wang; Zhi-Min Miao; Xue-Zhi Zhang; Jun Zheng; Ying Yuan (Cell Biochemistry and Biophysics, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

What is crop heterosis: new insights into an old topic - Donghui Fu; Meili Xiao; Alice Hayward; Guanjie Jiang; Longrong Zhu; Qinghong Zhou; Jiqiang Li; Min Zhang (Journal of Applied Genetics, 2015)

Mapping of quantitative trait loci for cold tolerance at the early seedling stage in landrace rice Xiang 743 - Wenqiang Liu; Tingting Lu; Yongchao Li; Xiaowu Pan; Yonghong Duan; Jun Min; Xiqin Fu; Xinnian Sheng; Junzhi Xiao; Sanxiong Liu; Jiang Tan; Yi Yao; et al. (Euphytica, 2015)

Spatially resolved estimation of ozone-related mortality in the United States under two representative concentration pathways (RCPs) and their uncertainty - Young-Min Kim; Ying Zhou; Yang Gao; Joshua S. Fu; Brent A. Johnson; Cheng Huang; Yang Liu (Climatic Change, 2015)

A Combinatorial Yeast Overlay Method for the Isolation of Antibacterial Oligopeptides - Ran He; Liang Cui; Yan Cao; Zhixue Wang; Kai Wang; Min Fu; Shaoyun Song; Chuanfu Dong; Xiaoxuan Wu; Ye Gao; Xiaoxiao Zhang; Fan Feng; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Alterations of natural killer cells in traumatic brain injury - Xiao-Dong Kong; Sheng Bai; Xin Chen; Hui-Jie Wei; Wei-Na Jin; Min-Shu Li; Yaping Yan; Fu-Dong Shi (Neuroscience Bulletin, 2014)

Atmospheric correction of HJ-1 A/B CCD over land: Land surface reflectance calculation for geographical information product - Qiaoyan Fu; Xiangjun Min; Lin Sun; Shengfang Ma (Journal of Geographical Sciences, 2014)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Testing hypotheses of mitochondrial gene‐tree paraphyly: unravelling mitochondrial capture of the Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) by the Taiwan Scimitar Babbler ( P omatorhinus musicus ) - Feng Dong; Fa‐Sheng Zou; Fu‐Min Lei; Wei Liang; Shou‐Hsien Li; Xiao‐Jun Yang (Molecular Ecology, 2014)
Species‐level paraphyly inferred from mitochondrial gene trees is a prevalent phenomenon in taxonomy and systematics, but there are several potential causes that are not easily explained by currently used methods. This study aimed to test the underlying causes behind the observed paraphyly of Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) via statistical analyses of four mitochondrial (mt DNA ) and nine nuclear (nu DNA ) genes. Mitochondrial gene trees show paraphyly of P . ruficollis with respect to the Taiwan Scimitar Babbler ( P omatorhinus musicus ), but nuclear genealogies support a sister‐group relationship. Predictive coalescent simulations imply several hypothetical explanations, the most likely being mitochondrial capture of P . ruficollis by P . musicus for the observed cyto‐nuclear incongruence. Further approximate Bayesian computation suggests a unidirectional introgression model with substantial level of gene flow from P . ruficollis to P . musicus during their initial divergence during the Late Pleistocene. This specific observation frames several potential causes for incongruent outcomes of mitochondrial and nuclear introgression in general, and on the whole, our results underscore the strength of multiple independent loci for species delimitation and importance of testing hypotheses that explain disparate causes of mitochondrial gene‐tree paraphyly.

Positional variation in grain mineral nutrients within a rice panicle and its relation to phytic acid concentration - Da Su; Faisal Sultan; Ning-chun Zhao; Bing-ting Lei; Fu-biao Wang; Gang Pan; Fang-min Cheng (Journal of Zhejiang University-SCIENCE B, 2014)

Crosstalk between TGF-β1 and CXCR3 signaling during urethral fibrosis - Hong Xie; Chao Feng; Qiang Fu; Ying-Long Sa; Yue-Min Xu (Molecular and Cellular Biochemistry, 2014)

Sodium fluoride induces apoptosis in the kidney of rats through caspase-mediated pathways and DNA damage - Guo Hua Song; Ji Ping Gao; Chun Fang Wang; Chao Yang Chen; Xiao Yan Yan; Min Guo; Yu Wang; Fu Bing Huang (Journal of Physiology and Biochemistry, 2014)

Two new eunicellin-based diterpenoids from the South China Sea gorgonian Muricella sibogae Nutting - Yuan-Ming Zhou; Min Chen; Xiu-Mei Fu; Yu-Chun Fang; Chang-Yun Wang (Natural Product Research, 2014)

Comparison of complete genome sequences of dog rabies viruses isolated from China and Mexico reveals key amino acid changes that may be associated with virus replication and virulence - Fulai Yu; Guoqing Zhang; Xiangfu Zhong; Na Han; Yunfeng Song; Ling Zhao; Min Cui; Simon Rayner; Zhen F. Fu (Archives of Virology, 2014)

Nucleoside derivatives from the marine-derived fungus Aspergillus versicolor - Min Chen; Xiu-Mei Fu; Chui-Jian Kong; Chang-Yun Wang (Natural Product Research, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Production economics and profitability analysis of horizontal rack culture and horizontal rack culture coupled with raft-string culture methods: a case study of Pacific oyster (Crassostrea gigas) farming in Chiayi and Yunlin Counties, Taiwan - Jung-Fu Huang; Jie-Min Lee (Aquaculture International, 2014)

The Correlation Between Dielectric Properties and Microstructure of Femoral Bone in Rats with Different Bone Qualities - Feng Tao; Feng Fu; Fusheng You; Zhenyu Ji; Jun Wen; Xuetao Shi; Xiuzhen Dong; Min Yang (Annals of Biomedical Engineering, 2014)

The promoter and the 5′-untranslated region of rice metallothionein OsMT2b gene are capable of directing high-level gene expression in germinated rice embryos - Chung-Shen Wu; Dai-Yin Chen; Chung-Fu Chang; Min-Jeng Li; Kuei-Yu Hung; Liang-Jwu Chen; Peng-Wen Chen (Plant Cell Reports, 2014)

Requirement of Runx3 in pulmonary vasculogenesis - Jong-Min Lee; Hyuk-Jae Kwon; Wing-Fu Lai; Han-Sung Jung (Cell and Tissue Research, 2014)

Clodronate liposomes reduce excessive scar formation in a mouse model of burn injury by reducing collagen deposition and TGF-β1 expression - Shao-wei Lu; Xing-mei Zhang; Hong-min Luo; Yu-cai Fu; Ming-yan Xu; Shi-jie Tang (Molecular Biology Reports, 2014)

GIS and SBF for estimating groundwater recharge of a mountainous basin in the Wu River watershed, Taiwan - HSIN-FU YEH; HUNG-I LIN; SHING-TSZ LEE; MIN-HSIANG CHANG; KUO-CHIN HSU; CHENG-HAW LEE (Journal of Earth System Science, 2014)

The maize d2003, a novel allele of VP8, is required for maize internode elongation - Hongkun Lv; Jun Zheng; Tianyu Wang; Junjie Fu; Junling Huai; Haowei Min; Xiang Zhang; Baohua Tian; Yunsu Shi; Guoying Wang (Plant Molecular Biology, 2014)

Charlson comorbidity index helps predict the risk of mortality for patients with type 2 diabetic nephropathy - You-Qun Huang; Rong Gou; Yong-Shu Diao; Qing-Hua Yin; Wen-Xing Fan; Ya-Ping Liang; Yi Chen; Min Wu; Li Zang; Ling Li; Jing Zang; Lu Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Testosterone promotes vascular endothelial cell migration via upregulation of ROCK-2/moesin cascade - Weiyong Liao; Wenjun Huang; Yanhong Guo; Min Xin; Xiaodong Fu (Molecular Biology Reports, 2013)

Copper ultrastructural localization, subcellular distribution, and phytotoxicity in Hydrilla verticillata (L.f.) Royle - Qinsong Xu; Han Qiu; Weiyue Chu; Yongyang Fu; Sanjuan Cai; Haili Min; Sha Sha (Environmental Science and Pollution Research, 2013)

Molecular characterization of novel haplotypes of eIF4E family in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Shuan-Tao Liu; Zhi-Gang Zhang; Qiao-Yun Li; Shu-Fen Wang; Zhi-Zhong Zhao; Jin-Dong Lu; Wen-Ling Xu; Xian-Xian Liu; Wei-Min Fu (Genes & Genomics, 2013)

Influence of HbA1c on short-term blood pressure variability in type 2 diabetic patients with diabetic nephropathy - Fang Liu; Min Wu; Yan-huan Feng; Hui Zhong; Tian-lei Cui; You-qun Huang; Ya-ping Liang; Yong-shu Diao; Li Zang; Ling Li; Jing Zang; Hong-yu Qiu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Lack of association between SLCO1B1 polymorphism and the lipid-lowering effects of atorvastatin and simvastatin in Chinese individuals - Qiang Fu; Yan-Peng Li; Yuan Gao; Song-Hua Yang; Pei-Qi Lu; Min Jia; Li-Rong Zhang (European Journal of Clinical Pharmacology, 2013)

Acute Clenbuterol Induces Hypotension, Atrioventricular Block and Cardiac Asystole in the Rabbit - Yan Ke; Li-Lan Fu; Xia-Fei Hong; Run Dong; Tian-Ming Xu; Jing-Fei Guo; Yan Liu; Ji-Min Cao (Cardiovascular Toxicology, 2013)

Risk factors for primary lung cancer among never smokers by gender in a matched case–control study - Yen-Li Lo; Chin-Fu Hsiao; Gee-Chen Chang; Ying-Huang Tsai; Ming-Shyan Huang; Wu-Chou Su; Yuh-Min Chen; Che-Wei Hsin; Chin-Hao Chang; Pan-Chyr Yang; Chien-Jen Chen; Chao A. Hsiung (Cancer Causes & Control, 2013)

Nicardipine in the treatment of aneurysmal subarachnoid haemorrhage: a meta-analysis of published data - Ren-qiang Huang; Fu-gang Jiang; Zi-min Feng; Tian-yi Wang (Acta Neurologica Belgica, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

The Effect of Fetal and Early Postnatal Iron Deficiency on Iron Metabolism in Adult Rats - Jinyan Fu; Anqiang Yang; Yajing Ma; Min Liu; Licui Zhang; Yong Wang; Liegang Liu (Biological Trace Element Research, 2012)

The variation of tree beta diversity across a global network of forest plots - Miquel De Cáceres; Pierre Legendre; Renato Valencia; Min Cao; Li‐Wan Chang; George Chuyong; Richard Condit; Zhanqing Hao; Chang‐Fu Hsieh; Stephen Hubbell; David Kenfack; Keping Ma; et al. (Global Ecology and Biogeography, 2012)
Aims With the aim of understanding why some of the world's forests exhibit higher tree beta diversity values than others, we asked: (1) what is the contribution of environmentally related variation versus pure spatial and local stochastic variation to tree beta diversity assessed at the forest plot scale; (2) at what resolution are these beta‐diversity components more apparent; and (3) what determines the variation in tree beta diversity observed across regions/continents? Location World‐wide. Methods We compiled an unprecedented data set of 10 large‐scale stem‐mapping forest plots differing in latitude, tree species richness and topographic variability. We assessed the tree beta diversity found within each forest plot separately. The non‐directional variation in tree species composition among cells of the plot was our measure of beta diversity. We compared the beta diversity of each plot with the value expected under a null model. We also apportioned the beta diversity into four components: pure topographic, spatially structured topographic, pure spatial and unexplained. We used linear mixed models to interpret the variation of beta diversity values across the plots. Results Total tree beta diversity within a forest plot decreased with increasing cell size, and increased with tree species richness and the amount of topographic variability of the plot. The topography‐related component of beta diversity was correlated with the amount of topographic variability but was unrelated to its species richness. The unexplained variation was correlated with the beta diversity expected under the null model and with species richness. Main conclusions Because different components of beta diversity have different determinants, comparisons of tree beta diversity across regions should quantify not only overall variation in species composition but also its components. Global‐scale patterns in tree beta diversity are largely coupled with changes in gamma richness due to the relationship between the latter and the variation generated by local stochastic assembly processes.

Laboratory assessment of uptake and toxicity of lanthanum (La) in the leaves of Hydrocharis dubia (Bl.) Backer - Qinsong Xu; Yongyang Fu; Haili Min; Sanjuan Cai; Sha Sha; Guangyu Cheng (Environmental Science and Pollution Research, 2012)

Neuroprotection by Silencing iNOS Expression in a 6-OHDA Model of Parkinson’s Disease - Min Li; Fu-rong Dai; Xiao-ping Du; Qi-dong Yang; Yuxiang Chen (Journal of Molecular Neuroscience, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Spontaneous retroperitoneal hemorrhage after hemodialysis involving anticoagulant agents - Wen-xing Fan; Zheng-xu Deng; Fang Liu; Rong-bo Liu; Ling He; Bogati Amrit; Li Zang; Jing-wen Li; Xian-rong Liu; Song-min Huang; Ping Fu (Journal of Zhejiang University-SCIENCE B, 2012)

Simultaneous quantification of lopinavir and ritonavir in human plasma by high performance liquid chromatography coupled with UV detection - HuiJuan Kou; Min Ye; Qiang Fu; Yang Han; XiaoLi Du; Jing Xie; Zhu Zhu; TaiSheng Li (Science China Life Sciences, 2012)

Origin and geological significance of the 1.81 Ga hyalophane-rich pegmatite veins from the high-pressure granulite terrain in the Central Zone of North China Craton - Min Qu; JingHui Guo; Yong Lai; Peng Peng; Fu Liu (Science China Earth Sciences, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Speciation in the Rana chensinensis species complex and its relationship to the uplift of the Qinghai–Tibetan Plateau - WEI‐WEI ZHOU; YANG WEN; JINZHONG FU; YONG‐BIAO XU; JIE‐QIONG JIN; LI DING; MI‐SOOK MIN; JING CHE; YA‐PING ZHANG (Molecular Ecology, 2012)
Speciation remains a fundamental issue in biology. Herein, we report an investigation into speciation in the Rana chensinensis species complex using DNA sequence data from one mitochondrial and five nuclear genes. A phylogenetic analysis of the data revealed four major clades in the complex, and each of them was found to likely represent a species, including one cryptic species. Ecological niche models were generated from 19 climatic variables for three of the four major clades, which were represented by widespread sampling, including R. chensinensis , Rana kukunoris and the potential cryptic species. Each clade is associated with a unique ecological unit, and this indicates that ecological divergence probably drove speciation. Ecological divergence is likely related to the late Cenozoic orogenesis of the Qinghai–Tibetan Plateau. In addition, gene flow between species was detected but only in peripheral portions of the ranges of the four major clades, thus likely had little influence on the speciation processes. Discordances between mitochondrial and nuclear genes were also found; the nominal species, R. chensinensis , contains multiple maternal clades, suggesting potential mitochondrial introgression between R. chensinensis and R. kukunoris .

Fas/FasL pathway-mediated alveolar macrophage apoptosis involved in human silicosis - San-qiao Yao; Liying Wang Rojanasakul; Zhi-yuan Chen; Ying-jun Xu; Yu-ping Bai; Gang Chen; Xi-ying Zhang; Chun-min Zhang; Yan-qin Yu; Fu-hai Shen; Ju-xiang Yuan; Jie Chen; et al. (Apoptosis, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Integrin β4 Signaling Promotes Mammary Tumor Cell Adhesion to Brain Microvascular Endothelium by Inducing ErbB2-Mediated Secretion of VEGF - Jie Fan; Bin Cai; Min Zeng; Yanyan Hao; Filippo G. Giancotti; Bingmei M. Fu (Annals of Biomedical Engineering, 2011)

A comparison of three methods for estimating leaf area index of paddy rice from optimal hyperspectral bands - Fu-min Wang; Jing-feng Huang; Zhang-hua Lou (Precision Agriculture, 2011)

Crop nitrogen use and soil mineral nitrogen accumulation under different crop combinations and patterns of strip intercropping in northwest China - Chun-Jie Li; Yu-Ying Li; Chang-Bing Yu; Jian-Hao Sun; Peter Christie; Min An; Fu-Suo Zhang; Long Li (Plant and Soil, 2011)

Water resources planning and management based on system dynamics: a case study of Yulin city - Xiao-jun Wang; Jian-yun Zhang; Jiu-fu Liu; Guo-qing Wang; Rui-min He; Amgad Elmahdi; Sondoss Elsawah (Environment, Development and Sustainability, 2011)

Identification of QTLs for maize seed vigor at three stages of seed maturity using a RIL population - Liu Jing-bao; Fu Zhi-yuan; Xie Hui-ling; Hu Yan-min; Liu Zong-hua; Duan Liu-jing; Xu Shang-zhong; Tang Ji-hua (Euphytica, 2011)

Up-regulation of growth factor independence 1 in endotoxin tolerant macrophages with low secretion of TNF-α and IL-6 - Min-Fang Zhu; Jing Zhang; Jie-Ming Qu; Hui-Jun Zhang; Shuang-Cheng Zhou; Sheng-Fu Dong; Hong-Ni Jiang; Hanssa Summah (Inflammation Research, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Analysis of Brassica rapa ESTs: gene discovery and expression patterns of AP2/ERF family genes - Jing Zhuang; Ai-Sheng Xiong; Ri-He Peng; Feng Gao; Bo Zhu; Jian Zhang; Xiao-Yan Fu; Xiao-Feng Jin; Jian-Min Chen; Zhen Zhang; Yu-Shan Qiao; Quan-Hong Yao (Molecular Biology Reports, 2010)

Multiple shoots induction in wild cotton (Gossypium bickii) through organogenesis and the analysis of genetic homogeneity of the regenerated plants - Xi-Yan Yang; Xian-Long Zhang; Li-Li Fu; Ling Min; Guan-ze Liu (Biologia, 2010)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Genome-wide transcriptome analysis of two maize inbred lines under drought stress - Jun Zheng; Junjie Fu; Mingyue Gou; Junling Huai; Yunjun Liu; Min Jian; Quansheng Huang; Xiying Guo; Zhigang Dong; Hongzhi Wang; Guoying Wang (Plant Molecular Biology, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Magnesium sulfate enhances exercise performance and manipulates dynamic changes in peripheral glucose utilization - Shiu-Min Cheng; Lin-Lan Yang; Sy-Huah Chen; Mei-Hsiang Hsu; I-Ju Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2010)

Necessity of Screening Water Chestnuts for Microcystins After Cyanobacterial Blooms Break Out - Fu-Gang Xiao; Xiao-Lian Zhao; Jian Tang; Xiao-Hong Gu; Jing-Ping Zhang; Wei-Min Niu (Archives of Environmental Contamination and Toxicology, 2009)

An efficient method to enhance gene silencing by using precursor microRNA designed small hairpin RNAs - Zhixin Shan; Qiuxiong Lin; Chunyu Deng; Xiaohong Li; Wei Huang; Honghong Tan; Yongheng Fu; Min Yang; Xi-Yong Yu (Molecular Biology Reports, 2009)

Improvement of arachidonic acid and eicosapentaenoic acid production by increasing the copy number of the genes encoding fatty acid desaturase and elongase into Pichia pastoris - Yun-Tao Li; Mao-Teng Li; Chu-Hua Fu; Peng-Peng Zhou; Jian-Min Liu; Long-Jiang Yu (Biotechnology Letters, 2009)

MoFLP1, encoding a novel fungal fasciclin-like protein, is involved in conidiation and pathogenicity in Magnaporthe oryzae - Tong-bao Liu; Guo-qing Chen; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Inhibition of hepatitis B virus replication by small interference RNA induces expression of MICA in HepG2.2.15 cells - Kai-Fu Tang; Min Chen; Jing Xie; Guan-Bin Song; Yi-Song Shi; Qi Liu; Zhe-Chuan Mei; Alexander Steinle; Hong Ren (Medical Microbiology and Immunology, 2009)

Determination of Microcystin-LR in Water from Lake Tai, China - Fu-Gang Xiao; Xiao-Lian Zhao; Jian Tang; Xiao-Hong Gu; Jing-Ping Zhang; Wei-Min Niu (Bulletin of Environmental Contamination and Toxicology, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

A phylogenetic analysis of laughingthrushes (Timaliidae: Garrulax ) and allies based on mitochondrial and nuclear DNA sequences - Xu Luo; Yan Hua Qu; Lian Xian Han; Shou Hsien Li; Fu Min Lei (Zoologica Scripta, 2009)
The interspecific relationships among extant laughingthrushes have been unclear for a long time and this has resulted in a confusing taxonomic history. Recent advances in molecular methods have greatly improved the resolution of the phylogeny of birds; however, little works has been done on this specific group because of the inaccessibility to many species. This diverse group includes 50 species mostly distributed in South China and South‐east Asia, and were traditionally arranged into the genus Garrulax , for which the non monophyly had been questioned by previous molecular studies. In this study, we infer a phylogeny for 23 Garrulax species and 20 species from close related genera. Mitochondrial data or combined with nuclear sequences both indicate paraphyly of Garrulax , dividing Garrulax species into two groups. Based on these results, we suggest resurrecting the genus name Trochalopteron Blyth, 1843 for one group and retaining Garrulax for the other pending further study. Using dating methods with a secondary calibration point, we develop a profile of the speciation history of laughingthrushes, which suggests that the Hengduan Mountains might not be the centre of origin for these birds as previously suggested.

Optimal waveband identification for estimation of leaf area index of paddy rice - Fu-min Wang; Jing-feng Huang; Qi-fa Zhou; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

A simple and effective method for total RNA isolation of appressoria in Magnaporthe oryzae - Tong-bao Liu; Jian-ping Lu; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

β-Adrenoceptors, but not dopamine receptors, mediate dopamine-induced ion transport in late distal colon of rats - Xiao-Hui Zhang; Xie-Fu Zhang; Jiu-Qin Zhang; Yue-Min Tian; Hong Xue; Ning Yang; Jin-Xia Zhu (Cell and Tissue Research, 2008)

No Correlation Between Heterozygosity and Vegetative Fitness in the Narrow Endemic and Critically Endangered Clematis acerifolia (Ranunculaceae) - Jordi López-Pujol; Fu-Min Zhang; Song Ge (Biochemical Genetics, 2008)

One new cinnamic imide dervative from the fruits of Tribulus terrestris - A-Li Lv; Nan Zhang; Min-Ge Sun; Yong-Fu Huang; Yi Sun; Hong-Yu Ma; Hui-Ming Hua; Yue-Hu Pei (Natural Product Research, 2008)

The sweet potato sporamin promoter confers high-level phytase expression and improves organic phosphorus acquisition and tuber yield of transgenic potato - Ya-Fang Hong; Chang-Yeu Liu; Kuo-Joan Cheng; Ai-Ling Hour; Min-Tsair Chan; Tung-Hai Tseng; Kai-Yi Chen; Jei-Fu Shaw; Su-May Yu (Plant Molecular Biology, 2008)

Magnaporthe oryzae MTP1 gene encodes a type III transmembrane protein involved in conidiation and conidial germination - Qin Lu; Jian-ping Lu; Xiao-dong Li; Xiao-hong Liu; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2008)

Solid lipid nanoparticles loading adefovir dipivoxil for antiviral therapy - Zhang Xing-guo; Miao Jing; Li Min-wei; Jiang Sai-ping; Hu Fu-qiang; Du Yong-zhong (Journal of Zhejiang University-SCIENCE B, 2008)

Quantifying biochemical variables of corn by hyperspectral reflectance at leaf scale - Qiu-xiang Yi; Jing-feng Huang; Fu-min Wang; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Evidence of Gene Conversion in the Evolutionary Process of the Codon 41/42 (-CTTT) Mutation Causing β-Thalassemia in Southern China - Wen Zhang; Wang-Wei Cai; Wei-Ping Zhou; Hai-Peng Li; Liang Li; Wei Yan; Qin-Kai Deng; Ya-Ping Zhang; Yun-Xin Fu; Xiang-Min Xu (Journal of Molecular Evolution, 2008)

Modeling the spill in the Songhua River after the explosion in the petrochemical plant in Jilin - Wenjing Fu; Huijin Fu; Karen Skøtt; Min Yang (Environmental Science and Pollution Research, 2008)

A new isopentenyl diphosphate isomerase gene from sweet potato: cloning, characterization and color complementation - Zhihua Liao; Min Chen; Yijian Yang; Chunxian Yang; Yufan Fu; Qitang Zhang; Qiang Wang (Biologia, 2008)

Genetic Diversity and Geographic Differentiation in the Threatened Species Dysosma pleiantha in China as Revealed by ISSR Analysis - Min Zong; Hai-Long Liu; Ying-Xiong Qiu; Shu-Zhen Yang; Ming-Shui Zhao; Cheng-Xin Fu (Biochemical Genetics, 2008)

Evolution of subcontinental lithospheric mantle beneath eastern China: Re–Os isotopic evidence from mantle xenoliths in Paleozoic kimberlites and Mesozoic basalts - Hong-Fu Zhang; Steven L. Goldstein; Xin-Hua Zhou; Min Sun; Jian-Ping Zheng; Yue Cai (Contributions to Mineralogy and Petrology, 2008)

Areas of endemism and patterns of diversity for aphids of the Qinghai‐Tibetan Plateau and the Himalayas - Xiao‐Lei Huang; Fu‐Min Lei; Ge‐Xia Qiao (Journal of Biogeography, 2008)
Aim The study aimed to identify areas of endemism for aphids in the Qinghai‐Tibetan Plateau and the Himalayas (QTPH), and to test congruence between patterns of endemism and patterns of overall species richness identified in a previous study. Location The QTPH. Methods A distribution data base of 326 endemic aphids in the QTPH was compiled. The study area was divided into a grid of 2°× 2° operative geographical units. Parsimony analysis of endemicity (PAE) was used to identify areas of endemism, and the diversity patterns of endemic species were then mapped using GIS. Results We identified 326 endemic species belonging to 138 genera within Adelgidae and 14 subfamilies of Aphididae. Five areas of endemism were found using PAE analysis: the eastern Himalayas, the western Himalayas, north‐western Yunnan, southern Tibet and the eastern QTPH. Maps of patterns of endemism identified four major centres for endemic aphids, namely the western Himalayas, the eastern Himalayas (or Sikkim‐Assam Himalayas), north‐western Hengduan Mountains and the mountains of southern Gansu Province, and three minor centres, southern Tibet, south‐eastern Tibet and the eastern Qinghai Province in the north‐eastern QTPH. Main conclusions Our study identifies major centres of aphid endemism. Furthermore, there is a noticeable congruence between patterns of endemism and patterns of species richness. The patterns of endemism were most likely influenced by the recent uplift of the QTPH.

Antitumor Effect of Paclitaxel-Loaded PEGylated Immunoliposomes Against Human Breast Cancer Cells - Tao Yang; Min-Koo Choi; Fu-De Cui; Seung-Jin Lee; Suk-Jae Chung; Chang-Koo Shim; Dae-Duk Kim (Pharmaceutical Research, 2007)

Relative Contributions of Collagen and Elastin to Elasticity of the Vocal Fold Under Tension - Roger W. Chan; Min Fu; Lindsay Young; Neeraj Tirunagari (Annals of Biomedical Engineering, 2007)

Hepatoprotective effect of a protein-enriched fraction from the maggots (Musca domestica) against CCl4-induced hepatic damage in rats - Fu-Rong Wang; Hui Ai; Xiao-Min Chen; Chao-Liang Lei (Biotechnology Letters, 2007)

Expression of CYP2E1 in human nasopharynx and its metabolic effect in vitro - De-Fu Hou; Shui-Liang Wang; Zhi-Min He; Fang Yang; Zhu-Chu Chen (Molecular and Cellular Biochemistry, 2007)

Proteomic analysis of the serum in patients with idiopathic pulmonary arterial hypertension - Min Yu; Xing-xiang Wang; Fu-rong Zhang; Yun-peng Shang; Yu-xi Du; Hong-juan Chen; Jun-zhu Chen (Journal of Zhejiang University-SCIENCE B, 2007)

China Subregional Avian Endemism and Biodiversity Conservation - Fu-Min Lei; Guo-An Wei; Hong-Feng Zhao; Zuo-Hua Yin; Jian-Li Lu (Biodiversity and Conservation, 2007)

Approximate recovery of coseismic deformation from Taiwan strong-motion records - Yih-Min Wu; Chien-Fu Wu (Journal of Seismology, 2007)

Effects of magnesium sulfate on dynamic changes of brain glucose and its metabolites during a short-term forced swimming in gerbils - Shiu-Min Cheng; Dar-Yu Yang; Chien-Pin Lee; Hung-Chuan Pan; Mao-Tsun Lin; Ssu-Hua Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2007)

Isolation of a human gallbladder cancer cell clone with high invasive phenotype in vitro and metastatic potential in orthotopic model and inhibition of its invasiveness by heparanase antisense oligodeoxynucleotides - Xin-Zhong Chang; Zhan-Min Wang; Jin-Ming Yu; Fu-Guo Tian; Wei Jin; Yi Zhang; Jie Yu; Lian-Fang Li; Xiao-Feng Liu; Zhi-Wei Li; Zhi-Min Shao (Clinical & Experimental Metastasis, 2007)

Plant Biodiversity in China: Richly Varied, Endangered, and in Need of Conservation - Jordi López-Pujol; Fu-Min Zhang; Song Ge (Biodiversity and Conservation, 2006)

Arsenic Uptake and Accumulation in Rice (Oryza sativa L.) at Different Growth Stages following Soil Incorporation of Roxarsone and Arsanilic Acid - Fu-Min Wang; Zhang-Liu Chen; Lu Zhang; Yan-Ling Gao; Yong-Xue Sun (Plant and Soil, 2006)

Surveillance of viral contamination of invasive medical instruments in dentistry - Lin-fu Zhou; Hai-hong Zhu; Jun Lin; Min-jun Hu; Feng Chen; Zhi Chen (Journal of Zhejiang University-SCIENCE B, 2006)

Geochemistry of the Emeishan flood basalts at Yangliuping, Sichuan, SW China: implications for sulfide segregation - Xie-Yan Song; Mei-Fu Zhou; Reid R. Keays; Zhi-Min Cao; Min Sun; Liang Qi (Contributions to Mineralogy and Petrology, 2006)

Successful implantation of intravenously administered stem cells correlates with severity of inflammation in murine myocarditis - Sohail Malek; Emel Kaplan; Ju-Feng Wang; Qingen Ke; Jamal S. Rana; Yu Chen; Bilal G. Rahim; Ma Li; Qin Huang; Yong-Fu Xiao; Freek W. A. Verheugt; James P. Morgan; et al. (Pflügers Archiv - European Journal of Physiology, 2006)

Promoter trapping in Magnaporthe grisea - Xiao-hong Liu; Jian-ping Lu; Jiao-yu Wang; Hang Min; Fu-cheng Lin (Journal of Zhejiang University-SCIENCE B, 2006)

Geochemistry and petrogenesis of the Yishak Volcanic Sequence, Kudi ophiolite, West Kunlun (NW China): implications for the magmatic evolution in a subduction zone environment - Chao Yuan; Min Sun; Mei-Fu Zhou; Wenjiao Xiao; Hui Zhou (Contributions to Mineralogy and Petrology, 2005)

Postglacial colonization of the Tibetan plateau inferred from the matrilineal genetic structure of the endemic red‐necked snow finch, Pyrgilauda ruficollis - YAN HUA QU; PER G. P. ERICSON; FU MIN LEI; SHOU HSIEN LI (Molecular Ecology, 2005)
Most phylogeographical studies of postglacial colonization focus on high latitude locations in the Northern Hemisphere. Here, we studied the phylogeographical structure of the red‐necked snow finch Pyrgilauda ruficollis , an endemic species of the Tibetan plateau. We analysed 879 base pairs (bp) of the mitochondrial cytochrome b gene and 529 bp of the control region in 41 birds from four regional groups separated by mountain ranges. We detected 34 haplotypes, 31 of which occurred in a single individual and only three of which were shared among sampling sites within regional groups or among regional groups. Haplotype diversity was high ( h = 0.94); nucleotide diversity was low (ð = 0.00415) and genetic differentiation was virtually non‐existent. Analyses of mismatch distributions and geographically nested clades yielded results consistent with contiguous range expansion, and the expansion times were estimated as 0.07–0.19 million years ago (Ma). Our results suggest that P. ruficollis colonized the Tibetan plateau after the extensive glacial period (0.5–0.175 Ma), expanding from the eastern margin towards the inner plateau. Thus, in contrast to many of the postglacial phylogeographical structures known at high latitudes, this colonization occurred without matrilineal population structuring. This might be due to the short glacial cycles typical of the Tibetan plateau, adaptation of P. ruficollis to cold conditions, or refugia and colonized habitat being semicontinuous and thus promoting population mixing.

Phylogeny of Aconitum subgenus Aconitum (Ranunculaceae) inferred from ITS sequences - Yan Luo; Fu-min Zhang; Qin-Er Yang (Plant Systematics and Evolution, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Specific amino acid restriction inhibits attachment and spreading of human melanoma via modulation of the integrin/focal adhesion kinase pathway and actin cytoskeleton remodeling - Ya-Min Fu; Hui Zhang; Mingjie Ding; Yi-Qi Li; Xing Fu; Zu-Xi Yu; Gary G. Meadows (Clinical & Experimental Metastasis, 2005)

Effective induction of immune tolerance by portal venous infusion with IL-10 gene-modified immature dendritic cells leading to prolongation of allograft survival - Ming Zhang; Quanxing Wang; Yushan Liu; Yanping Sun; Guoshan Ding; Zhiren Fu; Zhilian Min; Youhua Zhu; Xuetao Cao (Journal of Molecular Medicine, 2004)

Spontaneous clearance of high-titer serum HBV DNA and risk of hepatocellular carcinoma in a Chinese population - Rebecca A. Harris; Gang Chen; Wen Yao Lin; Fu Min Shen; W. Thomas London; Alison A. Evans (Cancer Causes & Control, 2003)

Priorities for the conservation of avian biodiversity in China based on the distribution patterns of endemic bird genera - Fu-Min Lei; Yan-Hua Qu; Qian-Qian Tang; Shu-Cheng An (Biodiversity and Conservation, 2003)

Ni?Cu?(PGE) magmatic sulfide deposits in the Yangliuping area, Permian Emeishan igneous province, SW China - Xie-Yan Song; Mei-Fu Zhou; Zhi-Min Cao; Min Sun; Yun-Liang Wang (Mineralium Deposita, 2003)

Seasonal variations of anthropogenic sulfate aerosol and direct radiative forcing over China - Ti-Jian Wang; Jin-Zhong Min; Yong-Fu Xu; Ka-Se Lam (Meteorology and Atmospheric Physics, 2003)

Absence of Archean basement in the South Kunlun Block: Nd‐Sr‐O isotopic evidence from granitoids - Chao Yuan; Min Sun; Mei‐Fu Zhou; Hui Zhou; Wenjiao Xiao; Jiliang Li (Island Arc, 2003)
The West Kunlun mountain range along the northwestern margin of the Tibetan Plateau is crucial in understanding the early tectonic history of the region. It can be divided into the North and South Kunlun Blocks, of which the former is considered to be part of the Tarim Craton, whereas consensus was not reached on the nature and origin of the South Kunlun Block. Samples were collected from the 471 Ma Yirba Pluton, the 405 Ma North Kudi Pluton and the 214 Ma Arkarz Shan Intrusive Complex. These granitoids cover approximately 60% of the Kudi area in the South Kunlun Block. Sr, Nd, and O isotope compositions preclude significant involvement of mantle‐derived magma in the genesis of these granitoids; therefore, they can be used to decipher the nature of lower–mid crust in the area. All samples give Mesoproterozoic Nd model ages (1.1–1.5 Ga) similar to those of the exposed metamorphic complex of this block but significantly different from those of the basement of the North Kunlun Block (2.8 Ga). This indicates that the South Kunlun Block does not have an Archean basement, and, thus, does not support the microcontinent model that suggests the South Kunlun Block was a microcontinent once separated from and later collided back with the North Kunlun Block.

Acute and moderate-term creatine monohydrate supplementation does not affect creatine transporter mRNA or protein content in either young or elderly humans - Mark Tarnopolsky; Gianni Parise; Min-H Fu Surname; Andrea Brose; Andrew Prasad; Oliver Speer; Theo Wallimann (Molecular and Cellular Biochemistry, 2003)

Conservation on diversity and distribution patterns of endemic birds in China - Fu-Min Lei; Yan-Hua Qu; Jian-Li Lu; Yao Liu; Zuo-Hua Yin (Biodiversity and Conservation, 2003)

Protective effects of adenoviral cardiotrophin-1 gene transfer on rubrospinal neurons after spinal cord injury in adult rats - Zheng-Feng Zhang; Wei-Hong Liao; Qing-Feng Yang; Hong-Yun Li; Ya-Min Wu; Xin-Fu Zhou (Neurotoxicity Research, 2003)

The interfacial mass transfer resistances of the ozone dry deposition over the field soil of Taichung county in Taiwan - Hsin-Min Chang; Len-Fu W. Chang; Fu-Tien Jeng (Environmental Science and Pollution Research, 2002)

Mesozoic lithosphere destruction beneath the North China Craton: evidence from major-, trace-element and Sr–Nd–Pb isotope studies of Fangcheng basalts - Hong-Fu Zhang; Min Sun; Xin-Hua Zhou; Wei-Ming Fan; Ming-Guo Zhai; Ji-Feng Yin (Contributions to Mineralogy and Petrology, 2002)

Platinum-group element geochemistry of the Hongge Fe–V–Ti deposit in the Pan-Xi area, southwestern China - Hong Zhong; Xin-Hua Zhou; Mei-Fu Zhou; Min Sun; Bing-Guang Liu (Mineralium Deposita, 2002)

Distribution of Polycyclic Aromatic Hydrocarbons in Aerosols and Dustfall in Macao - Qi Shihua; Yan Jun; Zhang Gan; Fu Jiamo; Sheng Guoying; Wang Zhishi; S. M. Tong; U. W. Tang; Min Yunshun (Environmental Monitoring and Assessment, 2001)

Effect of apple production base on regional water cycle in Weibei upland of the Loess Plateau - Huang Ming-bin; He Fu-hong; Yang Xin-min; Li Yu-shan (Journal of Geographical Sciences, 2001)

Seasonal variations of riverine organic carbon contents in Makou and Hekou gauge stations of the Zhujiang River, China - Quan-zhou Gao; Cheng-de Shen; Yan-min Sun; Wei-xi Yi; Jia-mo Fu; Guo-ying Sheng (Chinese Geographical Science, 2000)

The types of lake in Songnen Plain and their regional character - Jin-fu Lu; Dong-mei Jie; Zhi-min Li; Xue-tian Leng (Chinese Geographical Science, 2000)

Comparative study of platinum‐group elements in the Coto and Acoje blocks of the Zambales Ophiolite Complex, Philippines - Mei‐Fu Zhou; Graciano P. Yumul; John Malpas; Min Sun (Island Arc, 2000)
The Zambales Ophiolite Complex (ZOC), Philippines, includes two geochemically distinct, ophiolitic assemblages: the high‐Al chromitite‐bearing Coto Block and high‐Cr chromitite‐bearing Acoje Block. This paper reports a comparative platinum‐group element (PGE) study of these two blocks. The PGE data were obtained using Ni‐sulfide fire assay preconcentration combined with inductively coupled plasma mass spectrometry (ICP‐MS) measurement. Podiform chromitites in the Acoje Block have higher Cu, Ir, Ru and Rh contents than their equivalents in the Coto Block, although chromitites from both have similar Pt and Pd contents. The PGE mantle‐normalized patterns of dunites from the two blocks are also different: dunites from the Coto Block are depleted in Pt, whereas those from the Acoje Block have a relatively flat pattern. The data demonstrate that Coto and Acoje Blocks have different origins in terms of their source region and partial melting processes. This study implies that the ZOC is a paired ophiolite belt formed in an island arc and back‐arc basin environment.

Comparative study of platinum-group elements in the Coto and Acoje blocks of the Zambales Ophiolite Complex, Philippines - Mei-Fu Zhou; Graciano P. Yumul; John Malpas; Min Sun (Island Arc, 2000)

Inhibition of B16BL6 melanoma invasion by tyrosine and phenylalanine deprivation is associated with decreased secretion of plasminogen activators and increased plasminogen activator inhibitors - Bertha A. Pelayo; Ya-Min Fu; Gary G. Meadows (Clinical & Experimental Metastasis, 1999)

The effect of lanthanide chloride on abscisic acid and electron-transport activity of some crops - Fu Li Zeng; Ming Feng Zhang; Shao Min Zhou; Ji Gui Wu; Ru Wen Deng (Biological Trace Element Research, 1999)

Cloning, Expression and Sequence Analysis of the Classical Swine Fever Virus Nucleocapsid Protein - Jau-Jin Liu; Min-Liang Wong; Po-Fu Chen; Tien-Jye Chang (Virus Genes, 1998)

Organochlorinated Compounds in Waters of the Pearl River Delta Region - Yang Yanhong; Sheng Guoying; Fu Jimo; Min Yushun (Environmental Monitoring and Assessment, 1997)

Determination of Trace Organochlorinated Pesticides and Polychlorinated Biphenyls in Water - Zou Shichun; Zhang Zhanxia; Sheng Guoying; Min Yushun; Fu Jiamo (Environmental Monitoring and Assessment, 1997)